Hormetic UV-C irradiation retards postharvest senescence of Pleurotus ostreatus via ROS metabolism and antioxidant gene upregulation - Hafiz Muhammad Mubeen; Numan Khan; Rouna Li; Jiayi Hu; Yingying Zhang; Muhammad Shahar Yar; Muhammad Bilal; Mei Li (Postharvest Biology and Technology, 2026)

Structural dynamics and stability analysis of a novel ARSK variant confirms its role in MPS type X pathogenesis - Muhammad Bilal; Muhammad Fakhar; Thamir Eid; Nawal Helmi; Misbahuddin Rafeeq; Mehreen Gul; Hammal Khan; Muhammad Umair (Glycoconjugate Journal, 2026)

Increasing long-chain dicarboxylic acid production by pretreating grease trap waste using ceramic ultrafiltration - Boris Gilis; Kristien De Sitter; Muhammad Bilal; Sara Salvador Cob; Paulien Geertje Corlijn Leemans; Inge van Bogaert; Iris Cornet (Bioresource Technology, 2026)

H2O2-modified biochar for BC-g-C3N4/COF heterojunction toward efficient tetracycline degradation - Feng Guo; Qi Wei; Baojun Yi; Ruoyu Leng; Jiaqi Deng; Muhammad Bilal Ahmad; Dongyi Kong (Biomass and Bioenergy, 2026)

Evaluation of the Air Pollution Mitigation Potential of Some Roadside Plants for Urban Forest Management - Mahrukh; Sohaib Muhammad; Muhammad Tayyab; Ali Ahmad; Zaher Uddin Babar; Nahaa M. Alotaibi; Muhammad Bilal; Amr Elkelish; Iqra Parvaz; Bushra Munam; Summiya Faisal; Muhammad Hasnain (Water, Air, & Soil Pollution, 2026)

Dose-dependent neurotoxic effects of anastrozole via disrupting NLRP3 inflammasome and α-synuclein pathways - Amani Alghamdi; Salim Jamil; Abdulaziz Saleh Alkhoshaiban; Muhammad Bilal Azmat; Fuad M. Alzahrani; Khalid J. Alzahrani; Khalaf F. Alsharif; Hesham M. Hassan (Tissue and Cell, 2026)

Calcium signaling coordinates isoflavone and GABA accumulation in germinated soybean under combined UV-B and NaCl stress via energy metabolism reprogramming - Muhammad Bilal; Shijie Fang; Zhijie Yao; Bowen Qin; Chong Xie; Pei Wang; Runqiang Yang (Food Bioscience, 2026)

Retraction notice to ‘Nano-remediation technologies for the sustainable mitigation of persistent organic pollutants’ [Environ. Res. 211 (2022) 113060] - Liu Fei; Muhammad Bilal; Sarmad Ahmad Qamar; Hafiz Muhammad Imran; Areej Riasat; Muhammad Jahangeer; Misbah Ghafoor; Nisar Ali; Hafiz M.N. Iqbal (Environmental Research, 2026)

Reusing end-of-life reverse osmosis membranes: Strategies, challenges, and future perspectives - Zeeshan Arshad; Muhammad Ashraf; Taha Demraoui; Tauqir Ahmad; Muhammad Bilal Asif; Niaz Ali Khan; Mukarram Zubair; Muhammad Irshad Baig; Nisar Ullah; Yasir Abbas; Almotasembellah Abushaban; Nadeem Baig (Desalination, 2026)

Effectiveness of machine learning and deep learning techniques for multi-horizon weather forecasting - Abdullah Sami; Muhammad Bilal; Usman Habib; Adeel Ashraf Cheema (Meteorology and Atmospheric Physics, 2026)

Turning trash into treasure: bioactive peptides from food waste–a decade of progress in extraction, purification, and applications: a systematic review - Muhammad Bilal; Muhammad Usman; Maratab Ali; Samee-Ullah; Faryal Shaukat; Muhammad Arslan; Zhihua Li; Xiaobo Zou; Yemin Guo; Xia Sun (Critical Reviews in Food Science and Nutrition, 2026)

Chronic labetalol exposure induced dose-dependent testicular toxicity via disrupting HPG-axis, spermatogenesis and steroidogenic pathways: A biochemical, molecular and histopathological evidence - Salim Jamil; Fuad M. Alzahrani; Khalaf F. Alsharif; Khalid J. Alzahrani; Muhammad Bilal Azmat; Hesham M. Hassan; Muhammad Tahir Naseem (Tissue and Cell, 2026)

Characterizing dynamic motion and deformation during large rock avalanches using a joint framework integrating computer vision and seismic signal analysis - Yiwei Liu; Aiguo Xing; Wenpei Wang; Qiankuan Wang; Yu Zhuang; Muhammad Bilal; Kaiyue Zhu (Natural Hazards, 2026)

Cylindrospermopsin induces progressive myocardial injury via disrupting sympathetic β-adrenergic pathway and redox homeostasis: A molecular, radiological, and histopathological evaluation - Maha A. Al-Aream; Khalaf F. Alsharif; Fuad M. Alzahrani; Khalid J. Alzahrani; Muhammad Bilal Azmat; Mohamed Eissa; Hesham M. Hassan (Toxicon, 2026)

Retraction notice to “Environmental impact of lignocellulosic wastes and their effective exploitation as smart carriers – A drive towards greener and eco-friendlier biocatalytic systems” [Sci. Total Environ. 722 (2020) 137903] - Muhammad Bilal; Zhaoyu Wang; Jiandong Cui; Luiz Fernando Romanholo Ferreira; Ram Naresh Bharagava; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Pigmented cereals as functional food systems: Linking Phytochemistry, processing, and health - Muhammad Bilal; Zain Ul Abideen; Nabila Murtaza; Beenish Abbas; Hafeesa Rasheed; Muhammad Shahar Yar; Mohamed Fawzy Ramadan; Muhammad Hussain Ghazali (Food Chemistry, 2026)

Microplastics in Urban Wastewater: A Vector for Chemical and Biological Pollutants with Emerging Health Risks - Mamoona Sadia; Abid Mahmood; Muhammad Ibrahim; Bilal Aslam (Environmental Research, 2026)

Retraction notice to “Polyvinyl alcohol and aminated cellulose nanocrystal membranes with improved interfacial compatibility for environmental applications” [Environ. Res. 214 (2022) 113793] - Saleem Ahmad; Zaib Jahan; Farooq Sher; Muhammad Bilal Khan Niazi; Tayyaba Noor; Honghao Hou; Ofaira Azhar; Emina Karahmet Sher (Environmental Research, 2026)

Bifurcation and chaos design of radial basis neural network for predictive modeling of fractional double-strain HIV co-infection model with intercellular delays and stochastic effects - Muhammad Wajahat Anjum; Noreen Sher Akbar; M. Bilal Habib; A. Alzubaidi; S. Saleem (Theory in Biosciences, 2026)

Enhancing resource productivity and system sustainability on the Qinghai-Tibetan Plateau: a type-temporal-spatial coupling approach for forage-livestock balance - Jing Zhang; Nurlan Serekpayev; Muhammad Usman; Naeem Ahmad; Muhammad Bilal Hafeez; Qingping Zhou; Fujiang Hou; Zhibiao Nan (Plant and Soil, 2026)

Maximizing weight loss with cagrisema: a systematic review and GRADE-assessed meta-analysis of randomized controlled trials - Bilal Wazir Khan; Syed AsadUllah Agha; Ihsan Qamar; Muhammad Huzaifa Khattak; Amna Rehman; Tayyaba Ikram Qazi; Shahreena Athar Siddiqui; Nafila Zeeshan; Umer Zaryab Khan; Humaira Bibi; Muhammad Faaz Khan; Haris Wazir Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Long-Term Fermented Chicken Manure (CM) Amendment Enhances Soil Health, Sugar Beet Yield, and Shifts Microbial Functional Diversity - Jianyu Zhang; Songlin Yang; Xiaochen Lin; Shafaque Sehar; Muhammad Ishfaq; Muhammad Riaz; Muhammad Faheem Adil; Saqib Bilal; Xiaoyu Zhao; Jean Wan Hong Yong; Baiquan Song (Sugar Tech, 2026)

Robust Adaptive Propagated Interval Observer for Actuator Fault Diagnosis in Underactuated AUVs - Ishaq Ahmed; Ayman Alharbi; Jun Lu; Amar Jaffar; Muhammad Bilal (Journal of Marine Science and Engineering, 2026)
This paper presents an interval-observer-based actuator fault detection and isolation (FDI) method for underactuated autonomous underwater vehicles (AUVs) under bounded hydrodynamic uncertainty and time-varying ocean currents. A locally frozen linear time-invariant (LTI) representation enables deterministic set-membership analysis, and the robust adaptive propagated interval observer (RAPIO) propagates admissible center–radius state bounds within a Lyapunov framework. Adaptivity is introduced through a reinforcement learning (RL)-augmented uncertainty-bound modulation mechanism, where an offline-trained agent scales a nonnegative channel-wise slack term without modifying the scheduled observer-gain rule or the nominal center predictor. Under the stated observer and disturbance-envelope conditions, positivity, stability, and diagnostic-channel inclusion hold for any bounded learning signal. Actuator loss-of-effectiveness (LoE) faults are represented through the actuator-effectiveness channel and detected through interval-consistency violations, enabling axis-wise isolation of surge, yaw-rate, and pitch-rate actuator faults. The same schedule-blind decision layer is additionally evaluated with structurally distinct additive-bias and stuck/jam actuator models. All stuck/jam events are detected, and bias-magnitude sweeps identify channel-wise 100%-detection boundaries with zero false alarms. A structured 72-case scenario sweep shows reliable detection, strong false-alarm rejection, and acceptable detection delays compared with benchmark observers.

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Retraction notice to “Mitigation of environmental pollution by genetically engineered bacteria — Current challenges and future perspectives” [Sci. Total Environ. 667 (2019) 444–454] - Lina Liu; Muhammad Bilal; Xuguo Duan; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Retraction notice to “Environmental impacts of hazardous waste, and management strategies to reconcile circular economy and eco-sustainability” [Sci. Total Environ. 807 (2022) 150856] - Zhen Zhang; Muhammad Zeeshan Malik; Adnan Khan; Nisar Ali; Sumeet Malik; Muhammad Bilal (Science of The Total Environment, 2026)

Retraction notice to “Environmentally responsive and anti-bugs textile finishes – Recent trends, challenges, and future perspectives” [Sci. Total Environ. 690 (2019) 667–682] - Shahzad Ali Shahid Chatha; Muhammad Asgher; Rabbia Asgher; Abdullah Ijaz Hussain; Yasir Iqbal; Syed Makhdoom Hussain; Muhammad Bilal; Faizan Saleem; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Retraction notice to “TiO2/SiO2 decorated carbon nanostructured materials as a multifunctional platform for emerging pollutants removal” [Sci. Total Environ. 688 (2019) 299–311] - Tahir Rasheed; Muhammad Adeel; Faran Nabeel; Muhammad Bilal; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Retraction notice to “Effective exploitation of anionic, nonionic, and nanoparticle-stabilized surfactant foams for petroleum hydrocarbon contaminated soil remediation” [Sci. Total Environ. 704 (2020) 135391] - Nisar Ali; Muhammad Bilal; Adnan Khan; Farman Ali; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Numerical Analysis of Altitude Effects on Single-Cylinder Two-Stroke UAV Engine Performance - Muhammad Nouman Rashid; Faiq Said; Syed Ghafoor Shah; Muhammad Bilal; Hamza Sultan; Muhammad Qail (Next Research, 2026)

A multi-dimensional accounting framework to resolve the grassland-livestock paradox on the Qinghai-Tibetan Plateau - Jing Zhang; Naeem Ahmad; Muhammad Bilal Hafeez; Muhammad Usman; Qingping Zhou; Fujiang Hou; Zhibiao Nan (Global and Planetary Change, 2026)

Deciphering the role of potato peel on sunflower hybrids growth, photosynthesis, osmoregulation, oxidative defense and ion uptake under salinity - Sundas Fatima; Aasma Tufail; Muhammad Bilal Hafeez; Samreen Nazeer; Noreen Zahra; Fatima Latif; Sabina Asghar; Muhammad Ahsan; Muhammad Hamza; Muhammad Zubair Akram (Biocatalysis and Agricultural Biotechnology, 2026)

Green Synthesis of a ZnO@Sorghum Nano-Bioadsorbent for Enhanced Dye Wastewater Treatment - Muhammad Arslan Khalil; Bushra Sadia; Saima Noreen; Faisal Saeed Awan; Azeem Iqbal Khan; Muhammad Asif; Bilal Ahmad (Water, Air, & Soil Pollution, 2026)

Smart Wastewater Management: Data-Driven Prediction of Wastewater Using Optimized Learning Techniques - Ali Aldrees; Mohammad Jameel; Bilal Siddiq; Muhammad Hussain; Muhammad Faisal Javed; Furqan Ahmad (Water Conservation Science and Engineering, 2026)

Multi-tissue transcriptomics reveals candidate co-expression and metabolic networks associated with low-nitrogen adaptation in oat - Chenyue Yang; Zhongxiang Li; Muhammad Bilal; Yunyun Pang; Mengxin Zhu; Tao Hu (Plant and Soil, 2026)

Engineered biochar as a powerful tool for microplastics removal from wastewater: a critical review - Muhammad Bilal Shakoor; Karolina Mierzyńska; Fakhra Sharif; Piotr Zieliński (Environmental Geochemistry and Health, 2026)

Comparative effects of digestion residue-derived and corn straw biochar on free-living diazotrophs in nitrogen-deficient calcareous purple soil - Junwen Zhao; Yuting Chen; Haiyan Zhang; Yulan Chen; Bing Li; Muhammad Bilal Khan; Yingjie Wu; Xiaoyan Tang; Huanxiu Li; Rong Huang; Qiang Xu; Qiquan Li; et al. (Biology and Fertility of Soils, 2026)

Interannual variation in tree transpirational cooling and its controlling factors in warm-wet and hot-dry biomes - Muhammad Hayat; Liu Ran; Bai Jie; Xu Gui-Qing; Bilal Ahmad (Agricultural and Forest Meteorology, 2026)

Ambient particulate matter in Saudi Arabia (1980–2025): spatiotemporal patterns, source dynamics, and strategic research priorities - Muhammad Amin; Muhammad Bilal; Andi Gulam Alif B. Khutomi (Air Quality, Atmosphere & Health, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Can baxdrostat redefine blood pressure control in resistant and uncontrolled hypertension? a systematic review, meta-analysis, and trial sequential analysis - Bilal Wazir Khan; Muhammad Yahya; Hamza Wazir Khan; Miguel Alejandro Rivas Perez; Tayyaba Ikram Qazi; Humaira Obaid; Muhammad Mustafa Khan; Muhammad Maaz Amjad; Muhammad Faaz Khan; Aneeq Mahmood Khan; Muhammad Junaid Khan; Sajjad Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification of miR-21-5p and miR-21-3p regulated hub genes and drug repurposing targets in cervical cancer: an integrative computational analysis - Muhammad Bilal Azmi; Rafia Wasi; Arisha Sohail; Uzma Asif (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Editorial for the special issue on emerging technologies and future directions in air quality Remote Sensing - Umesh Chandra Dumka; Sanjeev Kimothi; Muhammad Bilal; Pawan Gupta; Persello Claudio (International Journal of Remote Sensing, 2026)

Visual analytics of vaccine hesitancy: mapping sentiment and misinformation flows across digital ecosystems - Shahbaz Aslam; Sobia Abid; Arshad Ali; Babar Hussain; Muhammad Zahid Bilal (Next Research, 2026)

Elucidating the role of ammonia doping in modulating combustion dynamics in ethane fuel-rich jet flames - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Ahmed E. Mansy; Muhammad Yousuf; Kai-Ru Jin; Du Wang; Boyang Su; Aqsa Liaqat; Mohammed Khalil; Zhi-Min Wang; Qingli Li; et al. (Fuel, 2026)

The role of oxygen vacancies and metallic Ru in regulating oxide pathway mechanism for acidic water electrolysis - Dinghua Zhou; Yutian Ding; Tao Song; Jiayi Wu; Zengyu Su; Zhiyong Fang; Muhammad Bilal Hussain; Peili Zhang; Xian-Zhu Fu; Shao-Qing Liu; Shuwen Wu; Jing-Li Luo (Chemical Engineering Journal, 2026)

Fabrication of Magnetic Polyvinyl Alcohol and Polyvinyl Pyrrolidone Ferrite Nanocomposites for the Removal of Reactive Dyes from wastewater by Adsorption Process - Muhammad Hasnain; Abdul Qadir Ahmad; Muhammad Junaid; Anam Zulfiqar; Rizwan Ali; Hafiz Muhammad Waqar Abid; Rajesh Kumar Manavalan; Khalid Bilal; Mahmoud F. Y. Shalaby (Water, Air, & Soil Pollution, 2026)

Multilevel barriers to antimicrobial stewardship in tertiary care hospitals: A comparative systematic scoping review of high-income versus low-/middle-income countries evidence mapped by study design and healthcare professionals - Azfar Athar Ishaqui; Zikria Saleem; Tauqeer Hussain Mallhi; Sultan M. Alshahrani; Khalid Orayj; Salman Ashfaq Ahmad; Rayah Asiri; Emad Ali Alsaleh; Muhammad Imran; Mohammed Ali Kaddoura; Bilal Jawed; Narendar Kumar; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Dynamic fragmentation and entrainment characteristics of a heavily jointed landslide: DEM simulation, field seismic signal, and UAV image analysis - Kaiping Jin; Muhammad Bilal; Ge Gao (Natural Hazards, 2026)

Spatio-temporal analysis of land surface temperature, urban heat island intensity, and urban thermal field variance index in Faisalabad, Pakistan - Muhammad Naveed; Bilal Hussain; Awais Ali; Ayesha Mariam; Abdul Ghafoor; Fozia Allah Ditta; Basharat Ali (Air Quality, Atmosphere & Health, 2026)

Therapeutic targeting of COX-2 in head and neck cancer: Mechanistic and clinical perspectives - Reena Gupta; Bilal Khaleel Midhin; Sabir Ali Siddiqui; Mohammad Abohassan; Pareshkumar N. Patel; Gunjan Singh; Vimal Arora; Priya Priyadarshini Nayak; Muhammad Shahid Iqbal; Zainb A. Taleb (DARU Journal of Pharmaceutical Sciences, 2026)

Phytochemical constituents, nutritional value, and biological activities of Lupinus albus : a review - Asmaa E. Sherif; Laiba Rehman; Abdul Rauf; Ahmed Ashour; Bilal Ahmad Ghalloo; Wadah Osman; Sherouk Hussein Sweilam; Muhammad Ahsan Raza; Tariq M. Aljarba; Kashif-ur-Rehman Khan (Natural Product Research, 2026)

Transboundary smog dynamics: A spatiotemporal assessment of brick kiln emission impacts in Central Punjab, Amritsar, and Ferozepur - Ayesha Naz; Muhammad Farooq Iqbal; Muhammad Imran Shahzad; Muhammad Usman; Bilal Hassan (Urban Climate, 2026)

Tapentadol induces progressive hepatic damage via disrupting Hippo–YAP and bile acid–FXR pathways: An integrated experimental and computational perspective - Han Hu; Salim Jamil; Muhammad Bilal Azmat; Mohammed Alissa; Ghfren S. Aloraini; Amal A. Albati; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

In-situ growth of layer double hydroxides on TFC membranes to improve forward osmosis performance - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Woei Jye Lau (Journal of Environmental Chemical Engineering, 2026)

AACVD-derived Co-Ni alloys for the efficient electrooxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid - Muthumariappan Akilarasan; Muhammad Ali Ehsan; Mohsin Pasha; Maryum Ali; Muhammad Nawaz Tahir; Muhammad Bilal Khan Niazi; Wasif Farooq (Journal of Environmental Chemical Engineering, 2026)

Effects of legume-grass mixtures and systematic pasture management practices on forage yield, nutritive quality and resource use efficiency in an arid region - Muhammad Bilal Hafeez; Weiqi Jiang; Lan Li; Jiao Ning; Adilbek Nogayev; Shanning Lou; Shree Prakash Pandey; Fujiang Hou (Field Crops Research, 2026)

Retraction notice to “Assessment of hepatotoxicity and nephrotoxicity in Cirrhinus mrigala induced by trypan blue - an azo dye” [Environ. Res. 215 (2022) 114120] - Bilal Hussain; Muhammad Sajad; Hassan Usman; Khalid A. Al-Ghanim; Mian Nadeem Riaz; Aydin Berenjian; Shahid Mahboob; Pau Loke Show (Environmental Research, 2026)

Dynamic interaction of lorentz forces and arrhenius thermal kinetics in shear-thinning/thickening fluids through porous medium - S. Bilal; Asadullah; Muhammad Yasir (Dynamics of Atmospheres and Oceans, 2026)

Global evaluation and uncertainty analysis of MODIS Deep Blue and MAIAC aerosol products over bright surfaces - Ping Zhang; Leiku Yang; Xin Pei; Muhammad Bilal; Yuxuan Wang; Yizhe Fan; Xiaoran Lv; Xiaoxia Xue; Weiqian Ji; Xiaofeng Lu; Xiaoqian Cheng (Atmospheric Environment, 2026)

Correlating the Performance of Forward Osmosis Process to the Characteristics of Inorganic Draw Solutions - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Niaz Muhammad; Mohamed Shaban; Sameerah I. Al-Saeedi; A. M. Elbasiony; Woei Jye Lau (Water, Air, & Soil Pollution, 2026)

A Critical Review on Advance Molecular Distortion Techniques for Textile Wastewater Treatment in Pakistan - Sahrish Ashraf; Muhammad Sultan; Muhammad Wakil Shahzad; Muhammad Imran; Rana M. A. Kanwar; Muhammad Nauman Ashraf; Zahid Mahmood Khan; Zubair Khaliq; Muhammad Bilal Qadir (Water, Air, & Soil Pollution, 2026)

Efficacy of Vachellia nilotica Extract-coated Urea in Maize: Field Performance and Phytochemical Basis of Urease Inhibition - Rashid Mahmood; Hina Jabeen; Muhammad Ajmal Rana; Faisal Nadeem; Ejaz Ahmed; Muhammad Bilal Chattha (Journal of Soil Science and Plant Nutrition, 2026)

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

Geochemical and petrographic insights into the Lumshiwal Formation (NW Himalayas): implications for provenance, paleoclimate, and economic potential - Syed Nohman Gilani; Muhammad Saleem Mughal; Khawaja Umair Majeed; Hammad Tariq Janjuhah; Yongzhi Wang; Muhammad Atif Bilal; Ahmer Bilal; Syed Wajee-Ul Hassan Gillani; Muhammad Hafeez (Carbonates and Evaporites, 2026)

Geospatial analysis of surface urban heat island dynamics and land use changes in Pakistan using multi-spectral indices - Awais Ali; Bilal Hussain; Muhammad Naveed; Bader Alshehri; Abdul Ghafoor; Zeeshan Zafar; Faisal Sultan Qadri (Advances in Space Research, 2026)

Foliar application of silicon alleviates adverse effect of drought stress by improving growth, physiological attributes, and antioxidant defense of camelina (Camelina sativa L.) - Bilal Ahmad Shahzad; Ejaz Ahmad Waraich; Muhammad Saleem; Saddam Hussain; Saifullah (Acta Physiologiae Plantarum, 2026)

Comment on “Validity study of the Turkish version of the Mini-Addenbrooke’s cognitive examination in mild cognitive impairment and Alzheimer’s disease” - Marwa Mehak; Warda Fatima Shafee; Muhammad Hamza Shafee; Bilal Ahmad (Acta Neurologica Belgica, 2026)

Slow-Release DAP Fertilizer Coated with Bacillus velezensis FB2 and Polyvinyl Alcohol for Sustainable Maize Production - Zumrah Rehman; Muhammad Bilal Khan Niazi; Zaib Jahan; Ghulam Abbas Shah; Hazrat Ali; Zia Ur Rahman Farooqi; Waqas Mohy-Ud-Din; Qasim Ali; Gamal Awad El-Shaboury; Haitham Ibrahim El-Mekkawy (Journal of Soil Science and Plant Nutrition, 2026)

Pharmacological profiling of medicinal plants: a contemporary overview - Bilal Aslam; Muhammad Rehan Sajid; Asif Hussain; Ifraha Abbas (Natural Product Research, 2026)

Spatiotemporal analysis of climatic and anthropogenic drivers of winter smog in the Indo-Gangetic Plain with a focus on Lahore - Muhammad Zeeshan Ghani; Mujtaba Hassan; Farrukh A. Chishtie; Syeda Saleha Fatim Ali; Syed Waqar Hussain Shah; Ahmad Bilal (Environmental Science and Pollution Research, 2026)

Trade adjusted carbon emissions and renewable energy electricity output: Evidence from method of moment quantile regression for N-11 economies - Maaz Amin; Salman Wahab; Bilal Ahmed; Muhammad Imran; Shahid Ali; Sakiru Adebola Solarin (Environment, Development and Sustainability, 2026)

Temporal transferability of spatially derived Manning’s roughness across flood regimes in the Mississippi River - Muhammad Bilal Zafar; Mantha S. Phanikumar (Journal of Hydrology, 2026)

Carvacrol-enriched chitosan/berry wax active films via Pickering emulsion: a sustainable solution for extending meat shelf-life - Suliman Khan; Ke Zhang; Sulafa B.H. Hashim; Mohammad Rezaul Islam Shishir; Naymul Karim; Muhammad Bilal; Zhihua Li; Xiaodong Zhai; Xiaobo Zou; Fujun Li (Food Chemistry, 2026)

Proton exchange membranes with monolayer graphene nanosheet nanofillers for direct methanol fuel cells - Muhammad Bilal; Kaiqiang He; Jun Lu; Zhikao Li; Jacek Jasieniak; Huanting Wang (Chemical Engineering Journal, 2026)

Assessment of Protective Role of Different Probiotic Strains against Bacterial and Endotoxin-Induced Sepsis in a Mouse Model - Sabeeka Sajjal; Hasnat Ahmad Bilal; Ambreen Zahra; Ayesha Saeed; Aiman Khan; Muhammad Musa Mubashar; Aisha Khatoon; Muhammad Imran Arshad (Probiotics and Antimicrobial Proteins, 2026)

Association of oral metoprolol exposure during heart failure hospitalization with death or readmission at 28-days and 6-months using a propensity score overlap-weighted EHR analysis - Azfar Athar Ishaqui; Emad Ali Alsaleh; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Khalid Orayj; Rayah Asiri; Sultan M. Alshahrani; Salman Ashfaq Ahmad; Narendar Kumar; Adnan Iqbal; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative disproportionality signals for methotrexate monotherapy versus methotrexate combined with hydroxychloroquine, leflunomide, or sulfasalazine in rheumatoid arthritis: newly highlighted signals evaluated using drug information safety profiles - Azfar Athar Ishaqui; Khalid Orayj; Zeeshan Ahmed; Salman Ashfaq Ahmad; Sultan M. Alshahrani; Rayah Asiri; Adnan Iqbal; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Optimum N Fertilization Enhances Salinity Tolerance and N use Efficiency in Maize through Modulation of Antioxidant Defense and Biochemical Pathways - Syed Ayyaz Javed; Muhammad Tauseef Jaffar; Muhammad Ashraf; Muhammad Ahmed; Ali Raza Siddiqui; Hafiz Muhammad Bilal; Jawad Amin; Sanaullah Sattar (Journal of Plant Growth Regulation, 2026)

Dichlorvos toxicity on hemato-biochemical, histopathological, and behavioral parameters in the grass carp (Ctenopharyngodon idella) - Mehvish Saleem; Cristiana Roberta Multisanti; Sana Ullah; Wardah Fazal; Muhammad Sohail; Muhammad Bilal; Muhammad Kashif Ashraf; Caterina Faggio (Ecotoxicology, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

Chasing development, breathing danger: health and economic losses from urban PM2.5 and O₃ pollution in the Yangtze River Delta, China - Fang Liu; Junyao Wang; Muhammad Bilal; Binxiu Xu (Air Quality, Atmosphere & Health, 2026)

The impact of green brand image and green perceived risk on green trust and green purchase intention: the moderating role consumption values - Bilal Ahmed; Salman Wahab; Muhammad Imran; Muhammad Imran; Nawaz Ali Shah; Shamsher Ali (Environment, Development and Sustainability, 2026)

A review of premise plumbing systems: from design and key performance domains to challenges and future research pathways for full-scale integration - Muhammad Bilal; Steven G. Sandi; Brendan M. Josey; Jinzhe Gong (Water Research, 2026)

Saxitoxin induces progressive myocardial injury via disrupting calcium-dependent excitation-contraction coupling pathway: A biochemical, radiological, and histological evaluation - Mohammed S. Alshammari; Muhammad Bilal Azmat; Mohammed Alissa; Abdullah Alghamdi; Suad A. Alghamdi; Mohammed A. Alshehri; Ghfren S. Aloraini; Ghada M. Alnafesah (Tissue and Cell, 2026)

Root inoculation with Trichoderma harzianum primes metabolic and stress-response pathways underlying growth and resistance in Brassica rapa - Bilal Ahmad; Aleena Alam; Sohail Abbas; Muhammad Ameer Hamza; Khalid Ali Khan; Hamed A. Ghramh; Raul Narciso C. Guedes; Qiyun Li; Rizhao Chen (Pesticide Biochemistry and Physiology, 2026)

Observation-based evidence reveals increased control of tree traits rather than hydroclimate on tree transpirational cooling across global regions - Muhammad Hayat; Liu Ran; Bai Jie; Xu Gui-Qing; Bilal Ahmad (Journal of Environmental Management, 2026)

New frontiers in beverage fortification: Delivery of functional ingredients via micro- and nanoencapsulation in dairy and non-dairy beverages - Mohammad Rezaul Islam Shishir; Suliman Khan; Naymul Karim; Muhammad Bilal; Sarfaraz Hussain; Md Saifullah; Ahmed K. Rashwan; Haroon Elrasheid Tahir; Isam A. Mohamed Ahmed; Xinhua Zhang; Fujun Li (Food Research International, 2026)

Retraction notice to ‘In-house fabrication of macro-porous biopolymeric hydrogel and its deployment for adsorptive remediation of lead and cadmium from water matrices’ [Environ. Res. 214 (2022) 113790] - Muhammad Khalid Azeem; Muhammad Rizwan; Atif Islam; Atta Rasool; Shahzad Maqsood Khan; Rafi Ullah Khan; Tahir Rasheed; Muhammad Bilal; Hafiz M.N. Iqbal (Environmental Research, 2026)

Predictive Machine Learning for Seasonal Water Quality Insights - Zouhaib Ali; Muhammad Bilal; Sallahuddin Panhwar; Muhammad Junaid; Hareef Ahmed Keerio; Israr Hussain (Water, Air, & Soil Pollution, 2026)

Comparative tissue level uptake of Lithium and Potassium across four urban tree species - Sahar AbdulHaq; Rida-Tuz- Zohra; Zafar Siddiq; Muhammad Umar Hayyat; Bushra Bilal (Trees, 2026)

Seismotectonic Analysis of Pabbi Blind-Thrust in the NW Himalayan Foreland: Evidence from the 2024 Kharian Earthquake - Mohammad Tahir; Bilal Saif; Raja Adnan Habib; Farhan Javed; Muhammad Zafar Iqbal; Talat Iqbal; Nasir Mahmood; Najeeb Ahmed (Pure and Applied Geophysics, 2026)

Probiotic-Derived Bacteriocins for Veterinary Biofilm Control: Mechanisms, Evidence, and One Health Translation - Muhammad Hassan Khalid; Farwa Farooq; Bilal Aslam; Muhammad Saria (Probiotics and Antimicrobial Proteins, 2026)

Innovative Approaches to Combat Antimicrobial Resistance: A Review of Emerging Therapies and Technologies - Mujeeb Ur Rahman; Junaid Ali Shah; Muhammad Nadeem Khan; Hazrat Bilal; Daochen Zhu; Zongjun Du; Da-Shuai Mu (Probiotics and Antimicrobial Proteins, 2026)

Development of cytarabine-loaded pH-responsive polymeric hydrogel: an in vitro and in vivo evaluation - Shaheer Khalid; Sharjeel Adnan; Asif Mahmood; Rai Muhammad Sarfraz; Hira Ijaz; Muhammad Farooq; Bilal Haroon (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Chaotic transitions and multistable regimes in a nonlinear wave model through hybrid analytical–numerical techniques - Muhammad Iqbal; Syeda Sarwat Kazmi; Muhammad Bilal Riaz; Muhammad Aziz Rehman (Modeling Earth Systems and Environment, 2026)
The modified Zakharov–Kuznetsov (mZK) model is a fundamental framework for describing nonlinear phenomena in plasma oscillations, optical systems, discrete electrical lattices, and oceanic wave dynamics. In this work, we establish a unified framework that combines exact solution construction with dynamical systems analysis of the mZK equation. Using the modified Khater method and the Sardar subequation technique under a traveling wave transformation, we derive new and more general families of solitary traveling wave solutions, including trigonometric, hyperbolic, rational, exponential–rational, and complex soliton forms. We show how free parameters govern the existence, shape, and stability of these solutions, with two- and three-dimensional MATLAB simulations illustrating their structures. Furthermore, we reformulate the mZK equation as a planar dynamical system and classify its qualitative features through phase portraits, identifying centers, saddles, and cusps. With the inclusion of periodic external forcing, the reduced system displays bifurcation and chaos, following a period-doubling route with multistability and sensitivity to parameter variations. To the best of our knowledge, this is the first study that simultaneously delivers exact soliton solutions and a complete nonlinear dynamics characterization of the mZK equation. This integrated approach provides a novel template for investigating broader classes of nonlinear evolution equations.

Assessing lead toxicity induced alterations in expression of transmembrane metal transporter OsHMA9 and physio-biochemical activities of canola - Khalid Bilal; Nosheen Noor Elahi; Muhammad Imtiaz; Abebe Bogale; Esmael M. Alyami; Norah Hamdi; Tawaf Ali Shah; Ahmad Mohammad Salamatullah (BioMetals, 2026)

Molecular Characterization of Oculocutaneous Albinism in Consanguineous Pakistani Families: Unraveling Disease-Causing Pathogenic Variants in OCA2 and TYR Genes for Precision Diagnosis - Haiba Kaul; Shagufta Naz; Hafiz Ishfaq Ahmad; Nameerah Saleem; Muhammad Shakil; Sabika Firasat; Bilal Majeed; Saima Sharif; Farzana Rashid; Abdullah Etezaz; Muhammad Umer Khan (Biochemical Genetics, 2026)

Reservoir Quality Evolution in the Permian Wargal Carbonate Ramp, Western Salt Range, Pakistan - Bilal Ahmed; Huafeng Tang; Shahzad Bakht; Muhammad Yousuf Jat Baloch (Journal of Marine Science and Engineering, 2026)
The Permian Wargal Formation of the western Salt Range preserves a shallow marine carbonate-ramp succession, in which heterogeneity reflects coupled depositional architecture, facies-selective diagenesis, and deformation-related structural compartmentalisation of the Wargal interval. This study integrates balanced restoration with stratigraphic logging, microfacies analysis, paragenetic reconstruction, and quantitative pore-network topology to evaluate how stratigraphic packaging and diagenetic overprint govern connected pathway development within a structurally partitioned fold–thrust setting. Balanced restoration of a representative transect yields 1.1336 km of minimum tectonic shortening (18.7%) and indicates shortening shared between thrust slip and distributed folding, providing an admissible geometric framework for assessing compartmentalisation. The Wargal succession is ~130 m thick and organised into three carbonate packages bounded by laterally persistent argillaceous marker intervals (~21–23 m and ~98–105 m), with grain-supported shoal to shoal-margin facies dominating intervening units. Diagenesis is strongly facies-selective; grain-supported microfacies record progressive calcite cementation that occludes pore throats, whereas mud-supported facies retain microporosity but are preferentially modified by neomorphism, compaction, and pressure-solution fabrics. Image-based analysis of 20 thin-section fields of view shows that pore connectivity varies systematically among microfacies and that a connectivity-weighted index (Iconn) covaries more closely with skeleton-derived connectivity than with segmented areal porosity (ϕ2D=0.124–9.750%). The combined results quantify the decoupling between pore volume and connectivity and provide a basis for predicting reservoir-quality evolution from facies architecture, diagenetic sequence, and structural segmentation, with direct relevance to subsurface characterisation of marine carbonate successions in hydrocarbon systems.

Exploiting endogenous Protoporphyrin IX for Photodynamic inactivation of Pseudomonas aeruginosa - Muhammad Bilal; Rabia Anjum; Sana Imtiaz; Muhammad Saleem (Journal of Fluorescence, 2026)

Susceptibility of two super elite basmati rice varieties cultivated in Pakistan to Whitebacked Planthopper (WBPH) Sogatella furcifera Horváth (Hemiptera: Delphacidae); A life–table bioassay - Muhammad Rizwan; Misbah Rizwan; Arshed Makhdoom Sabir; Muhammad Tahir; Bilal Atta; Tahir Hussain Awan (International Journal of Tropical Insect Science, 2026)

Biochar pyrolysis temperature determines the efficacy of 3, 4-dimethylpyrazole phosphate (DMPP) in reducing N2O emissions from low cadmium-contaminated paddy soil - Muhammad Laeeq Ur Rehman HASHMI; Muhammad Zia Ur Rahman HASHMI; Yasir HAMID; Bilal HUSSAIN; Tang SHENG; Wenjie LIU; Adnan ARSHAD; Tingqiang LI (Pedosphere, 2026)

Environment driven consumer psychological behavior based MPC energy model: a multi-dimensional digital twins framework using deep learning - Bilal Khan; Sahibzada Muhammad Ali; Zahid Ullah (Energy and Buildings, 2026)

Grease trap waste, a renewable resource for biosynthesis of long-chain dicarboxylic acids using Candida tropicalis ATCC 20962 - Boris Gilis; Muhammad Bilal; Kristien De Sitter; Inge Noëlle Adrienne Van Bogaert; Iris Cornet (Bioresource Technology, 2026)

Chitosan-mediated elicitation enhanced production of secondary metabolites and antioxidant assays in callus culture of Ocimum bacilicum L. (Purple Basil) - Gouhar Zaman; Samah Saleh Al-Shybany; Muhammad Naeem Bajwa; Muhammad Salman Khan; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Sulfur-Coated Urea Improves Rice productivity, Nitrogen Use Efficiency, and Soil Nitrogen Dynamics Under Alternate Wetting and Drying System - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Muhammad Bilal Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Umair Hassan; Uthman Balgith Algopishi; Mohamed Hashem; Sezai Ercişli (International Journal of Plant Production, 2026)

Retraction Note: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2026)

Hydrogeochemical dynamics of sub-Himalayan springs: assessing health risks and environmental impacts in Muzaffarabad, Pakistan - Mansoor Awan; Abrar Niaz; Ahmer Bilal; Muhammad Saleem Mughal; Li Yang; Xingyue Qu; Ali Yousaf Khan (Carbonates and Evaporites, 2026)

Land tenure, autonomy and crop choice: Institutional drivers of agricultural diversification in Uzbekistan - Muhammad Bilal; Pishenbay Umirbekov; Nodir Djanibekov; Abdusame Tadjiev; Bakhrom Mirkasimov (Agricultural Systems, 2026)

Exploring Fungal Diversity Through COI Primers: A Nontargeted eDNA Approach - Muhammad Asif Qayyoum; Muhammad Binyamin Khan; Hajra Saddique; Bilal Saeed Khan; Saowaluck Tibpromma; Dao‐Chao Jin; Ting Chi Wen; Tian‐Ci Yi (New Zealand Journal of Botany, 2026)
The broad amplification potential of COI primers, typically designed for arthropods, unexpectedly revealed fungal DNA alongside arthropod data in our assessment of fungal communities across tropical (Hainan, China) and nontropical (Guizhou, China) rainforests using eDNA metabarcoding of 96 samples. This nontarget finding demonstrates the ability of COI‐based metabarcoding to capture fungal diversity in previously unexplored ambient samples. Our results showed very different biogeographical patterns. For example, in Hainan, mixed land use (MIX) resulted in a complete collapse of diversity (Shannon = 0.00), whereas in Guizhou, some diversity remained (Shannon = 0.28). In the tropics, diversity decreased by 90%; in the nontropics, by 64%. This increased sensitivity was associated with pronounced habitat specialization, as organic matter (OM) environments exhibited the highest diversity in Hainan (Shannon = 3.73). A GLM showed that OM had the biggest positive effect (estimate = 3.815, p p = 0.653). However, 33% of the Guizhou samples revealed a continuous lack of diversity over the years, indicating population extinction. The primary driver of community structure was habitat type, as confirmed by PERMANOVA ( R 2 = 0.301, p = 0.001). In the tropics, MIX resulted in an 87% loss of diversity, whereas in Guizhou the effects were nonsignificant ( p = 0.207). This indicates that tropical mushrooms are at risk of catastrophic collapse due to niche specialization, necessitating immediate protection of OM‐rich habitats. On the other hand, nontropical systems require restoration to address the instability caused by dispersal limitation.

Heavy-metal pollution in the Jhelum River (Pakistan) alters hematological and biochemical biomarkers and drives tissue bioaccumulation in Wallago attu - Muhammad Bilal; Sana Ullah; Muhammad Kashif Ashraf; Caterina Faggio; Cristiana Roberta Multisanti (Biological Trace Element Research, 2026)

Homopterocarpin alleviates methoxychlor-induced hepatotoxicity via modulating thioredoxin/peroxiredoxin and TLR4/MyD88 pathway: A comprehensive biochemical, histopathological, and computational analysis - Mansour Abdulaziz Alsaleem; Salim Jamil; Abdulaziz Saleh Alkhoshaiban; Muhammad Bilal Azmat; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Synergistic Particle Swarm Optimized Bio-inspired Artificial Neural Network for Fractional Analysis of tumor-immune competitive system with multiple time delays - Muhammad Wajahat Anjum; Noreen Sher Akbar; Muhammad Bilal Habib; Taseer Muhammad (Swarm and Evolutionary Computation, 2026)

Multifunctional bio-composite hydrogels: PolyAMPs-tuned hydroxyapatite-PVA/gelatin systems development and characterization - Anum Ayub Awan; Waheed Miran; Muhammad Bilal Khan Niazi; Zakir Hussain; Aqeel Afzal; Usman Liaqat (Sustainable Chemistry and Pharmacy, 2026)

Synergistic effects in FeP4-NPC-CP Nanocomposites electrocatalysts for Boosted nitrate reduction to ammonia - Ya-Fei Guo; Sajid Mahmood; Anum Bilal; Ali Bahadur; Shahid Iqbal; Ali Hussain; Muhammad Sajjad; Syed Kashif Ali; Salah Knani (Fuel, 2026)

High Adsorption Potential of Co-Pyrolyzed Biochars for Acid Blue 93 in Wastewater - Dania Majeed; Muhammad Bilal Shakoor; Muhammad Awais; Naeem Akhtar Abbasi (Water, Air, & Soil Pollution, 2026)

Synergistic potential of clove oil and Bacillus culture filtrates (CFs) in suppressing the natural infection of Fusarium wilt pathogen in tomato - Muhammad Imran; Munirah F. Aldayel; Maryam M. Alomran; Reham A. Abd El Rahman; Kamal A. M. Abo-Elyousr; Muhammad Saqib Bilal; Zhongke Sun (Plant and Soil, 2026)

Phosphorene based nano-sensors for mycotoxins in food products: a review - Bilal Afzal; Nuzhat Jamil; Khadija Gull; Muhammad Yasir; Qudsia Kanwal; Toheed Ahmed; Attaullah Bukhari (Mycotoxin Research, 2026)

Apocynin Loaded pH-Sensitive Nanoparticles Based Transdermal Hydrogel: an Innovative Therapeutic Approach against Rheumatoid Arthritis - Raskha Akbar; Dildar Khan; Muhammad Bilal Sabir; Irfa Basharat Rajput; Mona Al Hamod; Asim. ur. Rehman; Naz Dilawar; Shefaat Ullah Shah; Sakina Niyazi; Abdullah R. Alanzi; Hattan A. Alharbi; Kifayat Ullah Shah (Journal of Pharmaceutical Innovation, 2026)

Sodium carbonate and sodium chloride as elicitors of secondary metabolite production in callus cultures of Fagonia indica - Muhammad Uzair Javed; Muhammad Asad Ullah; Tehreem Mahmood; Taimoor Khan; Iva Viehmannova; Anmol Akbar; Yasir Khan; Tariq Khan; Bilal Haider Abbasi; Christophe Hano; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2026)

Photoperiod and temperature: Key abiotic drivers of horticultural crop physiology in a changing climate - Muhammad Atiq Ashraf; Shumaila Nawaz; Uzma Bilal; Maria Abubakar; Shumaila Anam; Muhammad Azam; Burhan Khalid; Abdullah; Muhammad Asim; Rabbya Rayan Shah; Muhammad Ateeq (Biologia, 2026)

Status of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) on cauliflower, Punjab, Pakistan - Dilbar Hussain; Muhammad Sohail Qadir; Muhammad Asrar; Muhammad Saleem; Usama Saleem; Zeeshan Javed; Kanwal Hanif; Arshed Makhdoom Sabir; Ijaz Haider; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal (International Journal of Tropical Insect Science, 2026)

Convolutional autoencoders for low probability of detection constrained underwater acoustic communications - Mohsin Abrar Khan; Songzuo Liu; Muhammad Bilal; Ahmad Hassan (Ocean Engineering, 2026)

Computational prediction of thermomechanical properties in ionic liquid-modified MWCNT/carbon fiber composites - Bilal Ghafoor; Faisal Ghafoor; You Jinglin; Muhammad Shakeel Ahmed; Masood Ahmed; Silvia Tamborim; Sandro Campos Amico; Henri Stephan Schrekker (Next Research, 2026)

Comparative analysis of combustion behavior of raw and torrefied biomass pellets in a customized high-temperature flat flame furnace - Khuda Bukhsh; Rui Li; Muhammad Bilal Ahmad; Yunzeng Zhao; Zhongfa Hu; Shuangling Yue; Tedla Medhane Embaye; Xiandong Li; Zia ur Rahman; Xuebin Wang; Shuanghui Deng; Zongqing Bai (Fuel, 2026)

Retraction notice to ‘Quorum sensing - a promising tool for degradation of industrial waste containing persistent organic pollutants’ [Environ. Pollut. Part-B, 292 (2022) 118342] - Sonam Tripathi; Ram Chandra; Diane Purchase; Muhammad Bilal; Raja Mythili; Sangeeta Yadav (Environmental Pollution, 2026)

Long-term validation and error analysis of MODIS and VIIRS dark target aerosol products in Africa - Xiaoxia Xue; Leiku Yang; Ping Zhang; Muhammad Bilal; Weiqian Ji; Xin Pei; Yizhe Fan; Xiaofeng Lu; Xiaoqian Cheng (Atmospheric Research, 2026)

Wheat-Berseem intercropping system enhances soil fertility, carbon sequestration and crop productivity under nutrient-deficient conditions - Zafar Iqbal; Sundas Bilal; Sana ur Rehman; Imran Haider; Maryam Saeed; Maqshoof Ahmad; Muhammad Ali Raza; Mehraj A. Abbasov; Walid Soufan (Plant and Soil, 2026)

Intravenous thrombolysis as an adjunct to endovascular thrombectomy in acute basilar artery occlusion: a GRADE-assessed systematic review and meta-analysis - Shree Rath; Umama Alam; Aamna Kashif; Muhammad Ansab; Hafiza Tooba Siddiqui; Muhammad Burhan; Zarar Ahmad Khan Afridi; Ahmad Khan; Aiman Gulalay; Bilal Aslam; Raheel Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Extended reduced versus full-dose treatment with factor Xa inhibitors in patients with venous thromboembolism: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Muhammad Abdullah Ali; Muhammad Ansab; Shree Rath; Fazia Khattak; Zaryab Bacha; Hafiza Tooba Siddiqui; Fatima Sajjad; Abdullah Afridi; Zarar Ahmad Khan Afridi; Osama Ahmad; Abdul Moiz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Anti-arthritic appraisal of Acorus calamus L. extracts in complete Freund’s adjuvant‑induced arthritic Wistar rats via regulating inflammatory cytokines and OPG/RANKL pathway - Muhammad Usman Bari; Asif Hussain; Bilal Aslam; Zia-ud-Din Sindhu; Muhammad Rehan Sajid; Rifat Ullah Khan (Inflammopharmacology, 2026)

Balancing efficacy and resistance: oils vs. synthetic acaricides in the control of Panonychus citri - Muhammad Asif Qayyoum; Syed Husne Mobarak; Bilal Saeed Khan; Rehan Inayat; Asad Nawab; Tian-Ci Yi (Experimental and Applied Acarology, 2026)

Exploring smart solutions for stressed soils: dual-action of culture filtrates and nanoparticles for sustainable onion cultivation - Muhammad Imran; Maryam M. Alomran; Hanan A. Khalifa; Muhammad Saqib Bilal; Atef F. Ahmed; Esmat F. Ali; Abeer S. Alqurashi; Munirah F. Aldayel; Kamal A. M. Abo-Elyousr (European Journal of Plant Pathology, 2026)

Integrated assessment of groundwater potential and quality in a seismically active Himalayan city: a case study from Muzaffarabad, Pakistan - Raja Dilawar Sajjad; Abrar Niaz; Ahmer Bilal; Muhammad Tayyib Riaz; Ali Yousaf Khan; Xiwu Luan (Environmental Geochemistry and Health, 2026)

Sustainable food packaging: Life cycle assessment, recycling innovations, and Pestalotiopsis microspora in biodegradable solutions - Muhammad Bilal; Muhammad Arslan; Suliman Khan; Jiyong Shi; Zhihua Li; Yemin Guo; Xia Sun; Zou Xiaobo (Trends in Food Science & Technology, 2025)

Reimagining human creativity and learning in the age of generative AI: A multi-method meta-thematic synthesis - Muhammad Bilal Zafar; Hassnian Ali; Talha Yasin (Next Research, 2025)

Innovative Fe-F-Co-doped NiO nanoarrays: Pioneering high-efficiency electrochemical nitrate reduction to ammonia - Anum Bilal; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Khan; Imran Mahmood Khan; Muhammad Sajjad; Shahid Ali; Nicholas M. Musyoka; Guocong Liu; Abd-ElAziem Farouk; Nouf M. Alyami (Journal of Environmental Chemical Engineering, 2025)

Seismically induced soft-sediment deformation in alluvial fans: mechanisms and implications for geological evolution of the Ordos Basin (China) - Ahmer Bilal; Renchao Yang; Shaojie Chen; Nils Lenhardt; Muhammad Saleem Mughal; George Kontakiotis (Journal of Asian Earth Sciences, 2025)

Dynamic variation of bioactive compounds and techno-functional components of dough fortified with wheatgrass powder during steaming process - Muhammad Bilal; Hoang Trung; Chengpu Chen; Muhammad Shahar Yar; Dandan Li; Chong Xie; Runqiang Yang; Dong Jiang; Pei Wang (Food Chemistry, 2025)

Glucono-δ-lactone-induced gel fabrication of soybean protein isolate derived from germinated soybean: Focusing on protein aggregation and gelation - Guannan Liu; Sijin Wu; Shijie Fang; Yi Wang; Muhammad Bilal; Shujun Shen; Chong Xie; Pei Wang; Runqiang Yang (Food Hydrocolloids, 2025)

Retraction notice to “Citric acid-capped NiWO4/Bi2S3 and rGO-doped NiWO4/Bi2S3 nanoarchitectures for photocatalytic decontamination of emerging pollutants from the aqueous environment” [Environ. Res. Volume 212, Part B, September 2022, 113276] - Hina Liaquat; Muhammad Imran; Shoomaila Latif; Sajid Iqbal; Nazim Hussain; Muhammad Bilal (Environmental Research, 2025)

Retraction notice to “Development of reduced graphene oxide-supported novel hybrid nanomaterials (Bi2WO6@rGO and Cu-WO4@rGO) for green and efficient oxidative desulfurization of model fuel oil for environmental depollution” [Environ. Res., Part A, 212 (2022), 113160] - Aqsa Riaz; Muhammad Saeed; Mamoona Munir; Azeem Intisar; Sabah Haider; Shahzaib Tariq; Nazim Hussain; Rehana Kousar; Muhammad Bilal (Environmental Research, 2025)

Investigation of N-desmethyl-acetamiprid-induced neurotransmitter disturbances in cerebrospinal fluid from leukemia patients - Mengya Si; Muhammad Nadeem Khan; Hazrat Bilal; Muhammad Shafiq; Sabir Khan; Xiaoling Guo; Meimei Wang; Jilong Wu; Wang Zhen; Fen Yao; Adela Jing Li; Xiaoyang Jiao (Environmental Toxicology and Pharmacology, 2025)

Mixed convective heat transfer enhancement in hybrid nanofluid flow through complex-finned tube cavities - Noreen Sher Akbar; Salman Akhtar; Shakil Shaiq; Muhammad Fiaz Hussain; Taseer Muhammad; M. Farooq; M. Bilal Habib (Dynamics of Atmospheres and Oceans, 2025)

High accuracy computational approach to study Casson hybrid nanofluid flow under induced magnetic field inside wavy walls configuration having peristaltic motion with entropy generation - Noreen Sher Akbar; Javaria Akram; S. Ijaz; Zaib Jahan; Taseer Muhammad; Muhammad Bilal Habib; M. Fiaz Hussain; M. Farooq (Dynamics of Atmospheres and Oceans, 2025)

Collateral damage of neonicotinoid insecticides: Unintended effects on gut microbiota of non-target organisms - Muhammad Nadeem Khan; Hazrat Bilal; Sabir Khan; Muhammad Shafiq; Xiaoyang Jiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Sacrificial agent-free H2O2 production driven by S-scheme photocatalysis over hierarchical ZnO/UiO-66-NH2 heterojunction - Muhammad Adnan Qaiser; Jinhe Li; Wei Ren; Shahid Khan; Syed Bilal Ahmed; Waqar Ahmad Qureshi; Mohamed Hussein Abdurahman; Weikang Wang; Qinqin Liu (Chemical Engineering Journal, 2025)

Impact of Tannery Effluents on Groundwater Quality and Human Health in Kasur, Pakistan - Mohammad Salman Faisal; Muhammad Awais; Rohina Bashir; Muhammad Bilal Shakoor; Rizwan Aziz; Muhammad Rizwan; Affaq Ali; Simal Akhtar; Noor Fatima (Water, Air, & Soil Pollution, 2025)

Whitefly-Resistant Population Development Source Selection Among Cotton Germplasms of Pakistan Through Multivariate Tools - Obad Ul Rahman; Syed Bilal Hussain; Muhammad Javed (Plant Molecular Biology Reporter, 2025)

Genomic insights into autosomal recessive epilepsy: novel pathogenic variants in ITPA and CLN5 identified in consanguineous families - Anees Muhammad; Fawad Inayat; Bilal Ahmad Sethi; Muhammad Kashif; Assad Ullah Khan; Shahzad Ahmad; Amir Atlas; Shoaib Ur Rehman; Muhammad Tahir Sarwar (Molecular Biology Reports, 2025)

Dynamics of urinary tract infections: a comprehensive study on antimicrobial susceptibility, virulence profiling and molecular epidemiology of uropathogenic Escherichia coli from Pakistan - Zia Ashraf; Muhammad Hidayat Rasool; Bilal Aslam; Hasan Ejaz; Fatima Mujahid; Mohsin Khurshid (Molecular Biology Reports, 2025)

Dynamical transitions and multistability in nonlinear wave systems: dual analytical insights into the geophysical Korteweg–de Vries Equation - Muhammad Iqbal; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman; Mohie M. Alqezweeni (Modeling Earth Systems and Environment, 2025)

Consortium of Endophytic Bacillus australimaris CK11 and Staphylococcus epidermidis CK9 from Commiphora gileadensis Mediates Tomato Resilience to Combined Salinity, Heat, and Drought Stresses - Syed Saad Jan; Nasir Ali Khan; Sajjad Asaf; Raheem Shahzad; Lubna; Muhammad Imran; Saqib Bilal; In-Jung Lee; Ahmed Al-Harrasi (Journal of Plant Growth Regulation, 2025)

Green Synthesis of Mangifera Indica Mediated NiO and NiMn2O4 Nanomaterials for Electrocatalytic Water Splitting - Fatima Masood; Shabbir Hussain; Muhammad Arif; Shahzad Murtaza; Muhammad Imran; Muhammad Bilal Tahir; Khurram Shahzad Munawar; Hamad M. Alkahtani; Amer Alhaj Zen; Syed Adnan Ali Shah (International Journal of Environmental Research, 2025)

Microfacies analysis and depositional environment of Eocene Chorgali formation at Khanpur Dam Road Section, Hazara Basin, Pakistan - Bilal Shah; Syed Mamoon Siyar; Salman Khurshid; Dicky Muslim; Raden Irvan Sophian; Zahid Ullah; Abdul Wahid Asykarulloh; Asad Muhammad; Syed Muhammad; Wasim Sajjad (Carbonates and Evaporites, 2025)

Dolomitized stromatolites during regressive-transgressive cycles in the Cambrian Abbottabad Formation, Pakistan: depositional environment, sequence stratigraphic significance, and paleogeographic implications - Syed Kamran Ali; George Kontakiotis; Tariq Mahmood; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Ahmer Bilal; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2025)

Ex-situ multi-media bioleaching and functional characterization of indigenous fungal strains for chromium and zinc remediation in polluted soils - Ibrar Khan; Muhammad Bilal Akram; Aneela Rehman; Mujaddad Ur Rehman; Tawaf Ali Shah; Saad A. Alamri; Yasser S. Mostafa; Abdulrahman A. Almehizia (Biodegradation, 2025)

Bacterial community of the shrimp (Litopenaeus vannamei) gut and its relationship with water quality in a recirculating aquaculture system (RAS) - Arslan Emmanuel; Bilal Raza; Muhammad Naeem Ramzan; Zhongming Zheng (Aquaculture International, 2025)

Assessing long-term vegetation changes, pollution and climate response in the Uttarakhand Region, North India: implications of Google Earth Engine - Umesh Chandra Dumka; Kiran Rawat; Dimitris G. Kaskaoutis; Ankur Srivastava; Muhammad Bilal; Sanjeev Kimothi; Prasun Kumar Gupta; Nikul Kumari (Environmental Monitoring and Assessment, 2025)

Avoided mortality by particulate air pollution control measures in China - Aristeidis K. Georgoulias; Jos Lelieveld; Klaus Klingmüller; Dimitris Akritidis; Andrea Pozzer; Georgia Alexandri; Muhammad Bilal; Yafang Cheng; Hang Su; Prodromos Zanis (Science of The Total Environment, 2025)

Zinc-based nanoparticles improved the growth, chlorophyll, osmoregulation and ions relations of sunflower under combined shade and drought stress - Maria Tariq; Aasma Tufail; Muhammad Bilal Hafeez; Mafia Shoukat; Naeem Ahmad; Shahid Iqbal; Maqsood ul Hussan; Tayyaba Tariq; Muhammad Kamran; Muhammad Ahsan; Fahd Rasul; Noreen Zahra (Biocatalysis and Agricultural Biotechnology, 2025)

Bacillus species compatibility enhances VOC-mediated systemic resistance against Botrytis cinerea - Abdur Rashid Khan; Qurban Ali; Xuxiang Wu; Sheng Chen; Muhammad Ayaz; Hamza Tariq; Muhammad Saqib Bilal; Li Li; Sunil Mundra; Qin Gu; Huijun Wu; Xiaobo Li; et al. (World Journal of Microbiology and Biotechnology, 2025)

Exploring nonstructural NS5B protein to design a multi-epitope-based vaccine against HCV: immuno-informatics approach - Nouman Ali; Adeeba Ali; Muhammad Sheraz Yousuf; Arsheen Rehman; Saad Muhammad Islam; Bilal Ilyas; Aamir Ali (In Silico Pharmacology, 2025)

Corrigendum to ‘Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting’ [Chemosphere 310 (2023) 136835] - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2025)

Corrigendum to “Designing highly potential photocatalytic comprising silver deposited ZnO NPs with sulfurized graphitic carbon nitride (Ag/ZnO/S-g-C3N4) ternary composite” [J. Environ. Chem. Eng. 9 (2021) 104919] - Shahid Iqbal; Naveed Ahmad; Mohsin Javed; Muhammad Azam Qamar; Ali Bahadur; Shahid Ali; Zahoor Ahmad; Rana Muhammad Irfan; Guocong Liu; Muhammad Bilal Akbar; Muhammad Abdul Qayyum (Journal of Environmental Chemical Engineering, 2025)

Roles of dissolved organic matters in K-struvite formation in batch and fluidized-bed reactors: A kinetic insight - Muhammad Bilal Zahid; Xianfei Wang; Yangfan Xia; Xinyi Xu; Dawei Li; Feihu Li (Journal of Environmental Chemical Engineering, 2025)

Magnetic biochar for the remediation of arsenic contaminated water: A complete guide of science, synthesis, and solutions - Yasir Hamid; Yonglong Chen; Muhammad Haris; Muhammad Usman; Bilal Hussain; Muhammad Saqib Rashid; Temoor Ahmed; Muhammad Noman; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2025)

Co-combustion behaviour of municipal waste and food waste using TG-FTIR and Py-GC/MS: Thermo-kinetic behaviour and gaseous pollutants emission - Muhammad Bilal Ahmad; Guoxin Su; Lei Li; Junwu Ma; Xiaodong Li; Tedla Medhane Embaye; Zhongfa Hu; Shuanghui Deng; Haijun Guo; Xuebin Wang (Fuel, 2025)

Multi-biomarker assessment of essential and toxic elements accumulation in Labeo gonius from Khushab Lake (Pakistan) - Muhammad Kashif Ashraf; Sana Ullah; Muhamamd Bilal; Cristiana Roberta Multisanti; Caterina Faggio (Environmental Toxicology and Pharmacology, 2025)

Tuning water transport channels in sulfonated copolymer membranes for highly effective removal of arsenic and selenium from industrial wastewater - Syed Qamber Ali Zaidi; Muhammad Hafi Wadgama; Zaib Jahan; Muhammad Bilal Khan Niazi; Faheem Hassan Akhtar (Desalination, 2025)

AI-powered optimization of reactive red 195 dye decolorization: Evaluating the impact of operational factors - Zubair Khaliq; Anum Javaid; Abdulaziz Bentalib; Muhammad Bilal Qadir; Zubera Naseem; Shumaila Kiran; Fayyaz Ahmad; Nimra Nadeem; Maryam Bibi (Desalination, 2025)

Carbon-negative process Integration: Techno-economic framework for biomass-blend bio-energy carbon capture and storage polygeneration with high-value co-product streams - Syed Muhammad Mustafa Rizvi; Bilal Kazmi; Syed Ali Ammar Taqvi; AbdulAziz AlGhamdi (Biomass and Bioenergy, 2025)

Cobalt-catalyzed reductive cross-coupling: a review - Shamoon Hassan; Muhammad Bilal; Shehla Khalid; Nasir Rasool; Muhammad Imran; Adnan Ali Shah (Molecular Diversity, 2025)

Shaping a greener future: the moderating role of financial development on political stability in evaluating environmental sustainability across ASEAN economies - Shamaila Butt; Muhammad Ramzan; Muhammad Ali Chohan; Muddassar Bilal; Umbrin Akbar (Clean Technologies and Environmental Policy, 2025)

Biofumigation with carvacrol disrupts membrane integrity and metabolic homeostasis in yam leaf spot pathogen Alternaria alternata - Hamza Tariq; Wenwu Zou; Lanning Wang; Jingkun Lv; Abdur Rashid Khan; Muhammad Saqib Bilal; Danyu Shen; Daolong Dou (Pesticide Biochemistry and Physiology, 2025)

Insight into the effect of ammonia doping on the methane jet flame - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Samuel Daniel; Wang Du; Ahmed E. Mansy; Kai-Ru Jin; Zhen-Yu Tian (Fuel, 2025)

Corrigendum to “AI-powered optimization of reactive red 195 dye decolorization: Evaluating the impact of operational factors” [Desal. Volume 612 (2025), article number: 118936 https://doi.org/10.1016/j.desal.2025.118936] - Zubair Khaliq; Anum Javaid; Abdulaziz Bentalib; Muhammad Bilal Qadir; Zubera Naseem; Shumaila Kiran; Fayyaz Ahmad; Nimra Nadeem; Maryam Bibi (Desalination, 2025)

Advancing algae-based Bioenergy: Techno-Economic assessment of hydrogen and biochar production from algal biomass - Aliyan Tanweer; Syed Ali Ammar Taqvi; Bilal Kazmi; Safiya Khatoon; Muhammad Taha; Muhammad Nadir; Farooq Ahmad; Naveed Ahmad (Biomass and Bioenergy, 2025)

Evolving climatic patterns and drought risk in Pakistan’s agro-ecological zones - Raja Muhammad Usama; Sawaid Abbas; Mansour Almazroui; Muhammad Fahad Bilal; Asad Ali (Theoretical and Applied Climatology, 2025)

Impact of Reconditioning Treatment at Different Temperatures on Potato Cultivars Stored Under Cold Conditions - Adnan Amjad; Aziz Mouhaddach; Hanane Latifi; Rabia Mehboob; Tusneem Kausar; Mohamed Bouhrim; Ramzi A. Mothana; Omar M. Noman; Farzana Siddique; Muhammad Bilal; Shehnshah Zafar; Ashiq Hussain (Potato Research, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Role of Bacillus pseudomycoides in Enhancing the Nutritional Profile of Five Vigna radiata (L.) Cultivars Under Saline Stress - Bushra Bilal; Zafar Siddiq; Tehreema Iftikhar; Muhammad Umar Hayyat; Hammad Majeed (Journal of Soil Science and Plant Nutrition, 2025)

Advancing fungal phylogenetics: integrating modern sequencing, dark taxa discovery, and machine learning - Syed Atif Hasan Naqvi; Aqleem Abbas; Ammarah Hasnain; Zeshan Bilal; Fahad Hakim; Muhammad Shabbir; Ahsan Amin; Muhammad Umer Iqbal (Archives of Microbiology, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Efficient enrichment and selective recovery of rare earth elements from igneous carbonatite ore - Bilal Ben Ali; Muhammad Ouabid; Cheikh-ELwali Malainine; Jamal Ait Brahim; Otmane Raji; Tarik Chafik; Ouafae Achak; Oussama Khadiri Yazami; Yassine Ait-Khouia; Abdelmaula Aboulaich; Redouane Beniazza (Minerals Engineering, 2025)

Corrigendum to “Application of nanomaterials for enhanced production of biodiesel, biooil, biogas, bioethanol, and biohydrogen via lignocellulosic biomass transformation” [Fuel 315 (2022) 122840] - Mehvish Mumtaz; Zulqarnain Baqar; Nazim Hussain; Afifa; Muhammad Bilal; Hafiz Muhammad Husnain Azam; Qurat-ul-ain Baqir; Hafiz M.N. Iqbal (Fuel, 2025)

Machine learning assisted predictive urban digital twin for intelligent monitoring of air quality index for smart city environment - Khazina Naveed; Tariq Umer; Aamer Bilal Asghar; Muhammad Aslam; Krzysztof Ejsmont; Ahmed Sayed Mohammed Metwally; Kien Nguyen Thanh (Environmental Modelling & Software, 2025)

Corrigendum to “Dual-modification strategy for efficient inverted perovskite solar cells via thermally induced liquid crystals and boosting of phenethylammonium by carbazole” [Chem. Eng. J. 516 (2025) 163918] - Bilal Mehmood; Chen Zhang; Shan Wu; Jiangying Lu; Xu Zheng; Wei Jiang; Kamran Amin; Shudi Lu; Muhammad Iftikhar Khan; Muhammad Sultan; Tanveer Ashraf; Zhijie Wang; et al. (Chemical Engineering Journal, 2025)

Improving Fengyun-3D satellite atmospheric precipitable water vapor products through machine learning-based post-processing correction - Mengnan Li; Leiku Yang; Weiqian Ji; Muhammad Bilal; Xin Pei; Xueke Zheng; Yizhe Fan; Xiaofeng Lu; Xiaoqian Cheng; Weibing Du (Atmospheric Research, 2025)

Bio-metabolites Mechanism for the Eco-friendly Management of Alternaria Black Spot Disease Through the Use of Bio-agents in Canola - Effat Naz; Muhammad Jabran; Muhammad Bilal; Ikhlas Shafique; Farrukh Azeem; Amjad Abbas; Muhammad Amjad Ali (Journal of Crop Health, 2025)

Long-term PM2.5 exposure in Bangladesh: identification of pollution hotspots, trends, sources and health risk assessment - Md. Arfan Ali; Mazen E. Assiri; Muhammad Bilal; Salman Tariq; Gerrit de Leeuw; M. Nazrul Islam; Yu Wang; Lama Alamri; Ayman S. Ghulam; Shamsuddin Shahid (Air Quality, Atmosphere & Health, 2025)

High-performance PVC/polyacrylate-graphene oxide membranes for Pb (II) and Hg (II) ion removal from polluted water: synthesis, characterization, and adsorption studies - Noreen Nasir; Junaid Raza; Abdul Hamid; Naseem Ahmad Khan; Mubushar Majeed; Muhammad Sohail Aslam; Anis Ali Shah; Muhammad Iftikhar; Bilal Arshad; Muhammad Sohail; Muhammad Saeed; Shifa Shaffique; et al. (Environmental Monitoring and Assessment, 2025)

Assessing future water scarcity in China under climate and socioeconomic change: Can inter-basin transfers mitigate rising stress? - Muhammad Bilal Idrees; Haixing Liu; Siao Sun; Xian Zhou; Muhammad Zain Bin Riaz (Science of The Total Environment, 2025)

A novel bio-based time-temperature dependent colorimetric indicator film incorporated with Amaranthus leaf extract for beef freshness tracking - Muhammad Shahar Yar; Isaiah Henry Ibeogu; Muhammad Adnan; Faiza Rehman; Abisikha Regmi; Meng Zhou; Muhammad Bilal; Zheng Liu; Hadiza Kabir Bako; Chunbao Li (Food Chemistry, 2025)

Dual-modification strategy for efficient inverted perovskite solar cells via thermally induced liquid crystals and boosting of phenethylammonium by carbazole - Bilal Mehmood; Chen Zhang; Shan Wu; Jiangying Lu; Xu Zheng; Wei Jiang; Kamran Amin; Shudi Lu; Muhammad Iftikhar Khan; Muhammad Sultan; Tanveer Ashraf; Zhijie Wang; et al. (Chemical Engineering Journal, 2025)

Towards sustainable methanol production: energy, exergy, economics, and environmental evaluation of Thar coal gasification - Syeda Asra Arshad; Umna Nasir Ali; Syed Ali Ammar Taqvi; Bilal Kazmi; Ahsan Khalid; Muhammad Ahmer; Farooq Ahmad; Naveed Ahmad (Environment, Development and Sustainability, 2025)

Transboundary river water quality assessment: a case study of Kabul River Basin, Pakistan - Kashif Hussain; Muhammad Shahid Iqbal; Sarfraz Munir; Hazrat Bilal (Environmental Science and Pollution Research, 2025)

Characterising the Urban Heat Island in a low-rise indigenous city using remote sensing - Muhammad Usman; Janet E. Nichol; Ayman M. Abdallah; Muhammad Bilal (Urban Climate, 2025)

Urban flood management from the lens of social media data using machine learning algorithms - Muhammad Waseem Boota; Shan-e-hyder Soomro; Jikun Xu; Muhammad Irshad Ahmad; Haoming Xia; Yaochen Qin; Muhammad Bilal Idrees; Naseem Ahmad; Chaode Yan; Ayesha Yousaf; Xiaoju Ning (Journal of Hydrology, 2025)

Probing the active kinematics in northwestern Himalayan foreland, Pakistan: Insights from seismicity and gravity data - Mohammad Tahir; Bilal Saif; Tahir Muhammad Iqbal; Raja Adnan Habib; Talat Iqbal; Muhammad Awais; Muhammad Ali Shah (Journal of Geodynamics, 2025)

Retraction notice to “Recent advances in microstructural control via thermal spraying for solid oxide fuel cells” [Chem. React. Eng. 478 (2023) 147352] - Jiu-Tao Gao; Muhammad Bilal Hanif; Hui-u Zhang; Martin Motola; Cheng-Xin Li (Chemical Engineering Journal, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Comprehensive investigation and kinematic assessment of a small catastrophic landslide in Shiban Valley, Leshan City, Sichuan Province, China - Yiwei Liu; Aiguo Xing; Qiankuan Wang; Muhammad Bilal; Kaiyue Zhu; Wenpei Wang (Landslides, 2025)

Combined Application of Plant Growth Promoting Rhizobacteria and Kinetin on Maize Growth, Chlorophyll, Osmoregulation, and Oxidative Metabolism Under Drought Stress - Rubaika Khurshid; Shagufta Perveen; Muhammad Bilal Hafeez; Abid Niaz; Saeedeh Zarbakhsh (Journal of Soil Science and Plant Nutrition, 2025)

Exogenous applications of humic acid and salicylic acid differentially affect biomass accumulation and production of rare pharmacologically active withanolides in in vitro cultures of Withania coagulans - Mehnaz Khanum; Muhammad Uzair Javed; Sannia Batool; Gouhar Zaman; Muhammad Naeem Bajwa; Anisa Andleeb; Laurine Garros; Samantha Drouet; Duangjai Tungmunnithum; Christophe Hano; Bilal Haider Abbasi; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2025)

Mouse hindlimb unloading, as a model of simulated microgravity, leads to dysregulated iron homeostasis in liver and skeletal muscle cells - Bilal Rah; Jasmin Shafarin; Rizwan Qaisar; Asima Karim; Mawieh Hamad; Jibran Sualeh Muhammad (Life Sciences in Space Research, 2025)

Prospecting high-altitude springs in the Upper Indus Basin, Pakistan: Knowledge towards policy development - Arshad Ashraf; Muhammad Bilal Iqbal; Ali Kamran; Naveed Mustafa (Groundwater for Sustainable Development, 2025)

Failure process analysis of a catastrophic landslide in Zhenxiong triggered by prolonged low-intensity rainfall using centrifuge tests - Qiankuan Wang; Bin Li; Aiguo Xing; Yiwei Liu; Yu Zhuang; Muhammad Bilal (Engineering Geology, 2025)

Molecular prevalence and genetic diversity of Hepatozoon canis in Rhipicephalus sanguineus s.l. and Hyalomma anatolicum infesting dogs - Hafiza Amna Bilal; Madiha Rasool; Arfa Bibi; Hira Muqaddas; Iqra Majeed; Muhammad Farooq; Kasim Sakran Abass; Samir Ibenmoussa; Turki M. Dawoud; Shakir Ullah; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Exploring melatonin’s influence on secondary metabolism of Echinacea purpurea callus cultures - Tehreem Mahmood; Muhammad Uzair Javed; Gouhar Zaman; Bushra Khan; Negin Zarei; Cécile Abdallah; Christophe Hano; Johan-Owen De Craene; Arnaud Lanoue; Bilal Haider Abbasi; Nathalie Giglioli-Guivarc’h (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Seismicity patterns and geodynamics of the Hindukush seismic zone: A comprehensive study through relocation of moderate to large earthquakes - Bilal Saif; Mohammad Tahir; Muhammad Zafar Iqbal; Talat Iqbal; Muhammad Ali Shah (Journal of Mountain Science, 2025)

The role of nitric oxide and nitrogen in mediating copper stress in Brassica juncea L. - Bilal A. Rather; Asim Masood; Fei Qiao; Xuefei Jiang; Muhammad Mubashar Zafar; Hanqing Cong; Nafees A. Khan (Plant Science, 2025)

Modulation of phytochemical profiles and bioactive constituents in Ananas comosus via Lactiplantibacillus-mediated fermentation - Peter Ankutse; Faith Adisa Musumba; Muhammad Bilal; Yongbin Han; Yuqing Duan; Fang Li; Isaiah Henry Ibeogu; Emmanuel Adase (Food Bioscience, 2025)

Comprehensive assessment, intelligent prediction, and precise mitigation strategies for greenhouse gas emissions in full-scale wastewater treatment plants - Zitan Zhang; Fei Qi; Yao Liu; Muhammad Bilal Asif; Amir Ikhlaq; Zhenbei Wang; Caocao Chen; Chen Li; Jing Chang; Qun Li; Ye Li; Yujie Li; et al. (Environmental Research, 2025)

Investigating the dynamics of (3+1)-dimensional generalized nonlinear physical system via sensitivity and phase portraits - Muhammad Iqbal; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman (Modeling Earth Systems and Environment, 2025)

Exploring chaos and stability: dynamic insights into the stochastic Davey-Stewartson system through advanced sensitivity analysis - Muhammad Moneeb Tariq; Muhammad Bilal Riaz; Tomas Kozubek; Muhammad Aziz-ur-Rehman (Modeling Earth Systems and Environment, 2025)
In this study, we investigate the stochastic Davey-Stewartson equation in the presence of noise. These two-dimensional integrable equations are higher-dimensional versions of the nonlinear Schrödinger equation. Davey-Stewartson equations are important in plasma physics, nonlinear optics, hydrodynamics, and other disciplines because the solutions they provide are valuable in understanding many complex physical phenomena. We employ a modified version of the $$\left( \frac{G'}{G^2} \right)$$ G ′ G 2 approach to handle variable-coefficient systems with imaginary components, such as nonlinear Schrödinger systems. We have discovered a wide range of precise traveling wave solutions, including solitons, kink, periodic, and rational solutions. These solutions may have a significant impact in the domains of engineering and plasma physics. The presented techniques effectively achieve a variety of exponential solutions, including bright, dark, single, rational, and periodic solitary wave solutions. We used MATLAB to simulate our findings and provide 3D, 2D, and counter graphs that illustrate the impact of noise on the precise solutions of the stochastic Davey-Stewartson problem. We apply the Galilean transformation to derive the planar dynamical system, which enhances our understanding of the system’s dynamical analysis. We also conduct a sensitivity analysis to observe the systematic response to various initial conditions. This analysis focuses on the symmetrical aspects of the system and includes the illustration of phase portraits with equilibrium points. We also investigate the chaotic behavior of the planer dynamical system by introducing an additional external force. We predict the system’s behavior to increase the value of intensity and frequency. Our analysis reveals periodic, quasi-periodic, and chaotic processes.

Assessment of Climate-resilient Cotton Genotypes Exhibiting High-temperature Tolerance - Sajid Ali; Waqas Shafqat Chattha; Aziz Ullah; Muhammad Zahid Ihsan; Waqar Shafqat; Abdel-Halim Ghazy; Muhammad Afzal; Bilal Ayub (Journal of Crop Health, 2025)

Exploring the Mechanisms of Halophilic Bacterium SPSB2 and Mannitol in Mitigating Sodium Chloride and Arsenic Stress in Solanum Lycopersicum - Lubna; Muhammad Aizaz; Shima Ahmed Ali Alrumaidhi; Rawan Ahmed Mohammed Alhinai; Reem Saif Mohammed A. L. Kalbani; Ibrahim Khan; Saqib Bilal; Sajjad Asaf; Ahmed AL-Harrasi (Journal of Crop Health, 2025)

Seasonal Variations in Potable Water Quality of Bahawalpur City: A Comprehensive Assessment of Major Ions, Organic Matter, and Disinfection Byproducts - Sundas Kali; Mazhar Iqbal Zafar; Abida Farooqi; Muhammad Saifullah; Sajida Rasheed; Muhammad Bilal khan Niazi; Amir Waseem; Luiza C. Campos (Environmental Monitoring and Assessment, 2025)

Effect of soil types and moisture contents on the pupation behavior and adult emergence of Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Muhammad Bilal; Muhammad Mamoon-ur-Rashid; Shabana Wazir; Muhammad Naeem; Asif Ishaq; Rana Muhammad Kaleem Ullah; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2025)

A review: Improving aquaculture rearing water quality by removal of nutrients using microalgae, challenges and future prospects - Bilal Raza; Muhammad Naeem Ramzan; Wen Yang (Aquaculture, 2025)

Effect of human chorionic gonadotropin on oocyte maturation and developmental competence in buffalo - Muhammad Bilal; Muhammad Kamran Ashraf; Talha Ashraf; Muhammad Yaseen; Ali Husnain; Muhammad Bilal Bin Majeed; Muhammad Imran; Burhan E. Azam Rana; Muhammad Hassan Mushtaq; Amjad Riaz (Theriogenology, 2025)

Laccase-based biocatalytic systems application in sustainable degradation of pharmaceutically active contaminants - Anil Kumar Singh; Pedro Abellanas-Perez; Diandra de Andrades; Iris Cornet; Roberto Fernandez-Lafuente; Muhammad Bilal (Journal of Hazardous Materials, 2025)

Retraction notice to “Straw incorporation into microplastic-contaminated soil can reduce greenhouse gas emissions by enhancing soil enzyme activities and microbial community structure” [J. Environ. Manag. 351 (2024) 119616] - Tariq Shah; Zeeshan Khan; Muhammad Asad; Ayesha Imran; Muhammad Bilal Khan Niazi; Raf Dewil; Ajaz Ahmad; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Retraction notice to “Bio-mitigation of organic pollutants using horseradish peroxidase as a promising biocatalytic platform for environmental sustainability” [Environ. Res. 239-P1 (2023) 117192] - Muhammad Bilal; Anil Kumar Singh; Hafiz M.N. Iqbal; Tak H. Kim; Grzegorz Boczkaj; Khawlah Athmaneh; Syed Salman Ashraf (Environmental Research, 2025)

Environmentally friendly nitrogen doped paired mineral-carbon for catalytic degradation of diethyl phthalate and crop damage mitigation - Saeed Rehman; Hongjuan Sun; Muddasir Hanif; Tongjiang Peng; Xu Tang; Osama Tariq Satti; Muhammad Bilal (Chemical Engineering Journal, 2025)

Plant Growth Promoters (PGPs) Alleviate Salt Stress, Enhance Physiological Parameters, Secondary Metabolites and Silymarin Content in Milk Thistle - Noreen Zahra; Abdul Wahid; Muhammad Bilal Hafeez; Muhammad Waqas; Abida Kausar; Abdulaziz Abdullah Alsahli (Journal of Soil Science and Plant Nutrition, 2025)

Thymol as a Novel Plant-Derived Antibacterial Agent for Suppressing Xanthomonas citri pv. malvacearum in Cotton - Muhammad Naveed Aslam; Huma Khaliq; Hongwei Zhao; Anam Moosa; Ambreen Maqsood; Muhammad Aslam Farooqi; Muhammad Saqib Bilal; Tahir Mahmood; Tariq Mukhtar (Current Microbiology, 2025)

Correction: Shaikh et al. Acoustic Propagation and Transmission Loss Analysis in Shallow Water of Northern Arabian Sea. J. Mar. Sci. Eng. 2024, 12, 2256 - Shahabuddin Shaikh; Yiwang Huang; Ayman Alharbi; Muhammad Bilal; Abdul Sami Shaikh; Habib Hussain Zuberi; Muhammad Ayoob Dars (Journal of Marine Science and Engineering, 2025)
Errors in Figures [...]

Impact of forage levels and physical forms on feed sorting behavior, rumen morphometry, and selected blood parameters in fattening male goats - Muhammad Irfan Malik; Muhammad Afzal Rashid; Maria Teresa Capucchio; Muhammad Bilal; Muhammad Shahbaz Yousaf; Habib Ur Rehman; Amlan Kumar Patra (Small Ruminant Research, 2025)

Recent advances in engineering non-native microorganisms for poly(3-hydroxybutyrate) production - Said Nawab; Muhammad Wajid Ullah; Syed Bilal Shah; Ya-Fei Zhang; Hareef Ahmed Keerio; Yang-Chun Yong (World Journal of Microbiology and Biotechnology, 2025)

Unraveling the complexity of solitary waves in the Klein-Fock-Gordon equation: dynamical insights into bifurcation and Chaos analysis - Muhammad Moneeb Tariq; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman; Dilawaiz (Modeling Earth Systems and Environment, 2025)

The Chinese loess plateau, earthquakes, and flowslides: the need to enhance geotechnical disaster resilience - Muhammad Bilal; Aiguo Xing; Hemanta Hazarika (Landslides, 2025)

UV-B Stress Regulates the Transcription of UVR8 Signal System-Related Gene and the Synthesis of Isoflavones in Soybean Sprouts - Guannan Liu; Yunyun Zhao; Mian Wang; Muhammad Bilal; Pei Wang; Chong Xie; Hansong Yu; Runqiang Yang (Journal of Plant Growth Regulation, 2025)

Insights into the dynamics of biochemical profile and relative gene expression of cucumber fruits associated with Fusarium spoilage - Muhammad Imran; Hanan A. Khalifa; Zhongke Sun; Muhammad Saqib Bilal; Mohamed Hassan Abd El-Wahed; Kamal A. M. Abo-Elyousr; Esmat F. Ali; Chengwei Li (Journal of Plant Diseases and Protection, 2025)

Development and In-Vitro Tuning of Piperine Containing Solid Lipid Microparticles for the Treatment of Rheumatoid Arthritis - Muneeba Aziz; Sajid Bashir; Rai Muhammad Sarfraz; Hira Ijaz; Asif Mahmood; Zulcaif; Bilal Haroon; Milad A. Mezher; Mohamed M. Salem; Sami Al Zahrani; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

Investigating Bemisia tabaci (Hemiptera: Aleyrodidae) resistance mechanisms: a comprehensive analysis of variable responses to selective insecticides - Dilbar Hussain; Muhammad Saleem; Muhammad Sohail Qadir; Kanwal Hanif; Faisal Hafeez; Usama Saleem; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal; Muhammad Zubair (International Journal of Tropical Insect Science, 2025)

Heavy metals concentration and human health risk assessment in selected shrimp species of Pakistan - Alveena Draz; Muhammad Asghar Qazi; Talib Hussain; Owais Ahmad; Muhammad Mahd Nazir; Muhammad Bilal Bhatti; Nimra Hussain; Shahid Sherzada (Food Additives & Contaminants Part B-Surveillance, 2025)

Synergistic electrochemical performance of textile sludge based activated carbon with reduced graphene oxide as electrode for supercapacitor application - Naveed Ahmed Khan; Zaib Jahan; Naseem Iqbal; Muhammad Bilal Niazi; Rimsha Mehek (Waste Management, 2025)

Influence of physical forms of non-forage diet on growth performance, feeding behavior, rumen and blood indices, and nutrient digestibility in fattening goats - Muhammad Bilal; Muhammad Irfan Malik; Muhammad Afzal Rashid; Muhammad Awais Khurshid; Muhammad Shahbaz Yousaf; Habib Ur Rehman (Small Ruminant Research, 2025)

Enhancing the removal of total trihalomethanes and dissolved organic matter from water using zinc and iron-impregnated granulated activated carbon and response surface methodology - Sundas Kali; Mazhar Iqbal Zafar; Sajida Rasheed; Qizhi Zhou; Muhammad Bilal Khan Niazi; Abida Farooqi; Luiza C. Campos (Journal of Water Process Engineering, 2025)

Recent advances of wheat bran arabinoxylan exploitation as the functional dough additive - Muhammad Bilal; Dandan Li; Chong Xie; Runqiang Yang; Zhenxin Gu; Dong Jiang; Xueming Xu; Pei Wang (Food Chemistry, 2025)

Predictive modeling of emulsion stability and drop characteristics using machine learning: A study on surfactant influence and time dynamics - Hasnain Ahmad Saddiqi; Asmat Ullah; Zainab Javed; Qazi Muhammad Ali; Muhammad Bilal Jan; Iftikhar Ahmad; Farooq Ahmad (Food and Bioproducts Processing, 2025)

Particle size of wheat straw from genetically improved wheat affects the production performance and feeding behavior of Sahiwal cows - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Muhammad Qamar Bilal; Muhammad Riaz; Muhammad Farooq Khalid; Zia-Ur-Rehman; Urooj Anwar; Riaz Mustafa; Waseem Abbas; Umar Farooq (Tropical Animal Health and Production, 2025)

CsdlFusion: An Infrared and Visible Image Fusion Method Based on LatLRR-NSST and Compensated Saliency Detection - Hui Chen; Ziming Wu; Zihui Sun; Ning Yang; Muhammad llyas Menhas; Bilal Ahmad (Journal of the Indian Society of Remote Sensing, 2025)

Carvone-loaded chitosan nanoparticles alleviate joint destruction by downregulating the expression of pro, inflammatory cytokines and MMP-13 in adjuvant-induced rat model - Zartashia Kanwal; Bushra Akhtar; Bilal Aslam; Muhammad Imran Arshad (Inflammopharmacology, 2025)

Utilizing contemporary machine learning techniques for determining soilcrete properties - Waleed Bin Inqiad; Muhammad Saud Khan; Zohaib Mehmood; Naseer Muhammad Khan; Muhammad Bilal; Mohammed Sazid; Saad S. Alarifi (Earth Science Informatics, 2025)
Soilcrete is an innovative construction material made by combining naturally occurring earth materials with cement. It can be effectively used in areas where other construction materials are not readily available due to financial or environmental reasons since soilcrete is made from readily available natural clay. It can also help to cut down the greenhouse gas emissions from the construction industry by encouraging the use of resources that are locally available. Thus, it is imperative to reliably predict different properties of soilcrete since the accurate determination of these properties is crucial for the widespread use of soilcrete materials. However, the laboratory determination of these properties is subjected to significant time and resource constraints. As a result, this research was undertaken to provide empirical prediction models for the density, shrinkage, and strain of soilcrete mixes using two machine learning algorithms: Gene Expression Programming (GEP) and Extreme Gradient Boosting (XGB). The analysis revealed that XGB-based predictions correlated more with real-life values than GEP having training $${\text{R}}^{2}=0.999$$ R 2 = 0.999 for both density and shrinkage prediction and $${\text{R}}^{2}=0.944$$ R 2 = 0.944 for strain prediction. Moreover, several explanatory analyses including individual conditional expectation (ICE) analysis and shapely analysis were done on the XGB model which showed that water-to-binder ratio, metakaolin content, and modulus of elasticity are some of the most important variables for forecasting soilcrete materials properties. Furthermore, an interactive graphical user interface (GUI) has been developed for effective utilization in civil engineering industry to forecast these properties of soilcrete materials.

A critical review of NO2 and AOD in major Asian cities: challenges, mitigation approaches and way forwards - Most Mastura Munia Farjana Jion; Abu Reza Md Towfiqul Islam; Mahir Shahrier; Md Yousuf Mia; Jannatun Nahar Jannat; Md Arfan Ali; Md Abdullah Al Masud; Md Firoz Khan; Muhammad Bilal; Abubakr M. Idris; Guilherme Malafaia (Air Quality, Atmosphere & Health, 2025)

Unveiling concentrations of trace elements in the Lower Indus River: risks to aquatic life and human health - Muhammad Waseem Boota; Shan-e-hyder Soomro; Haoming Xia; Yaochen Qin; Muhammad Bilal Idrees; Ayesha Yousaf (Frontiers in Marine Science, 2024)
Concentration of trace elements (CTEs) is a significant environmental concern worldwide. This study assessed CTE levels in the Lower Indus River (LIR) by analyzing CTEs in water, sediments, tissues of fish ( Cirrhinus mrigala ), and macrophytes using electrothermal atomic absorption spectrometry (ETAAS) and flame atomic absorption spectrometry (FAAS). The study shows that CTE range—arsenic (As, 58.7–112.1 μg/L), lead (Pb, 59.9–95.6 μg/L), cadmium (Cd, 3.8–8.1 μg/L), nickel (Ni, 40.9–63.4 μg/L), and zinc (Zn, 590.7–847.6 μg/L)—and water parameters (temperature, pH, COD, BOD, turbidity, and alkalinity) exceeded WHO (World Health Organization) acceptable limits. The CTEs (mg/kg dried basis) were analyzed in fish tissues, and As, Cd, Cr, Cu, Hg, Ni, and Zn have the following accumulation order: liver > gill > muscle. In contrast, Ag and Pb were present in higher amounts in gills than in the liver (gill > liver > muscle). Prediction of bioavailability of CTEs, with the extraction of sediment load with EDTA, revealed that As, Cd, and Zn were among the most bioavailable elements in the LIR. Health risk assessment indicated that the presence of CTEs in the fish could pose potential adverse health effects on humans. The study emphasizes significant ecological and health concerns due to fish consumption in the affected region, noting high risks of non-carcinogenic effects. These insights are essential for policymakers and stakeholders in Sindh Province to manage and reduce trace element pollution.

Acoustic Propagation and Transmission Loss Analysis in Shallow Water of Northern Arabian Sea - Shahabuddin Shaikh; Yiwang Huang; Ayman Alharbi; Muhammad Bilal; Abdul Sami Shaikh; Habib Hussain Zuberi; Muhammad Ayoob Dars (Journal of Marine Science and Engineering, 2024)
This study investigates acoustic propagation and transmission loss in shallow water at an unexplored site in the northern Arabian Sea near the Pakistan coastline using a normal mode theoretical framework. Sound propagation in shallow water with range-independent bathymetry was analyzed using a customized Kraken C program to compute eigenvalues and eigenfunctions. The sound speed profile and clay silt sediment samples of the northern Arabian Sea, which characterize the water column and ocean bottom, respectively, were determined. Coherent and incoherent transmission losses for frequencies ranging from 50 to 500 Hz were calculated across different ranges and depths. Results indicate significant intensity fluctuations with increasing range, leading to higher transmission loss. Low frequencies (50–225 Hz) exhibit more significant transmission loss, while higher frequencies (230–500 Hz) show reduced loss. Transmission loss is higher for receivers at 19 m depth compared to those at shallower depths (8 m and 12 m) because the receivers are positioned near the layer of bottom sediments. Factors such as source and receiver depth, sediment properties, bottom roughness, and sound frequency significantly influence transmission loss. The novel dataset for the region supports the assessment of sonar performance, underwater communication, navigation, and marine life exploration.

Effect of differential exposure of UV-C and melatonin stress on the therapeutic potential of bioactive compounds in Moringa oleifera - Muhammad Naeem Bajwa; Gouhar Zaman; Muhammad Asad Ullah; Muhammad Uzair Javed; Anisa Andleeb; Christophe Hano; Bilal Haider Abbasi (South African Journal of Botany, 2024)

Leveraging machine learning to model salinity and water flux for improved insights into forward osmosis membrane bioreactors - Ali Aldrees; Bilal Siddiq; Wael S. Al-Rashed; Muhammad Faisal Javed; Majid Khan (Journal of Water Process Engineering, 2024)

A novel carboxymethyl cellulose/gum xanthan and citric acid-based film that enhances the precision of blackcurrant anthocyanin-induced color detection for beef spoilage tracking - Muhammad Shahar Yar; Isaiah Henry Ibeogu; Hadiza Kabir Bako; Fawze Alnadari; Muhammad Bilal; Faiza Rehman; Jiaying Zhu; Tianming Zhou; Zerun Zhao; Chunbao Li (Food Chemistry, 2024)

A robust and simple non-enzymatic electrochemical sensor based on carbon dots-metal oxide composite for the detection of metronidazole traces in food products - Hafiza Khadija Aslam; Sehrish Bilal; Sana Mir; Sobia Tabassum; Mazhar Amjad Gilani; Mustansara Yaqub; Muhammad Asim (Food Chemistry, 2024)

Polypyrrole as the MOFs/polymer interfacial binder applied in mixed matrix porous separator for high temperature safe lithium-ion batteries - Shabab Hussain; Muhammad Bilal Hussain; Qian Zhou; Jinwu Peng; Jingjing Lin; Bin Zhang; Lei Wang (Chemical Engineering Journal, 2024)

Biomass and polyphenolic enhancement in date palm (Phoenix dactylifera L.) callus cultures through Fusarium oxysporum elicitation - Huda Enaya Mahood; Virginia Sarropoulou; Thiresia-Teresa Tzatzani; Muhammad Uzair Javed; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Morphometric and molecular characterization of Channa marulius from Riverine system of Punjab, Pakistan - Ghulam Rabbani; Fayyaz Rasool; Mahroze Fatima; Muhammad Bilal Bin Majeed (Molecular Biology Reports, 2024)

Predominance of MGMT promoter methylation among Pakistani glioblastoma patients - Noor Muhammad; Samir Fasih; Bilal Malik; Shahid Hameed; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2024)

Modeling the dynamics of dengue fever with double susceptibility and optimal control strategies - Muhammad Younas Khan; Saif Ullah; Muhammad Farooq; Muhammad Bilal Riaz (Modeling Earth Systems and Environment, 2024)

Nanobiochar-Coating Regulates N and P Release from DAP Fertilizer in Soil and Improves Maize Crop Productivity - Ghulam Abbas Shah; Mughees Mustafa; Hani Z. Asfour; Khubra Shoukat; Ahsan Yasin; Nadeem Ali; Muhammad Bilal Khan Niazi; Gabrijel Ondrasek; Muhammad Imtiaz Rashid (Journal of Soil Science and Plant Nutrition, 2024)

Effect of Plant Growth Regulators On Water Relations, Proximate Composition, and Ascorbate/glutathione Cycle of Late-sown Wheat Under Saline Conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Ali Raza; Rui Wang; Jun Li (Journal of Crop Health, 2024)

Performance evaluation of irrigation outlets with physical model study in Indus basin irrigation system of Pakistan - Ghulam Nabi; Fiaz Hussain; Bilal Sajjad; Muhammad Masood; Dengfeng Liu (Environmental Monitoring and Assessment, 2024)

Iron Overloading Potentiates the Antitumor Activity of 5-Fluorouracil by Promoting Apoptosis and Ferroptosis in Colorectal Cancer Cells - Bilal Rah; Jasmin Shafarin; Asima Karim; Khuloud Bajbouj; Mawieh Hamad; Jibran Sualeh Muhammad (Cell Biochemistry and Biophysics, 2024)
Resistance to 5-fluorouracil (5-FU) remains a significant challenge in colorectal cancer (CRC) treatment. Ferric ammonium citrate (FAC) is commonly used as an iron supplement due to its food-fortification properties; however, its potential role as a chemosensitizer in cancer therapy has not been studied. In this study, we explored the ability of FAC to sensitize CRC cells and increase their susceptibility to 5-FU-mediated anticancer effects. We assessed cell viability, cell cycle progression, apoptosis, mitochondrial membrane potential (MMP), reactive oxygen species (ROS) levels, ferroptosis, and iron metabolism-related protein expression using two CRC cell lines. Additionally, we conducted in silico analyses to compare iron markers in normal colon and CRC tumor tissues. Compared to controls, CRC cells pretreated with FAC and then treated with 5-FU exhibited significantly reduced growth and viability, along with increased ROS-mediated ferroptosis. Mechanistically, FAC-pretreated then 5-FU-treated CRC cells showed enhanced apoptosis, increased Bak/Bax expression, MMP depolarization, and decreased antiapoptotic protein levels (Bcl-2 and Bcl-xL). This combined treatment also led to G2/M cell cycle arrest, upregulation of p21 and p27, and downregulation of cyclin D1, c-Myc, survivin, and GPX4. Analysis of human colon tumor tissue revealed decreased expression of IRP-1 , HMOX-1 , and FTH1 but increased HAMP expression. In contrast, FAC-pretreated/5-FU-treated CRC cells exhibited a reverse pattern, suggesting that FAC-induced chemosensitization enhances 5-FU-mediated anticancer activity in CRC by disrupting iron homeostasis. These findings highlight the potential of iron overload as a chemosensitization strategy for improving CRC chemotherapy.

Therapeutic Potential of Green Synthesized Silver Nanoparticles for Promoting Wound-Healing Process in Diabetic Mice - Riffat Iqbal; Amna Asghar; Arslan Habib; Shaista Ali; Sadaf Zahra; Muhammad Imran Hussain; Ahmad Bilal Ahsan; Yulai Liang (Biological Trace Element Research, 2024)

Role of quality assessment of the recycled packaging material in determining its safety profile as food contact material - Muhammad Rehan Khan; Muhammad Bilal Sadiq; Lukáš Vápenka; Stefania Volpe; Aleš Rajchl; Elena Torrieri (Waste Management, 2024)

Microscale urban heat variability and time-location patterns: Elevated exposure for bikers and rickshaw drivers beyond average city temperatures in megacity - Bilal Ahmed Usmani; Muhammad Ahmed; Tahani Waqar; Asad Allana; Zafar Ahmed; Zafar Fatmi (Urban Climate, 2024)

Letter to Editor regarding “Validation and calibration of aerosol optical depth and classification of aerosol types based on multi-source data over China” by Wang et al. (2023) - Muhammad Bilal; Janet E. Nichol; Gerrit de Leeuw; Max P. Bleiweiss; Adel S. Aldosary; Muhammad Tauhidur Rahman (Science of The Total Environment, 2024)

Integrative metagenomic dissection of last-resort antibiotic resistance genes and mobile genetic elements in hospital wastewaters - Muhammad Shafiq; Xiaoling Guo; Meimei Wang; Hazrat Bilal; Li Xin; Yumeng Yuan; Fen Yao; Taha Majid Mahmood Sheikh; Muhammad Nadeem Khan; Xiaoyang Jiao (Science of The Total Environment, 2024)

Synergistic biochar and Serratia marcescens tackle toxic metal contamination: A multifaceted machine learning approach - Hamid Rehman; Aqib Hassan Ali Khan; Tayyab Ashfaq Butt; Muhammad Toqeer; Muhammad Bilal; Mahtab Ahmad; Ahmed Abdullah Alawi Al-Naghi; Enamur Rahim Latifee; Omar Ali Saad Algassem; Mazhar Iqbal (Journal of Environmental Management, 2024)

Environmental Heavy Metal Exposure and Associated Cardiovascular Diseases in Light of the Triglyceride Glucose Index - Muhammad Bilal Sardar; Mohsin Raza; Ammara Fayyaz; Muhammad Asfandyar Nadir; Zain Ali Nadeem; Muhammad Babar (Cardiovascular Toxicology, 2024)

Towards sustainable manufacturing: unpacking green practices’ impact on environmental performance in Pakistan - Muhammad Bilal; Zhao Xicang; Wu Jiying; Muhammad Umair Wattoo; Muhammad Adnan (Environment, Development and Sustainability, 2024)

Optimizing sustainability: a dual-channel supply chain model considering the carbon abatement cost subsidy and the low-carbon consumption subsidy - Yunfeng Zhang; Lijun Sun; Muhammad Bilal; Tingting Song (Environment, Development and Sustainability, 2024)

Prediction of surface urban heat island based on predicted consequences of urban sprawl using deep learning: A way forward for a sustainable environment - Shun Fu; Lufeng Wang; Umer Khalil; Ali Hassan Cheema; Israr Ullah; Bilal Aslam; Aqil Tariq; Muhammad Aslam; Saad S. Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Flexible MXenes for printing energy storage devices - Iftikhar Hussain; Onkar Jaywant Kewate; Sumanta Sahoo; Sikandar Aftab; P. Rosaiah; Muhammad Ahmad; Muhammad Bilal Hanif; Wail Al Zoubi; Zeeshan Ajmal; Waqas Ul Arifeen; Mohd Zahid Ansari; Bhargav Akkinepally; et al. (Chemical Engineering Journal, 2024)

Feasible biosynthesis of biologically active metabolites in in vitro culture of Macrotyloma uniflorum - Sannia Batool; Mehnaz Khanum; Hasnat Tariq; Gouhar Zaman; Muhammad Uzair Javed; Bilal Haider Abbasi; Christophe Hano; Nathalie Giglioli-Guivarc'h (Biocatalysis and Agricultural Biotechnology, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

The effect of ambient air temperature on meltwater production and flow dynamics in snow avalanches - Yu Zhuang; Aiguo Xing; Muhammad Bilal; Perry Bartelt (Landslides, 2024)

Recent Advances in Plant Drought Tolerance - Muhammad Farooq; Abdul Wahid; Noreen Zahra; Muhammad Bilal Hafeez; Kadambot H. M. Siddique (Journal of Plant Growth Regulation, 2024)

Evaluation the Effects of Copper Nanoparticles Dietary Supplementation on Growth Performance, Carcass Characteristics, and Serum Antioxidant Status in Broilers - Bilal Ahmed; Muhammad Sharif; Safdar Hassan; Muhammad Khalid Bashir; Fawwad Ahmad (Biological Trace Element Research, 2024)

Temporal stress perturbations generated by the Kahramanmaraş Mw 7.8 & 7.5 2023 seismic doublet in Türkiye - Mohammad Tahir; Bilal Saif; Seema Tahir; Mahmood Sultan; Talat Iqbal; Muhammad Ali Shah (Acta Geophysica, 2024)

Optimized prediction modeling of micropollutant removal efficiency in forward osmosis membrane systems using explainable machine learning algorithms - Ali Aldrees; Muhammad Faisal Javed; Majid Khan; Bilal Siddiq (Journal of Water Process Engineering, 2024)

Engineering of interfacial electric field by g-C3N4/ZnSnO3 heterojunction for excellent photocatalytic applications - Zia Ur Rehman; Sajid Ur Rehman; Muhammad Bilal; Faheem K. Butt; Asif Hussain; Jawad Ahmad Jrar; Kewang Zheng; Yongcai Zhang; Xiaoyong Xu; Xiaozhi Wang; Jianhua Hou (Journal of Cleaner Production, 2024)

Micro and nano-encapsulated natural products in yogurt: An emerging trend to achieve multifunctional benefits in product quality and human health. - Mohammad Rezaul Islam Shishir; Md Saifullah; Sulafa B.H. Hashim; Halah Aalim; Muhammad Bilal; Suliman Khan; Gobinath Marappan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Muhammad Arslan; Farah Saleena Taip; et al. (Food Hydrocolloids, 2024)

Mitigating cadmium exposure risk in rice with foliar nano-selenium: Investigations through Caco-2 human cell line in-vivo bioavailability assay - Bilal Hussain; Xianyuan Yin; Qiang Lin; Yasir Hamid; Muhammad Usman; Muhammad Laeeq-ur-Rehman Hashmi; Min Lu; Muhammad Imran Taqi; Zhenli He; Xiao e Yang (Environmental Pollution, 2024)

Examining performance, milk, and meat in ruminants fed with macroalgae and microalgae: A meta-analysis perspective - Muhammad Ainsyar Harahap; Slamet Widodo; Ulvi Fitri Handayani; Ririen Indriawaty Altandjung; Wulandari; Awistaros Angger Sakti; Bayu Andri Atmoko; Windu Negara; Yelsi Listiana Dewi; Hardi Julendra; Ahmad Sofyan; Tegoh Wahyono; et al. (Tropical Animal Health and Production, 2024)

Dynamic Characteristics and Risk Assessment of the Yiziyan Rock Topples in Jinsha County, Guizhou, China - Yufang Zhang; Kun Yuan; Muhammad Bilal; Junyi He; Aiguo Xing (Rock Mechanics and Rock Engineering, 2024)

Assessment of body mass-related covariates for rifampicin pharmacokinetics in healthy Caucasian volunteers - Muhammad Bilal; Sami Ullah; Ulrich Jaehde; Christina Trueck; Dario Zaremba; Bertil Wachall; Manfred Wargenau; Bernhard Scheidel; Martin H. J. Wiesen; Malaz Gazzaz; Chunli Chen; Sören Büsker; et al. (European Journal of Clinical Pharmacology, 2024)
Purpose Currently, body weight-based dosing of rifampicin is recommended. But lately, fat-free mass (FFM) was reported to be superior to body weight (BW). The present evaluation aimed to assess the influence of body mass-related covariates on rifampicin’s pharmacokinetics (PK) parameters in more detail using non-linear mixed effects modeling (NLMEM). Methods Twenty-four healthy Caucasian volunteers were enrolled in a bioequivalence study, each receiving a test and a reference tablet of 600 mg of rifampicin separated by a wash-out period of at least 9 days. Monolix version 2023R1 was used for NLMEM. Monte Carlo simulations (MCS) were performed to visualize the relationship of body size descriptors to the exposure to rifampicin. Results A one-compartment model with nonlinear (Michaelis–Menten) elimination and zero-order absorption kinetics with a lag time best described the data. The covariate model including fat-free mass (FFM) on volume of distribution (V/F) and on maximum elimination rate (Vmax/F) lowered the objective function value (OFV) by 56.4. The second-best covariate model of sex on V/F and Vmax/F and BW on V/F reduced the OFV by 51.2. The decrease in unexplained inter-individual variability on Vmax/F in both covariate models was similar. For a given dose, MCS showed lower exposure to rifampicin with higher FFM and accordingly in males compared to females with the same BW and body height. Conclusion Our results indicate that beyond BW, body composition as reflected by FFM could also be relevant for optimized dosing of rifampicin. This assumption needs to be studied further in patients treated with rifampicin.

Metrics for Sustainability and Circular Economy Practices in Context to Modern Manufacturing Environment - Mohd Bilal Naim Shaikh; Mohammed Ali; Umer Masood Chaudry; Muhammad Kashif Khan (Circular Economy and Sustainability, 2024)

Enhanced capacity of thiol-functionalized sugarcane bagasse and rice husk biochars for arsenite sorption in aqueous solutions - Israr Masood ul Hasan; Nabeel Khan Niazi; Irshad Bibi; Fazila Younas; Fahad Al-Misned; Muhammad Bilal Shakoor; Fawad Ali; Shazia Ilyas; Muhammad Mahroz Hussain; Jinli Qiao; Andreas Lüttge (Environmental Science and Pollution Research, 2024)
The utilization of biowastes for producing biochar to remove potentially toxic elements from water represents an important pathway for aquatic ecosystem decontamination. Here we explored the significance of thiol-functionalization on sugarcane bagasse biochar (Th/SCB–BC) and rice husk biochar (Th/RH–BC) to enhance arsenite (As(III)) removal capacity from water and compared their efficiency with both pristine biochars (SCB–BC and RH–BC). The maximum As(III) sorption was found on Th/SCB–BC and Th/RH–BC (2.88 and 2.51 mg g −1 , respectively) compared to the SCB–BC and RH–BC (1.51 and 1.40 mg g −1 ). Relatively, a greater percentage of As(III) removal was obtained with Th/SCB–BC and Th/RH–BC (92% and 83%, respectively) at a pH 7 compared to pristine SCB–BC and RH–BC (65% and 55%) at 6 mg L −1 initial As(III) concentration, 2 h contact time and 1 g L −1 sorbent dose. Langmuir ( R 2 = 0.99) isotherm and pseudo-second-order kinetic ( R 2 = 0.99) models provided the best fits to As(III) sorption data. Desorption experiments indicated that the regeneration ability of biochars decreased and it was in the order of Th/SCB–BC (88%) > Th/RH–BC (82%) > SCB–BC (77%) > RH–BC (69%) up to three sorption–desorption cycles. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy results demonstrated that the thiol (-S–H) functional groups were successfully grafted on the surface of two biochars and as such contributed to enhance As(III) removal from water. Spectroscopic data indicated that the surface functional moieties, such as -S–H, − OH, − COOH, and C = O were involved to increase As(III) sorption on thiol-functionalized biochars. This study highlights that thiol-grafting on both biochars, notably on SCB–BC, enhanced their ability to remove As(III) from water, which can be used as an effective technique for the treatment of As from drinking water. Graphical Abstract

Functionality of wheat straw-derived biochar enhanced its efficiency for actively capping Cd and Pb in contaminated water and soil matrices: Insights through batch adsorption and flow-through experiments - Yasir Hamid; Yonglong Chen; Qiang Lin; Muhammad Haris; Muhammad Usman; Muhammad Saqib Rashid; Ioannis Anastopoulos; Bilal Hussain; Hayssam M. Ali; Fakhir Hannan; Xianyuan Yin; Xiaoe Yang (Chemosphere, 2024)

Exploring the efficacy of plant growth promoters in nutrient acquisition and antioxidant defense responses of late sown wheat under saline conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Wahidah H. Al-Qahtani; Pankaj Sharma; Azamal Husen; Jun Li (South African Journal of Botany, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Bio-perfume guns: Antifungal volatile activity of Bacillus sp. LNXM12 against postharvest pathogen Botrytis cinerea in tomato and strawberry - Abdur Rashid Khan; Qurban Ali; Muhammad Ayaz; Muhammad Saqib Bilal; Hamza Tariq; Mahmoud H. El-Komy; Qin Gu; Huijun Wu; Joachim Vater; Xuewen Gao (Pesticide Biochemistry and Physiology, 2024)

Leaching kinetics of ash impurities from aphanitic graphite by combining dual-ultrasound and hydrochloric acid–potassium hydrogen fluoride - Xiangning Bu; Zheng Tong; Xibing Ren; Muhammad Bilal; Chao Ni (Minerals Engineering, 2024)

An updated and gridded probabilistic seismic hazard assessment of Quetta city, Pakistan using multiple source models - Bilal Saif; Mohammad Tahir; Muhammad Ali Shah; Muhammad Naveed Mushtaq; Muhammad Yousaf Khan; Azmat Azad; Talat Iqbal (Journal of Asian Earth Sciences, 2024)

A novel computational methodology to design solar radiation absorbing glass - Faraan Fareed; Uzma Habib; Hafiz Ali Haider Sehole; Salma Sherbaz; Muhammad Bilal Khan Niazi; Adnan Maqsood (Energy and Buildings, 2024)

The Acute Impact of Propofol on Blood–Brain Barrier Integrity in Mice - Ehsan Nozohouri; Yeseul Ahn; Sumaih Zoubi; Dhavalkumar Patel; Sabrina Rahman Archie; Khondker Ayesha Akter; Muhammad Bilal Siddique; Juyang Huang; Thomas J. Abbruscato; Ulrich Bickel (Pharmaceutical Research, 2024)

Efficacy of activated carbon using Salvadora persica stem for remediation of potentially toxic dyes from aqueous solution - Muhammad Bilal; Wahid Ullah; Tahir Abbas; Javed Ali; Syed Shah Hassan; Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan (Environmental Monitoring and Assessment, 2024)

Impacts of low temperatures, storage durations and food attractants in the parasitoid Dirhinus giffardii (Silvestri) and host Bactrocera zonata (Saunders) - Muhammad Sarwar; Bilal Rasool; Nazir Ahmad; Sayed Muhammad Masoom Shah (International Journal of Tropical Insect Science, 2024)

Ranitidine degradation in layered double hydroxide activated peroxymonosulfate system: impact of transition metal composition and reaction mechanisms - Afia Sharmin; Muhammad Bilal Asif; Guomin Zhang; Muhammed A. Bhuiyan; Biplob Pramanik (Environmental Science and Pollution Research, 2024)
Ranitidine, a competitive inhibitor of histamine H 2 receptors, has been identified as an emerging micropollutant in water and wastewater, raising concerns about its potential impact on the environment and human health. This study aims to address this issue by developing an effective removal strategy using two types of layered double hydroxide (LDH) catalysts (i.e., CoFeLDH and CoCuLDH). Characterization results show that CoFeLDH catalyst has superior catalytic properties due to its stronger chemical bond compared to CoCuLDH. The degradation experiment shows that 100% degradation of ranitidine could be achieved within 20 min using 25 mg/L of CoFeLDH and 20 mg/L of peroxymonosulfate (PMS). On the other hand, CoCuLDH was less effective, achieving only 70% degradation after 60 min at a similar dosage. The degradation rate constant of CoFeLDH was 10 times higher than the rate constant of CoCuLDH at different pH range. Positive zeta potential of CoFeLDH made it superior over CoCuLDH regarding catalytic oxidation of PMS. The catalytic degradation mechanism shows that sulfate radicals played a more dominant role than hydroxyl radicals in the case of LDH catalysts. Also, CoFeLDH demonstrated a stronger radical pathway than CoCuLDH. XPS analysis of CoFeLDH revealed the cation percentages at different phases and proved the claim of being reusable even after 8 cycles. Overall, the findings suggest that CoFeLDH/PMS system proves to be a suitable choice for attaining high degradation efficiency and good stability in the remediation of ranitidine in wastewater.

Retraction Note: The detoxification of heavy metals from aqueous environment using nano-photocatalysis approach: a review - Muhammad Bilal Tahir; Habiba Kiran; Tahir Iqbal (Environmental Science and Pollution Research, 2024)

Reactive layered hydroxide membrane for advanced water treatment: Micropollutant degradation and antifouling potential - Afia Sharmin; Muhammad Bilal Asif; Guomin Zhang; Muhammed A. Bhuiyan; Biplob Kumar Pramanik (Chemosphere, 2024)

Improving the efficiency of photovoltaic-thermoelectric generator system using novel flying squirrel search optimization algorithm: Hybrid renewable and thermal energy system (RTES) for electricity generation - Muhammad Yaqoob Javed; Aamer Bilal Asghar; Khazina Naveed; Ali Nasir; Basem Alamri; Muhammad Aslam; Essam A. Al-Ammar; Zsolt Conka (Process Safety and Environmental Protection, 2024)

Cold plasma: A success road to mycotoxins mitigation and food value edition - Bilal Murtaza; Lili Wang; Xiaoyu Li; Muhammad Kashif Saleemi; Muhammad Yasir Nawaz; Mengyao Li; Yongping Xu (Food Chemistry, 2024)

Comparative influence of active PLA and PP films on the quality of minimally processed cherry tomatoes - Muhammad Rehan Khan; Lukas Vapenka; Muhammad Bilal Sadiq; Elena Torrieri; Ales Rajchl (Food Packaging and Shelf Life, 2024)

Understanding adefovir pharmacokinetics as a component of a transporter phenotyping cocktail - Qian Dong; Chunli Chen; Max Taubert; Muhammad Bilal; Martina Kinzig; Fritz Sörgel; Oliver Scherf-Clavel; Uwe Fuhr; Charalambos Dokos (European Journal of Clinical Pharmacology, 2024)
Purpose Adefovir (as dipivoxil) was selected as a probe drug in a previous transporter cocktail phenotyping study to assess renal organic anion transporter 1 (OAT1), with renal clearance (CL R ) as the primary parameter describing renal elimination. An approximately 20% higher systemic exposure of adefovir was observed when combined with other cocktail components (metformin, sitagliptin, pitavastatin, and digoxin) compared to sole administration. The present evaluation applied a population pharmacokinetic (popPK) modeling approach to describe adefovir pharmacokinetics as a cocktail component in more detail. Methods Data from 24 healthy subjects were reanalyzed. After establishing a base model, covariate effects, including the impact of co-administered drugs, were assessed using forward inclusion then backward elimination. Results A one-compartment model with first-order absorption (including lag time) and a combination of nonlinear renal and linear nonrenal elimination best described the data. A significantly higher apparent bioavailability (73.6% vs. 59.0%) and a lower apparent absorption rate constant (2.29 h −1 vs. 5.18 h −1 ) were identified in the combined period compared to the sole administration period, while no difference was seen in renal elimination. The population estimate for the Michaelis-Menten constant (K m ) of the nonlinear renal elimination was 170 nmol/L, exceeding the observed range of adefovir plasma maximum concentration, while the maximum rate (V max ) of nonlinear renal elimination was 2.40 µmol/h at the median absolute estimated glomerular filtration rate of 105 mL/min. Conclusion The popPK modeling approach indicated that the co-administration primarily affected the apparent absorption and/or prodrug conversion of adefovir dipivoxil, resulting in the minor drug-drug interaction observed for adefovir as a victim. However, renal elimination remained unaffected. The high K m value suggests that assessing renal OAT1 activity by CL R has no relevant misspecification error with the cocktail doses used.

Novel strategy to raise the content of aglycone isoflavones in soymilk and gel: Effect of germination on the physicochemical properties - Guannan Liu; Jie Zhou; Sijin Wu; Shijie Fang; Muhammad Bilal; Chong Xie; Pei Wang; Yongqi Yin; Runqiang Yang (Food Research International, 2024)

Cross-cultural adaptation, validation and reliability analysis of child food neophobia scale among Pakistani preschoolers - Muhammad Jamal Khan; Almab Zainab; Syed Ubaid Ullah Shah; Muhammad Bilal Khan; Minchan Wu; Jiaqi Huo; Hanshuang Zou; Qian Lin (Food Quality and Preference, 2024)

Recent Advances of carbon Pathways for Sustainable Environment development - K.S. Aryamol; Kuppusamy Kanagaraj; Senthilkumar Nangan; Jozef T. Haponiuk; Manunya Okhawilai; Saravanan Pandiaraj; Muhammad Bilal Hanif; Abdullah N. Alodhayb; Sabu Thomas; Natesan Thirumalaivasan; Sreeraj Gopi (Environmental Research, 2024)

Qualitative and quantitative analysis of high-value metabolites from callus culture of Alcea rosea L. - Hasnat Tariq; Anisa Andleeb; Sannia Batool; Urooj Ali; Muhammad Waqas; Abdul Wahab; Gouhar Zaman; Samantha Drouet; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

Exogenous Application of Plant Growth Regulators Improves Economic Returns, Grain Yield and Quality Attributes of Late-Sown Wheat under Saline Conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Hira Shair; Muhammad Farooq; Jun Li (International Journal of Plant Production, 2024)

Pyridine-2,6-Dicarboxylic Acid As a Facile and Highly Selective “Turn-Off” Fluorimetric Chemosensor for Detection of Cu (II) Ions in Aqueous Media - Javed Hussain Shah; Shahzad Sharif; Muhammad Shahbaz; Bilal Riaz; Sundas Shahzad; Onur Şahin; Khurram Shahzad Munawar; Hijaz Ahmad; Essam A. Al-Ammar (Journal of Fluorescence, 2024)

Silver oxide doped iron oxide/alginate nanocomposite coated cotton cloth for selective catalytic reduction of potassium ferricyanide - Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan; Abdullah M. Asiri; Tahseen Kamal; Muhammad Bilal; Shahid Ali Khan (Chemosphere, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Rock avalanche-induced air blasts: Implications for landslide risk assessments - Yu Zhuang; Perry Bartelt; Aiguo Xing; Muhammad Bilal (Geomorphology, 2024)

Experiments and analytical model for axial strength of FRP-reinforced reactive powder concrete circular columns under axial compression - Khaled Mohamed Elhadi; Abdellatif Selmi; Ali Raza; Bilal Ahmed; Mohamed Hechmi El Ouni; Muhammad Arshad (Engineering Structures, 2024)

Biocatalytic Functionalities of Lignin Peroxidase-Based Systems in Lignin Depolymerization and Pollutants Removal from Environmental Matrices - Anil Kumar Singh; Roberto Fernandez-Lafuente; Jens Ejbye Schmidt; Grzegorz Boczkaj; Muhammad Bilal (Current Pollution Reports, 2024)
Purpose of Review In the presented review, we have summarized and highlighted recent developments in the use of lignin peroxidase (LiP) to remove a variety of pollutants from water matrices. The high redox potential of LiP is underlined by its excellent catalytic functionalities in the elimination of pharmaceuticals, phenolics, dyes, polycyclic aromatic hydrocarbons (PAHs), endocrine-disrupting chemicals (EDCs), and other miscellaneous pollutants. LiP-based computational frameworks for theoretical bioremediation of multiple pollutants have also been discussed, which have prompted a rise in scientific interest. Recent Findings According to current studies, both free and immobilized LiPs are biocatalysts capable of efficient pollutant degradation and LMW transformation. Some immobilized LiP preparations demonstrated excellent recyclability, enabling its reusability in multiple catalytic cycles. Additionally, computational degradability makes it easier to comprehend the mechanisms underlying the degradation of recalcitrant pollutants. Summary The capacity of LiP to cleave C–C and C–O–C bonds has led to its widespread application as a biocatalyst. Its outstanding potential to catalyze oxidative cleavage has been effectively used in the remediation of pollutants without needing mediators. Nevertheless, we brought attention to the current LiP system in pollutants remediation and computational framework, which has generated a significant rise in scientific interest.

Supplementation of nano-biochar improved growth and physiological attributes in wheat seedlings exposed to salt stress through enhanced activity of hydrolysing and nitrogen metabolic enzymes and regulation of crucial metabolites - Waqas Yousaf; Anis Ali Shah; Muhammad Bilal Afzal; Zaib-un Nisa; Naila Ali; Muhammad Yasin Ashraf; Hosam O. Elansary; Aqeel Ahmad (South African Journal of Botany, 2024)

Hydrogen from sewage sludge: Production methods, influencing factors, challenges, and prospects - Usman Khan; Muhammad Bilal; Hossain Md. Adil; Nnabodo Darlington; Ahsan Khan; Nouman Khan; I. Ihsanullah (Science of The Total Environment, 2024)

Assessing the impact of geopolitical, economic, and institutional factors on China's environmental management in the Russian-Ukraine conflicting era - Bilal Ahmed; Salman Wahab; Syed Rahim; Muhammad Imran; Afaq Ahmad Khan; Mohammed Moosa Ageli (Journal of Environmental Management, 2024)

Evaluation of soil texture classification from orthodox interpolation and machine learning techniques - Lei Feng; Umer Khalil; Bilal Aslam; Bushra Ghaffar; Aqil Tariq; Ahsan Jamil; Muhammad Farhan; Muhammad Aslam; Walid Soufan (Environmental Research, 2024)

Highly efficient micropollutant decomposition by ultrathin amorphous cobalt-iron oxide nanosheets in peroxymonosulfate-mediated membrane-confined catalysis - Muhammad Bilal Asif; Seok-Jin Kim; Thien S. Nguyen; Javeed Mahmood; Cafer T. Yavuz (Chemical Engineering Journal, 2024)

Toxicological assessment of dietary exposure of polyethylene microplastics on growth, nutrient digestibility, carcass and gut histology of Nile Tilapia (Oreochromis niloticus) fingerlings - Muhammad Mahmood; Syed Makhdoom Hussain; Pallab K. Sarker; Shafaqat Ali; Muhammad Saleem Arif; Nadia Nazish; Danish Riaz; Nisar Ahmad; Bilal Ahamad Paray; Adan Naeem (Ecotoxicology, 2024)

Depositional and Bio-Sequence Stratigraphic Framework of Late Cretaceous Kawagarh Formation, Kala-Chitta Range, Pakistan: Equivalent of Gurpi Formation (Iran) - Muhammad Awais; Bilal Wadood; Muhammad Ishaq; Muhammad Bilal; Zeeshan Zafar; Nasar Khan; Aminullah Khan (Journal of Earth Science, 2024)

Enhancing the Quality and Fruit Yield of Sweet Cherry (Prunus Avium) Cultivars by Foliar Application of Boron - Muhammad Sajid; Abdul Basit; Syed Tanveer Shah; Ayesha Khan; Izhar Ullah; Muhammad Bilal; Muhammad Suleman Khan; Waleed Khan (Applied Fruit Science, 2024)

Harnessing the power of bacterial laccases for xenobiotic degradation in water: A 10-year overview - Mujeeb ur Rahman; Muhammad Wajid Ullah; Junaid Ali Shah; Sivasamy Sethupathy; Hazart Bilal; Sidikov Akmal Abdikakharovich; Afaq Ullah Khan; Khalid Ali Khan; Noureddine Elboughdiri; Daochen Zhu (Science of The Total Environment, 2024)

RNA based gene silencing modalities to control insect and fungal plant pests – Challenges and future prospects - Muhammad Waqas Choudry; Pashma Nawaz; Neelam Jahan; Rabia Riaz; Bilal Ahmed; Muhammad Hassan Raza; Zohaib Fayyaz; Kausar Malik; Samia Afzal (Physiological and Molecular Plant Pathology, 2024)

Reduced graphene oxide supported polyaniline/copper (II) oxide nanostructures for enhanced photocatalytic degradation of Congo red and hydrogen production from water - Mohsin Raza Dustgeer; Asim Jilani; Mohammad Omaish Ansari; Muhammad Bilal Shakoor; Shafaqat Ali; Aniqa Imtiaz; Hazirah Syahirah Zakria; Mohd Hafiz Dzarfan Othman (Journal of Water Process Engineering, 2024)

An intercomparison of SEMARA high-resolution AOD and MODIS operational AODs - Mozhgan Bagherinia; Siamak Bodaghpour; Neamat Karimi; Eslam Javadnia; Muhammad Bilal; Alaa Mhawish (Atmospheric Pollution Research, 2024)

Formation mechanism and dynamic process of open-pit coal mine landslides: a case study of the Xinjing landslide in Inner Mongolia, China - Qiankuan Wang; Aiguo Xing; Xueyong Xu; Ye Zhou; Qiang Yang; Hongzhu Song; Jun Peng; Longxiang Zhai; Muhammad Bilal; Yiwei Liu (Landslides, 2024)

Zinc-Coated Urea with Gelatin-Enhanced Zinc Biofortification, Apparent Nitrogen Recovery, and Ryegrass Production - Bilal Abdullah; Muhammad Bilal Khan Niazi; Zaib Jahan; Tariq Shah; Umer Shahzad Malik; Bilal Beig; Abid Mahmood; Ghulam Abbas Shah; Zahid Iqbal (Journal of Soil Science and Plant Nutrition, 2024)

Soil Carbon Mineralization and Aggregate Distribution in Various Tillage Practices of Rice–Wheat Cropping System: A Field and Laboratory Study - Naeem Ahmad; Ahmad Latif Virk; Muhammad Bilal Hafeez; Zheng-Rong Kan; Zujiao Shi; Rui Wang; Hafiz Muhammad Waleed Iqbal; Muhammad Ishaq Asif Rehmani; Xiaoli Wang; Rattan Lal; Jun Li (Journal of Soil Science and Plant Nutrition, 2024)

Wound healing, antioxidant and antibacterial activities of polyphenols of Psidium guajava L. leaves - Kainat Bilal; Fatima Mehboob; Nosheen Akhtar; Irfan Ali Mirza; Muhammad K. Okla; M. Junaid Dar; Ibrahim A. Saleh; Naser Zomot; Humaira Fatima (South African Journal of Botany, 2024)

Progress in layered double hydroxides (LDHs): Synthesis and application in adsorption, catalysis and photoreduction - Ahmad Farhan; Aman Khalid; Nimra Maqsood; Sidra Iftekhar; Hafiz Muhammad Adeel Sharif; Fei Qi; Mika Sillanpää; Muhammad Bilal Asif (Science of The Total Environment, 2024)

Carbon trade-off and energy budgeting under conventional and conservation tillage in a rice-wheat double cropping system - Naeem Ahmad; Ahmad Latif Virk; Abdul-Sattar Nizami; Rattan Lal; Scott X. Chang; Muhammad Bilal Hafeez; Xingyu Guo; Rui Wang; Xiaoli Wang; Hafiz Muhammad Waleed Iqbal; Gadah Albasher; Jun Li (Journal of Environmental Management, 2024)

RETRACTED: Straw incorporation into microplastic-contaminated soil can reduce greenhouse gas emissions by enhancing soil enzyme activities and microbial community structure - Tariq Shah; Zeeshan Khan; Muhammad Asad; Ayesha Imran; Muhammad Bilal Khan Niazi; Raf Dewil; Ajaz Ahmad; Parvaiz Ahmad (Journal of Environmental Management, 2024)

New trends in functionalities and extraction of plant proteins in designing plant-based meat analogues: A critical review - Aaysha Ihsan; Zia Ahmad; Jie Zheng; Muhammad Bilal; Hafiz Muhammad Rizwan Abid; Aijun Hu (Food Bioscience, 2024)

Zinc sulfate as a draw solute in forward osmosis and its regeneration by reagent precipitation - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Kew-Ho Lee (Desalination, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Role of biogas slurry to reclaim soil properties providing an eco-friendly approach for crop productivity - Asif Mukhtiar; Athar Mahmood; Muhammad Anjum Zia; Muaz Ameen; Renji Dong; Yang Shoujun; Muhammad Mansoor Javaid; Bilal Ahmad Khan; Muhammad Ather Nadeem (Bioresource Technology Reports, 2024)

Chimaphila umbellata; a biotechnological perspective on the coming-of-age prince’s pine - Urooj Ali; Muhammad Mustajab Khan; Naveera Khan; Rida tul Haya; Muhammad Usama Asghar; Bilal Haider Abbasi (Phytochemistry Reviews, 2024)

Inversion techniques for focal mechanism determination of small-magnitude earthquakes: a comparative study using the Burewala earthquake ($$M_w$$ $$\sim $$ 4) in Pakistan - Sadia Sabahat; Mohammad Tahir; Fatima Munir; Bilal Saif; Muhammad Tahir Iqbal; Javed Iqbal; Talat Iqbal (Journal of Seismology, 2024)

Evaluating the Morpho-physiological Responses of Stevia (Stevia rebaudiana) to Foliar Application of Various Plant Growth Promoters Under Drought Stress - Fatima Ahmadzai; Kanval Shaukat; Hafiz Mohammad Akram; Mahmood ur Rehman Ansari; Noreen Zahra; Abdul Samad; Mereen Nizar; Muhammad Bilal Hafeez; Ali Raza (Journal of Crop Health, 2024)

Synergistic effect of combating air pollutants and carbon emissions in the Yangtze River Delta of China: spatial and temporal divergence analysis and key influencing factors - Fang Liu; Anqi Li; Muhammad Bilal; Yuwei Yang (Environmental Science and Pollution Research, 2024)

Enhancement in the production of phenolic compounds from Fagonia indica callus cultures via Fusarium oxysporum triggered elicitation - Taimoor Khan; Muhammad Uzair Javed; Tehreem Mahmood; Bushra Khan; Tariq Khan; Muhammad Asad Ullah; Razia Khurshid; Gouhar Zaman; Christophe Hano; Nathalie Giglioli-Guivarc’h; Bilal Haider Abbasi (In Vitro Cellular & Developmental Biology - Plant, 2024)

Analyzing employees’ green behavioral intention in the hospitality industry: a multilevel model - Bilal Khalid; Khurram Shahzad; Muhammad Usman Anwar Baig (Environment, Development and Sustainability, 2024)

Fucoidan-based nanomaterial and its multifunctional role for pharmaceutical and biomedical applications - Muhammad Waheed Iqbal; Tahreem Riaz; Shahid Mahmood; Muhammad Bilal; Muhammad Faisal Manzoor; Sarmad Ahmad Qamar; Xianghui Qi (Critical Reviews in Food Science and Nutrition, 2024)

A systematic review on potential microbial carbohydrases: current and future perspectives - Dilshad Begum Golgeri M.; Sikandar I. Mulla; Zabin K. Bagewadi; Swati Tyagi; Anyi Hu; Swati Sharma; Muhammad Bilal; Ram Naresh Bharagava; Luiz Fernando R. Ferreira; Dummi Mahadevan Gurumurthy; Ashok Kumar Nadda (Critical Reviews in Food Science and Nutrition, 2024)

Remediation of Cd-polluted soil, improving Brassica napus L. growth and soil health with Hardystonite synthesized with zeolite, limestone, and green Zinc oxide nanoparticles - Fakhir Hannan; Muhamamd Iqbal; Faisal Islam; Muhammamd A. Farooq; Muhammad Bilal Shakoor; Ahsan Ayyaz; Muhammad Saad Shoaib Khan; Juanjuan Li; Qian Huang; Weijun Zhou (Journal of Cleaner Production, 2024)

Navigating environmental concerns: Unveiling the role of economic growth, trade, resources and institutional quality on greenhouse gas emissions in OECD countries - Salman Wahab; Muhammad Imran; Bilal Ahmed; Syed Rahim; Taimoor Hassan (Journal of Cleaner Production, 2024)

Enzyme-linked carbon nanotubes as biocatalytic tools to degrade and mitigate environmental pollutants - Muhammad Bilal; Anil Kumar Singh; Hafiz M.N. Iqbal; Jakub Zdarta; Anna Chrobok; Teofil Jesionowski (Environmental Research, 2024)

Development and testing of environment friendly nanohybrid coatings for sustainable agriculture technologies - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Munir Zia; Ghulam Abbas Shah; Ayman A. Ghfar; Zahid Iqbal (Environmental Research, 2024)

Chitooligosaccharide modified pesticide-loaded polyurethane microcapsules to mitigate drought stress in wheat - Ge Chen; WenJie Shangguan; HuiPing Chen; ChunLi Xu; Muhammad Bilal; PengYue Zhao; Chong Cao; ManLi Yu; QiLiang Huang; LiDong Cao (Chemical Engineering Journal, 2024)

Recalling the reported toxicity assessment of deoxynivalenol, mitigating strategies and its toxicity mechanisms: Comprehensive review - Bilal Murtaza; Lili Wang; Xiaoyu Li; Muhammad Yasir Nawaz; Muhammad Kashif Saleemi; Aisha Khatoon; Xu Yongping (Chemico-Biological Interactions, 2024)

Long-term validation and error analysis of DB and MAIAC aerosol products over bright surface of China - Weiqian Ji; Leiku Yang; Xinyao Tian; Muhammad Bilal; Xin Pei; Yu Zheng; Xiaofeng Lu; Xiaoqian Cheng (Atmospheric Research, 2024)

Deciphering the Role of Phytohormones and Osmolytes in Plant Tolerance Against Salt Stress: Implications, Possible Cross-Talk, and Prospects - Sadam Hussain; Muhammad Bilal Hafeez; Rabia Azam; Kashf Mehmood; Marjan Aziz; Sezai Ercisli; Talha Javed; Ali Raza; Noreen Zahra; Saddam Hussain; Xiaolong Ren (Journal of Plant Growth Regulation, 2024)

Detection of high-risk human papillomavirus infected cervical biopsies samples by immunohistochemical expression of the p16 tumor marker - Muhammad Shafique; Iqra Shoaib; Bilal Aslam; Rabia Khalid; Imrana Tanvir; Muhammad Hidayat Rasool; Tawaf Ali Shah; Khalid S. Almaary; Mohammed Bourhia; Muhammad Usman Qamar (Archives of Microbiology, 2024)

Surveillance of pesticide residues in tomato and eggplant and assessment of acute and chronic health risks to the consumers in Pakistan - Aasma Bibi; Farida Anjum; Syed Roohul Hussain; Abdul Ahad; Azeem Ud Deen; Muhammad Suleman; Bilal Jan (Environmental Science and Pollution Research, 2023)

Unlocking green innovation and environmental performance: the mediated moderation of green absorptive capacity and green innovation climate - Sadaf Akhtar; Cai Li; Jan Muhammad Sohu; Yasir Rasool; Muhammad Iatzaz Ul Hassan; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Pathological effects of feeding aflatoxin-contaminated feed on immune status and reproductive performance of juvenile white leghorn males and its mitigation with ∝-tocopherol and Moringa oleifera - Muhammad Kashif Saleemi; Ahmad Raza; Aisha Khatoon; Muhammad Zubair; Shafia Tehseen Gul; Xu Yongping; Bilal Murtaza; Faqir Muhammad; Bushra Akhtar; Farhat Jubeen; Farzana Rizvi; Khawar Zubair; et al. (Environmental Science and Pollution Research, 2023)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Assessment of heavy metal accumulation in dust and leaves of Conocarpus erectus in urban areas: Implications for phytoremediation - Atta ur rehman; Kousar Yasmeen; Fakhrul Islam; Shoaib Ahmad Anees; Aqil Tariq; Muhammad Zubair; Muhammad Bilal; Inayat Ur Rahman; Siddiq Ur Rahman; Wesam Atef Hatamleh (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Effect of heterogeneity on the diffusion of Pb in apatite for petrochronological applications: A multiscale approach to characterizing the influence of apatite chemistry and anisotropy on Pb diffusion - Matee Ullah; Urs Klötzli; Ce’cile Gautheron; Laurent Tassan-Got; Fakhrul Islam; Muhammad Younas; Kamran Shehzad; Muhammad Khubab; Muhammad Ibrar; Bilal Wadood (Lithos, 2023)

Does the impact of financial development reinforce sustainability ecological footprint? Fresh evidence from middle and high-income economies - Bilal Aslam; Guitao Zhang; Muhammad Asif Amjad; Shujun Guo; Maowang Ji (Journal of Cleaner Production, 2023)

Revolutionizing water purification: Unleashing graphene oxide (GO) membranes - Izaz Ali Shah; Muhammad Bilal; I. Ihsanullah; Sharafat Ali; Muhammad Yaqub (Journal of Environmental Chemical Engineering, 2023)

Well Log Analysis and Comparison of Supervised Machine Learning Algorithms for Lithofacies Identification in Pab Formation, Lower Indus Basin - Pal Washa Shahzad Rathore; Matloob Hussain; Muhammad Bilal Malik; Yawar Amin (Journal of Applied Geophysics, 2023)

RETRACTED: Bio-mitigation of organic pollutants using horseradish peroxidase as a promising biocatalytic platform for environmental sustainability - Muhammad Bilal; Anil Kumar Singh; Hafiz M.N. Iqbal; Tak H. Kim; Grzegorz Boczkaj; Khawlah Athmaneh; Syed Salman Ashraf (Environmental Research, 2023)

RETRACTED: Recent advances in microstructural control via thermal spraying for solid oxide fuel cells - Jiu-Tao Gao; Muhammad Bilal Hanif; Hui-Yu Zhang; Martin Motola; Cheng-Xin Li (Chemical Engineering Journal, 2023)

Pb diffusion in perfect and defective zircon for thermo/petro-chronological investigations: An atomistic approach - Matee Ullah; Urs Klötzli; Bilal Wadood; Muhammad Khubab; Fakhrul Islam; Kamran Shehzad; Rafique Ahmad (Chemical Geology, 2023)

Sequence variants in different genes underlying Bardet-Biedl syndrome in four consanguineous families - Amjad Ali; Abdullah; Muhammad Bilal; Emily Kathryn Mis; Saquib Ali Lakhani; Wasim Ahmad; Imran Ullah (Molecular Biology Reports, 2023)

Subtractive sequence analysis aided druggable targets mining in Burkholderia cepacia complex and finding inhibitors through bioinformatics approach - Syed Shah Hassan; Rida Shams; Ihosvany Camps; Zarrin Basharat; Saman Sohail; Yasmin Khan; Asad Ullah; Muhammad Irfan; Javed Ali; Muhammad Bilal; Carlos M. Morel (Molecular Diversity, 2023)

Role of Aminolevulinic Acid in Mediating Salinity Stress Tolerance in Sunflower (Helianthus annuus L.) - Irfana Lalarukh; Noreen Zahra; Aleena Shahzadi; Muhammad Bilal Hafeez; Sehar Shaheen; Abida Kausar; Ali Raza (Journal of Soil Science and Plant Nutrition, 2023)

Transcriptomic analysis approach towards an improved tolerance of Escherichia coli to gallic acid stress - Lina Liu; Shijie Tang; Tingting Liu; Zihao Zhang; Xuefeng Wang; Muhammad Bilal; Shuai Liu; Hongzhen Luo; Yuping Zhao; Xuguo Duan (Archives of Microbiology, 2023)

Deep-Neural-Network-Based Receiver Design for Downlink Non-Orthogonal Multiple-Access Underwater Acoustic Communication - Habib Hussain Zuberi; Songzuo Liu; Muhammad Bilal; Ayman Alharbi; Amar Jaffar; Syed Agha Hussnain Mohsan; Abdulaziz Miyajan; Mohsin Abrar Khan (Journal of Marine Science and Engineering, 2023)
The excavation of the ocean has led to the submersion of numerous autonomous vehicles and sensors. Hence, there is a growing need for multi-user underwater acoustic communication. On the other hand, due to the limited bandwidth of the underwater acoustic channel, downlink non-orthogonal multiple access (NOMA) is one of the fundamental pieces of technology for solving the problem of limited bandwidth, and it is expected to be beneficial for many modern wireless underwater acoustic applications. NOMA downlink underwater acoustic communication (UWA) is accomplished by broadcasting data symbols from a source station to several users, which uses superimposed coding with variable power levels to enable detection through successive interference cancellation (SIC) receivers. Nevertheless, comprehensive information of the channel condition and channel state information (CSI) are both essential for SIC receivers, but they can be difficult to obtain, particularly in an underwater environment. To address this critical issue, this research proposes downlink underwater acoustic communication using a deep neural network utilizing a 1D convolution neural network (CNN). Two cases are considered for the proposed system in the first case: in the first case, two users with different power levels and distances from the transmitter employ BPSK and QPSK modulations to support multi-user communication, while, in the second case, three users employ BPSK modulation. Users far from the base station receive the most power. The base station uses superimposed coding. The BELLHOP ray-tracing algorithm is utilized to generate the training dataset with user depth and range modifications. For training the model, a composite signal passes through the samples of the UWA channel and is fed to the model along with labels. The DNN receiver learns the characteristic of the UWA channel and does not depend on CSI. The testing CIR is used to evaluate the trained model. The results are compared to the traditional SIC receiver. The DNN-based DL NOMA underwater acoustic receiver outperformed the SIC receiver in terms of BER in simulation results for all the modulation orders.

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Graphene-grafted bimetallic MOF membranes for hazardous & toxic contaminants treatment - Ayesha Rehman; Zaib Jahan; Muhammad Bilal Khan Niazi; Tayyaba Noor; Farhan Javed; Sarah I. Othman; Mostafa R. Abukhadra; Alam Nawaz (Chemosphere, 2023)

How environmental regulation imperatives introduce innovation in firm financing choice among selected asian economies - Bilal Haider Subhani; Shen Zunhuan; Naheed Nawazesh Roni; Umar Farooq; Muhammad Asif Khan (Journal of Cleaner Production, 2023)

A critical review on efficient thermal environment controls in indoor vertical farming - Md Shamim Ahamed; Muhammad Sultan; Danielle Monfet; Md Sazan Rahman; Ying Zhang; Azlan Zahid; Muhammad Bilal; T.M. Abir Ahsan; Yasmine Achour (Journal of Cleaner Production, 2023)

Thermochemical conversion of agricultural waste to hydrogen, methane, and biofuels: A review - Ahmed Khan; Muhammad Bilal Khan Niazi; Reema Ansar; Zaib Jahan; Farhan Javaid; Rafiq Ahmad; Hirra Anjum; Muhammad Ibrahim; Awais Bokhari (Fuel, 2023)

Size-resolved ambient bioaerosols concentration, antibiotic resistance, and community composition during autumn and winter seasons in Qatar - Bilal Sajjad; Kashif Rasool; Azhar Siddique; Khadeeja Abdul Jabbar; Shimaa S. El-Malaha; Muhammad Umar Sohail; Fares Almomani; M. Rami Alfarra (Environmental Pollution, 2023)

Solubilization and Uptake of Phosphorus (P) by Wheat and Maize Crops from Indigenous Rock Phosphate Applied with Biogas Slurry and Bagasse Ash - Ammara Farooq; Bushra Saeed; Hafiz Muhammad Bilal; Muhammad Aamer Maqsood; Muhammad Nasim; Tariq Aziz; Minggang Xu (Water, Air, & Soil Pollution, 2023)

Large Rock Collapse-Induced Air Blast: Elucidating the Role of Geomorphology - Yu Zhuang; Muhammad Bilal; Aiguo Xing; Bin Li; Kai He; Yaoming Zhang (Rock Mechanics and Rock Engineering, 2023)

Two-dimensional frictional heating simulation based on landslide process reconstruction - Yanbo Zhang; Aiguo Xing; Bin Li; Muhammad Bilal; Wenbin Chang (Landslides, 2023)

The role of technological innovation, economic policy uncertainty, and poverty reduction in attaining environmental sustainability agenda: contextual evidence from developing South and East Asian Economies - Hummera Saleem; Muhammad Bilal Khan; Seyed Mohammadreza Mahdavian; Umar Nawaz Kayani (Environment, Development and Sustainability, 2023)

Development of ZnO-GO-NiO membrane for removal of lead and cadmium heavy metal ions from wastewater - Arslan Maqbool; Ameen Shahid; Zaib Jahan; Muhammad Bilal Khan Niazi; Muhammad Ali Inam; Ahmed M. Tawfeek; Emadeldin M Kamel; Muhammad Saeed Akhtar (Chemosphere, 2023)

Versatile application of BiVO4/TiO2 S-scheme photocatalyst: Photocatalytic CO2 and Cr(VI) reduction - Viktoriia Liapun; Muhammad Bilal Hanif; Marcel Sihor; Xenia Vislocka; Saravanan Pandiaraj; Unnikrishnan V K; Guru Karthikeyan Thirunavukkarasu; Miroslava Filip Edelmannová; Martin Reli; Olivier Monfort; Kamila Kočí; Martin Motola (Chemosphere, 2023)

Long-term PM2.5 pollution over China: Identification of PM2.5 pollution hotspots and source contributions - Md. Arfan Ali; Zhongwei Huang; Muhammad Bilal; Mazen E. Assiri; Alaa Mhawish; Janet E. Nichol; Gerrit de Leeuw; Mansour Almazroui; Yu Wang; Yazeed Alsubhi (Science of The Total Environment, 2023)

Efficient removal of hexavalent chromium Cr (VI) using magnesium-iron layered double hydroxide supported on orange peel (Mg-Fe LDH@OPP): A synthetic experimental and mechanism studies - Waleed Usmani; Muhammad Ali Inam; Rashid Iftikhar; Iqra Irfan; Rabia Adnan; Muhammad Bilal Khan Niazi; Rizwan Khan; Muhammad Hassan (Journal of Water Process Engineering, 2023)

Preservative paper containing phenolic acid grafted on chitosan for post-harvest peach preservation - Linyun Mou; Jin Zhang; Ya Lu; Muhammad Bilal; Jianlong Li; Ganpeng Li (Food Bioscience, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Enzyme-conjugated MXene nanocomposites for biocatalysis and biosensing - Muhammad Bilal; Anil Kumar Singh; Hafiz M.N. Iqbal; Grzegorz Boczkaj (Chemical Engineering Journal, 2023)

Solid-State Fermentation as a Green Technology for Biomass Valorization: Optimization Techniques for Bioprocess—An Overview - Luiz Henrique Sales de Menezes; Polyany Cabral Oliveira; Eliezer Luz do Espírito Santo; Márcia Soares Gonçalves; Muhammad Bilal; Héctor A. Ruiz; Erik Galvão Paranhos da Silva; Luiz Carlos Salay; Julieta Rangel de Oliveira; Marcelo Franco (BioEnergy Research, 2023)

Recent developments and challenges in uranium extraction from seawater through amidoxime-functionalized adsorbents - Bilal Ahmed; Zia Ahmad; Amina Khatoon; Iqra Khan; Nusrat Shaheen; Attiya Abdul Malik; Zahid Hussain; Muhammad Ali Khan (Environmental Science and Pollution Research, 2023)

Investigating symmetrical influence of economic expansion, oil price, and industrial production on trade deficit: a policy pathway toward three neighboring Asian states - Muhammad Bilal Arif; Arshad Mahmood Malik; Gulnaz Hameed; Aadil Hameed Shah; Nigah Hussain; Rabia Shahid (Environmental Science and Pollution Research, 2023)

Wood as a green and sustainable alternative for environmentally friendly & flexible electronic devices - Hizbullah Malik; Muhammad Bilal Khan Niazi; Waheed Miran; Ahmed M. Tawfeek; Zaib Jahan; Emadeldin M. Kamel; Nouman Ahmed; Muhammad Saeed Akhtar (Chemosphere, 2023)

Influence of abiotic stresses on disease infestation in plants - Noreen Zahra; Muhammad Bilal Hafeez; Manal Al Shukaily; Abdullah M. Al-Sadi; Kadambot H.M. Siddique; Muhammad Farooq (Physiological and Molecular Plant Pathology, 2023)

Techno-economic assessment of sunflower husk pellets treated with waste glycerol for the Bio-Hydrogen production– A Simulation-based case study - Bilal Kazmi; Syed Ali Ammar Taqvi; Salman Raza Naqvi; Asif Ali Mirani; Muhammad Shahbaz; Muhammad Naqvi; Dagmar Juchelková; Gaber E. Eldesoky (Fuel, 2023)

Techno-economic sustainability assessment for bio-hydrogen production based on hybrid blend of biomass: A simulation study - Syed Muhammad Mustafa Rizvi; Bilal kazmi; Syed Ali Ammar Taqvi; Mahwish Mobeen Khan; Haslinda Zabiri; Danial Qadir; Ahmed Sayed M. Metwally (Fuel, 2023)

Comparative immunocompetence and interspecies transmission of avian orthoavulavirus-1 in feral birds originating from rural and urban settings - Momena Habib; Aziz Ul-Rahman; Zia-ur-Rehman; Muhammad Akbar Shahid; Noreen Sarwar; Muhammad Bilal; Muhammad Saeed Imran; Muhammad Munir; Shaista Abbas; Muhammad Zubair Shabbir (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Ginsenosides in cancer: Targeting cell cycle arrest and apoptosis - Muhammad Ajmal Shah; Syed Muhammad Abuzar; Kainat Ilyas; Irtaza Qadees; Momna Bilal; Rimsha Yousaf; Roaa Mohammed Tahir Kassim; Azhar Rasul; Uzma Saleem; Maria Silvana Alves; Haroon Khan; Renald Blundell; et al. (Chemico-Biological Interactions, 2023)

Sustainable bioethanol production from first- and second-generation sugar-based feedstocks: Advanced bibliometric analysis - Cláudia Elisa César Guimarães; Francisco Simão Neto; Viviane de Castro Bizerra; Jean Gleison Andrade do Nascimento; Roberta Bussons Rodrigues Valério; Paulo Gonçalves de Sousa Junior; Ana Kátia de Sousa Braz; Rafael Leandro Fernandes Melo; Juliana de França Serpa; Rita Karolinny Chaves de Lima; Artemis Pessoa Guimarães; Maria Cristiane Martins de Souza; et al. (Bioresource Technology Reports, 2023)

Comprehensive insights into the regulatory mechanisms of lncRNA in alkaline-salt stress tolerance in rice - Obaid Ur Rehman; Muhammad Uzair; Muhammad Shahbaz Farooq; Bilal Saleem; Safira Attacha; Kotb A. Attia; Umer Farooq; Sajid Fiaz; Wael. H. El-Kallawy; Itoh Kimiko; Muhammad Ramzan Khan (Molecular Biology Reports, 2023)

Quality Analysis of Canola and Mustard Oil Using Fluorescence Spectroscopy - Muhammad Saleem; Hina Ali; M. Bilal; Babar M. Atta; Naveed Ahmad (Journal of Fluorescence, 2023)

Transforming Lignin Biomass to Value: Interplay Between Ligninolytic Enzymes and Lignocellulose Depolymerization - Namra Ahmad; Shakira Aslam; Nazim Hussain; Muhammad Bilal; Hafiz M. N. Iqbal (BioEnergy Research, 2023)
Lignin is the main constituent of lignocellulosic biomasses, which have a significant untapped ability to replace ecologically unfavorable and non-renewable fossil fuels. The lignin is broken down by ligninolytic bacteria, which also use a peripheral pathway to transform heterogeneous lignin derivatives into central intermediates like protocatechuate or catechol. By undergoing ring cleavage through the -ketoadipate pathway, these intermediates become metabolites by producing acetyl-CoA for internal product biosynthesis, including the creation of triacylglycerols and polyhydroxyalkanoates. Expanding our understanding of ligninolytic microbial communities, strains, and enzymes through bioprospecting can help us better understand the metabolism of aromatics. The most viable idea for sustainable development is the valorization of lignin into biopolymers as well as other high-value goods. This process is now being used to generate a variety of biopolymers, including polyesters, epoxies, phenol resins, poly (lactic acids), poly hydroxyl alkanoates, and polyurethanes. Furthermore, lignin recalcitrance remained a possible barrier to efficient lignin valorization, prompting several efforts to design high-efficiency bioprocesses to produce specific polymer types as well as other important bioproducts. Graphical Abstract

The influence of exogenous melatonin and chitosan on secondary metabolites’ production and biological activities of tissue extracts in agitated micro-shoot cultures of Ajuga integrifolia Buch. Ham. ex D.Don - Muhammad Asad Ullah; Faiza Zareen Gul; Gouhar Zaman; Junaid Iqbal; Samantha Drouet; Duangjai Tungmunnithum; Christophe Hano; Bilal Haider Abbasi (Acta Physiologiae Plantarum, 2023)

Zinc oxide nanoparticles: A unique saline stress mitigator with the potential to increase future crop production - Mahmoud F. Seleiman; Awais Ahmad; Martin L. Battaglia; Hafiz Muhammad Bilal; Bushra A. Alhammad; Naeem Khan (South African Journal of Botany, 2023)

Lupeol, a plant triterpenoid mitigates salt induced stress: growth and antioxidative response of Brassica nigra under in vitro condition - Muhammad Zia; Joham Sarfraz Ali; Saad Hanif; Anila Sajjad; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Anti-arthritic effects of geranium essential oil loaded chitosan nanoparticles in Freund’s complete adjuvant induced arthritic rats through down-regulation of inflammatory cytokines - Rana Dawood Naseer; Faqir Muhammad; Bilal Aslam; Muhammad Naeem Faisal (Inflammopharmacology, 2023)

Surface water quality, public health, and ecological risks in Bangladesh—a systematic review and meta-analysis over the last two decades - Hazrat Bilal; Xiaowen Li; Muhammad Shahid Iqbal; Yonglin Mu; Roberto Xavier Supe Tulcan; Muhammad Asad Ghufran (Environmental Science and Pollution Research, 2023)

Simultaneous removal of ternary heavy metal ions by a newly isolated Microbacterium paraoxydans strain VSVM IIT(BHU) from coal washery effluent - Veer Singh; Jyoti Singh; Nidhi Singh; Sachchida Nand Rai; Manoj Kumar Verma; Manisha Verma; Vishal Singh; Mahesh Sanjay Chivate; Muhammad Bilal; Vishal Mishra (BioMetals, 2023)

Improved photocatalytic decolorization of reactive black 5 dye through synthesis of graphene quantum dots–nitrogen-doped TiO2 - Muhammad Saqib Khan; Nadia Riaz; Saeed Rehman; Liu Chenhui; Ahson Jabbar Shaikh; Muhammad Arfan; Iftikhar Zeb; Muhammad Arshad; Farhan Hafeez; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Economic and non-economic drivers of tourism: bidirectional causality of tourism and environment for South Asian economies - Salman Wahab; Bilal Ahmed; Muhammad Imran; Adnan Safi; Zeeshan Wahab (Environmental Science and Pollution Research, 2023)

Influence of heat stress during grain development on the wheat grain yield, quality, and composition - Muhammad Bilal Hafeez; Noreen Zahra; Abida Kausar; Jun Li; Abdul Rehman; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Multifunctional catalyst-assisted sustainable reformation of lignocellulosic biomass into environmentally friendly biofuel and value-added chemicals - Muhammad Naeem; Muhammad Imran; Shoomaila Latif; Adnan Ashraf; Nazim Hussain; Grzegorz Boczkaj; Wojciech Smułek; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Effective assessment of biopolymer-based multifunctional sorbents for the remediation of environmentally hazardous contaminants from aqueous solutions - Shahid Nawaz; Andleeb Tabassum; Sara Muslim; Tayyaba Nasreen; Ausra Baradoke; Tak H. Kim; Grzegorz Boczkaj; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Solar light driven degradation of textile dye contaminants for wastewater treatment – studies of novel polycationic selenide photocatalyst and process optimization by response surface methodology desirability factor - Arif Nawaz; Muhammad Atif; Adnan Khan; Mohsin Siddique; Nisar Ali; Falak Naz; Muhammad Bilal; Tak H. Kim; Malwina Momotko; Hameed Ul Haq; Grzegorz Boczkaj (Chemosphere, 2023)

Modulation of growth and biochemical responses in spinach (Spinacia oleracea L.) through foliar application of some amino acids under drought conditions - Abida Kausar; Noreen Zahra; Hira Tahir; Muhammad Bilal Hafeez; Waseem Abbas; Ali Raza (South African Journal of Botany, 2023)

Screening and growth assessment of indigenous and exotic sesame genotypes under osmotic stress - Jahangir Ahmed; Ghulam Qadir; Muhammad Fraz Ali; Talha Javed; Hafiz Muhammad Jhanzab; Fahad Masoud Wattoo; Imran Mahmood; Muhammad Ansar; Muhammad Akram Khan; Usman Zulfiqar; Bilal Ahamad Paray (South African Journal of Botany, 2023)

Effect of wind and solar energy production, and economic development on the environmental quality: Is this the solution to climate change? - Bilal Hussain; Syed Asif Ali Naqvi; Sofia Anwar; Muhammad Usman (Gondwana Research, 2023)

Bio-fabricated bismuth-based materials for removal of emerging environmental contaminants from wastewater - Zohaib Saddique; Muhammad Imran; Ayesha Javaid; Shoomaila Latif; Tak H. Kim; Marcin Janczarek; Muhammad Bilal; Teofil Jesionowski (Environmental Research, 2023)

Hydroxylated polymethoxyflavones reduce the activity of pancreatic lipase, inhibit adipogenesis and enhance lipolysis in 3T3-L1 mouse embryonic fibroblast cells - Bilal Ahmad; Emily P. Friar; Muhammad Sufyan Vohra; Nasar Khan; Christopher J. Serpell; Michelle D. Garrett; Jason Siau Ee Loo; Isabel Lim Fong; Eng Hwa Wong (Chemico-Biological Interactions, 2023)

Recent advances to Neuroprotection: repurposing drugs against neuroinflammatory disorders - Wishah Bilal; Muhammad Babar Khawar; Ali Afzal; Arshia Naseer; Syeda Eisha Hamid; Sara Shahzaman; Fareeha Qamar (Molecular Biology Reports, 2023)

A critical review and prospect of NO2 and SO2 pollution over Asia: Hotspots, trends, and sources - Most. Mastura Munia Farjana Jion; Jannatun Nahar Jannat; Md. Yousuf Mia; Md. Arfan Ali; Md. Saiful Islam; Sobhy M. Ibrahim; Subodh Chandra Pal; Aznarul Islam; Aniruddha Sarker; Guilherme Malafaia; Muhammad Bilal; Abu Reza Md Towfiqul Islam (Science of The Total Environment, 2023)

Corrigendum to “New outlook on hazardous pollutants in the wastewater environment: Occurrence, risk assessment and elimination by electrodeionization technologies” [Environ. Res. 219 (2023) 115112] - Gargi Mistry; Kartik Popat; Jimit Patel; Kashish Panchal; Huu Hao Ngo; Muhammad Bilal; Sunita Varjani (Environmental Research, 2023)

Construction and elucidation of zerovalent iron@terephthalic acid/iron oxide catalyst to activate peroxymonosulfate for accelerating and long-lasting NOx removal - Hafiz Muhammad Adeel Sharif; Muhammad Bilal Asif; Yuwei Wang; Kifayatullah Khan; Yang Cai; Xu Xiao; Changping Li (Chemical Engineering Journal, 2023)

Correction: Comparative studies of enhancing oil recovery optimization for optimum oil feld development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Azizullah Shaikh; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

Comparative studies of enhancing oil recovery optimization for optimum oil field development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

Estimating ground-level PM2.5 using subset regression model and machine learning algorithms in Asian megacity, Dhaka, Bangladesh - Abu Reza Md. Towfiqul Islam; Mohammed Al Awadh; Javed Mallick; Subodh Chandra Pal; Rabin Chakraborty; Md. Abdul Fattah; Bonosri Ghose; Most. Kulsuma Akther Kakoli; Md. Aminul Islam; Hasan Raja Naqvi; Muhammad Bilal; Ahmed Elbeltagi (Air Quality, Atmosphere & Health, 2023)

In-vitro assessment of a novel plant rhizobacterium, Citrobacter freundii, for degrading and biocontrol of food mycotoxin deoxynivalenol - Bilal Murtaza; Xiaoyu Li; Liming Dong; Muhammad Kashif Saleemi; Mazhar Iqbal; Saima Majeed; Ashiq Ali; Gen Li; Bowen Jin; Lili Wang; Yongping Xu (Toxicon, 2023)

Assembling CoAl-layered metal oxide into the gravity-driven catalytic membrane for Fenton-like catalytic degradation of pharmaceuticals and personal care products - Muhammad Bilal Asif; Hongyu Kang; Zhenghua Zhang (Chemical Engineering Journal, 2023)

Sex differences in the inflammatory response to stroke - Muhammad Bilal Tariq; Juneyoung Lee; Louise D. McCullough (Seminars in Immunopathology, 2023)

Formation and propagation of dust cloud induced by Ultar rock avalanche on April 9, 2018, in Karimabad, Hunza, Pakistan - Hasnain Gardezi; Aiguo Xing; Muhammad Bilal; Yu Zhuang; Shahmir Janjua (Landslides, 2023)

Removal of Toxic Metals from Water by Nanocomposites through Advanced Remediation Processes and Photocatalytic Oxidation - Ahmad Farhan; Misbah Zulfiqar; Samiah; Ehsan Ullah Rashid; Shahid Nawaz; Hafiz M.N. Iqbal; Teofil Jesionowski; Muhammad Bilal; Jakub Zdarta (Current Pollution Reports, 2023)
Purpose of Review Heavy and toxic metals are becoming more prevalent in the water sources of the globe, which has detrimental repercussions for both human health and the health of ecosystems. The summary of recent findings on treatment possibilities of toxic metal species by nanomaterials should facilitate the development of more advanced techniques of their removal. Recent Findings The high concentrations of chromium, mercury, and arsenic identified in wastewater cause a hazard to human health. There is a wide variety of nanoadsorbents and nanophotocatalysts used for heavy/hazardous metal removal. Recent research has resulted in the production of advanced nanostructures that exhibit extraordinary heavy/hazardous metal adsorption effectiveness and photocatalytic diminution of metal ions. These nanostructures have physically and chemically tunable features. Summary In this review article, the use of carbon-based nanomaterials, polymer-based nanomaterials, and semiconductor-based nanomaterials are extensively discussed to remove mercury, chromium, and arsenic ions from wastewater by the adsorption process. Advanced nanomaterials involved in photocatalytic reduction are also comprehensively discussed.

A novel three-band macroalgae detection index (TMI) for aquatic environments - Majid Nazeer; Mohammad M. M. Alsahli; Janet Elizabeth Nichol; Jiayi Pan; Weicheng Wu; Muhammad Bilal; Urooj Saeed (International Journal of Remote Sensing, 2023)

Cottonseed oil: A review of extraction techniques, physicochemical, functional, and nutritional properties - Tahreem Riaz; Muhammad Waheed Iqbal; Shahid Mahmood; Iqra Yasmin; Ali Ahmad Leghari; Abdur Rehman; Anam Mushtaq; Khubaib Ali; Muhammad Azam; Muhammad Bilal (Critical Reviews in Food Science and Nutrition, 2023)

Spinach-derived boron-doped g-C3N4/TiO2 composites for efficient photo-degradation of methylene blue dye - Sadia Faryad; Umair Azhar; Muhammad Bilal Tahir; Wahid Ali; Muhammad Arif; Muhammad Sagir (Chemosphere, 2023)

Deployment of oxidoreductases for sustainable biocatalytic degradation of selected endocrine-disrupting chemicals - Anil Kumar Singh; Muhammad Bilal; Teofil Jesionowski; Hafiz M.N. Iqbal (Sustainable Chemistry and Pharmacy, 2023)

Enzymatic cofactor regeneration systems: A new perspective on efficiency assessment - Karolina Bachosz; Jakub Zdarta; Muhammad Bilal; Anne S. Meyer; Teofil Jesionowski (Science of The Total Environment, 2023)

A discussion on PM2.5 exposure data used in the published paper by Anwar et al. (2021) - Muhammad Bilal; Gerrit de Leeuw; Janet E. Nichol; Max P. Bleiweiss; Alaa Mhawish; Leiku Yang; Huabin Chai; Md. Arfan Ali (Journal of Hazardous Materials, 2023)

Inorganic oxide systems as platforms for synergistic adsorption and enzymatic conversion of estrogens from aqueous solutions: Mechanism, stability and toxicity studies - Jakub Zdarta; Filip Ciesielczyk; Muhammad Bilal; Katarzyna Jankowska; Karolina Bachosz; Oliwia Degórska; Agnieszka Rybarczyk; Teofil Jesionowski; Anne S. Meyer (Journal of Environmental Chemical Engineering, 2023)

Precise geopressure predictions in active foreland basins: An application of deep feedforward neural networks - Muhammad Raiees Amjad; Muhammad Zafar; Muhammad Bilal Malik; Zohaib Naseer (Journal of Asian Earth Sciences, 2023)

Effect of water-in-oil and oil-in-water with Span 80 on coal flotation - Jixuan Gao; Zheng Tong; Xiangning Bu; Muhammad Bilal; Yue Hu; Chao Ni; Guangyuan Xie (Fuel, 2023)

Performance evaluation of phosphonium based deep eutectic solvents coated cerium oxide nanoparticles for CO2 capture - Tausif Ahmad; Jibran Iqbal; Mohamad Azmi Bustam; Muhammad Babar; Muhammad Bilal Tahir; Muhammad Sagir; Muhammad Irfan; Hafiz Muhammad Anwaar Asghar; Afaq Hassan; Asim Riaz; Lai Fatt Chuah; Awais Bokhari; et al. (Environmental Research, 2023)

Co-pyrolysis of sewage sludge and biomass for stabilizing heavy metals and reducing biochar toxicity: A review - Badr A. Mohamed; Roger Ruan; Muhammad Bilal; Nadeem A. Khan; Mukesh Kumar Awasthi; Mariam A. Amer; Lijian Leng; Mohamed A. Hamouda; Dai‑Viet Nguyen Vo; Jian Li (Environmental Chemistry Letters, 2023)
The huge amounts of sewage sludge produced by municipal wastewater treatment plants induce major environmental and economical issues, calling for advanced disposal methods. Traditional methods for sewage sludge disposal increase greenhouse gas emissions and pollution. Moreover, biochar created from sewage sludge often cannot be used directly in soil applications due to elevated levels of heavy metals and other toxic compounds, which alter soil biota and earthworms. This has limited the application of sewage sludge-derived biochar as a fertilizer. Here, we review biomass and sewage sludge co-pyrolysis with a focus on the stabilization of heavy metals and toxicity reduction of the sludge-derived biochar. We observed that co-pyrolyzing sewage sludge with biomass materials reduced heavy metal concentrations and decreased the environmental risk of sludge-derived biochar by up to 93%. Biochar produced from sewage sludge and biomass co-pyrolysis could enhance the reproduction stimulation of soil biota by 20‒98%. Heavy metals immobilization and transformation are controlled by the co-feed material mixing ratio, pyrolysis temperature, and pyrolysis atmosphere.

Investigation of PT 58 and PEG-6000-based finned heat sinks for thermal management of electronics - Radhi Abdullah Lawag; Hafiz Muhammad Ali; Md Hasan Zahir; Bilal A. Qureshi (Journal of Cleaner Production, 2023)

Impacts of earlier natural gas phase-out & heat-saving policies on district heating and the energy system - Muhammad Bilal Siddique; Per Sieverts Nielsen; Mathias Berg Rosendal; Ida Græsted Jensen; Dogan Keles (Energy Policy, 2023)

Remediation of Environmental Contaminants Through Phytotechnology - Abdul Latif; Aown Abbas; Javed Iqbal; Muhammad Azeem; Waleed Asghar; Rehmat Ullah; Muhammad Bilal; Muhammad Arsalan; Madeeha Khan; Rizwan Latif; Muhammad Ehsan; Asad Abbas; et al. (Water, Air, & Soil Pollution, 2023)

The Application of Chemometric Methods in the Production of Enzymes Through Solid State Fermentation Uses the Artificial Neural Network—a Review - Luiz Henrique Sales de Menezes; Adriana Bispo Pimentel; Polyany Cabral Oliveira; Iasnaia Maria de Carvalho Tavares; Héctor A. Ruiz; Murammad Irfan; Muhammad Bilal; Thiago Pereira das Chagas; Erik Galvão Paranhos da Silva; Luiz Carlos Salay; Julieta Rangel de Oliveira; Marcelo Franco (BioEnergy Research, 2023)

Manipulation of plant growth stimulants on plant morphology, phenology, and disease incident of Gossypium hirsutum L. under various thermal regimes - Muhammad Sarwar; Muhammad Farrukh Saleem; Basharat Ali; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Ashfaq Wahid; Muhammad Shahid; Theodore M. Mwamba; Bilal Ahmad Khan; Hamza Maqsood (Arabian Journal of Geosciences, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Research on sustainable development evaluation and improvement path of resource-based cities based on coupling of emergy and system dynamics - Haichao Ma; Qingsong Wang; Yujie Zhang; Muhammad Bilal Hussain; Yue Xu; Shu Tian; Xueliang Yuan; Qiao Ma; Renxiao Yuan; Yanshuang Jia (Environment, Development and Sustainability, 2023)

Determining the influencing factors of consumers’ attitude toward renewable energy adoption in developing countries: a roadmap toward environmental sustainability and green energy technologies - Mirza Huzaifa Asif; Tan Zhongfu; Azer Dilanchiev; Muhammad Irfan; Elchin Eyvazov; Bilal Ahmad (Environmental Science and Pollution Research, 2023)

Development of reusable chitosan-supported nickel sulfide microspheres for environmentally friendlier and efficient bio-sorptive decontamination of mercury toxicant - Yonghong Han; Juan Tao; Adnan Khan; Afrasiab Khan; Nisar Ali; Sumeet Malik; Chunhao Yu; Yong Yang; Teofil Jesionowski; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Assessing chemical hazard and unraveling binding affinity of priority pollutants to lignin modifying enzymes for environmental remediation - Anil Kumar Singh; Muhammad Bilal; Teofil Jesionowski; Hafiz M.N. Iqbal (Chemosphere, 2023)

Photocatalytic degradation and electrochemical energy storage properties of CuO/SnO2 nanocomposites via the wet-chemical method - Azam Khan; Inam Ullah; Afaq Ullah Khan; Bilal Ahmad; Khadijah Mohammedsaleh Katubi; Norah Salem Alsaiari; Muhammad Saleem; Mohd Zahid Ansari; Jianjun Liu (Chemosphere, 2023)

Cellulose/inorganic nanoparticles-based nano-biocomposite for abatement of water and wastewater pollutants - Zhen Zhang; Abdulrazaq Ibrahim Said Ahmed; Muhammad Zeeshan Malik; Nisar Ali; Adnan khan; Farman Ali; Mohamed Osman Hassan; Badr A. Mohamed; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Membrane-based nanoconfined heterogeneous catalysis for water purification: A critical review✰ - Quang Viet Ly; Lele Cui; Muhammad Bilal Asif; Waris Khan; Long D Nghiem; Yuhoon Hwang; Zhenghua Zhang (Water Research, 2023)

Unraveling the mutualistic interaction between endophytic Curvularia lunata CSL1 and tomato to mitigate cadmium (Cd) toxicity via transcriptomic insights - Sajjad Asaf; Rahmatullah Jan; Muhammad Aaqil Khan; Lubna; Abdul Latif Khan; Saleem Asif; Saqib Bilal; Waqar Ahmad; Muhammad Waqas; Kyung-Min Kim; Ahmed AL-Harrasi; In-Jung Lee (Science of The Total Environment, 2023)

Tricks and tracks in waste management with a special focus on municipal landfill leachate: Leads and obstacles - Swayansu Sabyasachi Mohanty; Shaili Vyas; Yamini Koul; Priya Prajapati; Sunita Varjani; Jo-Shu Chang; Muhammad Bilal; Konstantinos Moustakas; Pau Loke Show; Meththika Vithanage (Science of The Total Environment, 2023)

MOF-based membranes for oil/water separation: Status, challenges, and prospects - Mohammad Awwad; Muhammad Bilal; Muhammad Sajid; Muhammad Saqib Nawaz; Ihsanullah Ihsanullah (Journal of Environmental Chemical Engineering, 2023)

New outlook on hazardous pollutants in the wastewater environment: Occurrence, risk assessment and elimination by electrodeionization technologies - Gargi Mistry; Kartik Popat; Jimit Patel; Kashish Panchal; Huu Hao Ngo; Muhammad Bilal; Sunita Varjani (Environmental Research, 2023)

Relating green information acquisition, absorptive capacity, institutional pressure, and firm performance: an environmentally sustainable perspective - Naila Nureen; Da Liu; Bilal Ahmad; Muhammad Irfan (Environmental Science and Pollution Research, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Assessing eco-label knowledge and sustainable consumption behavior in energy sector of Pakistan: an environmental sustainability paradigm - Mirza Huzaifa Asif; Tan Zhongfu; Muhammad Irfan; Bilal Ahmad; Madad Ali (Environmental Science and Pollution Research, 2023)

The role of economic growth, information technologies, and globalization in achieving environmental quality: a novel framework for selected Asian countries - Hummera Saleem; Muhammad Bilal Khan; Seyed Mohammadreza Mahdavian (Environmental Science and Pollution Research, 2023)

Biodegradation mechanism of chlorpyrifos by halophilic bacterium Hortaea sp. B15 - Tony Hadibarata; Risky Ayu Kristanti; Muhammad Bilal; Murat Yilmaz; Palanivel Sathishkumar (Chemosphere, 2023)

Microbial fuel cell: A green eco-friendly agent for tannery wastewater treatment and simultaneous bioelectricity/power generation - Christina Saran; Diane Purchase; Ganesh Dattatraya Saratale; Rijuta Ganesh Saratale; Luiz Fernando Romanholo Ferreira; Muhammad Bilal; Hafiz M.N. Iqbal; Chaudhery Mustansar Hussain; Sikandar I. Mulla; Ram Naresh Bharagava (Chemosphere, 2023)

Biocatalytic degradation of reactive blue 221 and direct blue 297 dyes by horseradish peroxidase immobilized on iron oxide nanoparticles with improved kinetic and thermodynamic characteristics - Umme Kalsoom; Nasira Khalid; Affaf Ibrahim; Syed Salman Ashraf; Haq Nawaz Bhatti; Zainab Ahsan; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Genetically engineered microorganisms for environmental remediation - Hamza Rafeeq; Nadia Afsheen; Sadia Rafique; Arooj Arshad; Maham Intisar; Asim Hussain; Muhammad Bilal; Hafiz M.N. Iqbal (Chemosphere, 2023)

The effect of optimizing chemical fertilizers consumption structure to promote environmental protection, crop yield and reduce greenhouse gases emission in China - Shu Tian; Yue Xu; Qingsong Wang; Yujie Zhang; Xueliang Yuan; Qiao Ma; Xiufen Feng; Haichao Ma; Jixiang Liu; Chengqing Liu; Muhammad Bilal Hussain (Science of The Total Environment, 2023)

Spontaneous intra-electron transfer within rGO@Fe2O3-MnO catalyst promotes long-term NOx reduction at ambient conditions - Hafiz Muhammad Adeel Sharif; Muhammad Bilal Asif; Yuwei Wang; Ya-Nan Hou; Bo Yang; Xu Xiao; Changping Li (Journal of Hazardous Materials, 2023)

Development of zinc ferrite nanoparticles with enhanced photocatalytic performance for remediation of environmentally toxic pharmaceutical waste diclofenac sodium from wastewater - Shoomaila Latif; Amna Liaqat; Muhammad Imran; Ayesha Javaid; Nazim Hussain; Teofil Jesionowski; Muhammad Bilal (Environmental Research, 2023)

Efficacy of endophytic SB10 and glycine betaine duo in alleviating phytotoxic impact of combined heat and salinity in Glycine max L. via regulation of redox homeostasis and physiological and molecular responses - Saqib Bilal; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Ahmed Al-Harrasi; In-Jung Lee (Environmental Pollution, 2023)

Graphene-based nanoarchitectures as ideal supporting materials to develop multifunctional nanobiocatalytic systems for strengthening the biotechnology industry - Muhammad Bilal; Ehsan Ullah Rashid; Jakub Zdarta; Teofil Jesionowski (Chemical Engineering Journal, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

A population pharmacokinetic model of remdesivir and its major metabolites based on published mean values from healthy subjects - Ahmed Abouellil; Muhammad Bilal; Max Taubert; Uwe Fuhr (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Remdesivir is a direct-acting anti-viral agent. It was originally evaluated against filoviruses. However, during the COVID-19 pandemic, it was investigated due to its anti-viral activities against (SARS-CoV-2) virus. Therefore remdesivir received conditional approval for treatment of patients with severe coronavirus disease. Yet, its pharmacokinetic properties are inadequately understood. This report describes the population pharmacokinetics of remdesivir and its two plasma-detectable metabolites (GS-704277 and GS-441524) in healthy volunteers. The data was extracted from published phase I single escalating and multiple i.v remdesivir dose studies conducted by the manufacturer. The model was developed by standard methods using non-linear mixed effect modeling. Also, a series of simulations were carried out to test suggested clinical doses. The model describes the distribution of remdesivir and each of its metabolites by respective two compartments with sequential metabolism between moieties, and elimination from central compartments. As individual data were not available, only inter-cohort variability could be assessed. The estimated point estimates for central (and peripheral) volumes of distribution for remdesivir, GS-704277, and GS-441524 were 4.89 L (46.5 L), 96.4 L (8.64 L), and 26.2 L (66.2 L), respectively. The estimated elimination clearances of remdesivir, GS704277, and GS-441524 reached 18.1 L/h, 36.9 L/h, and 4.74 L/h, respectively. The developed model described the data well. Simulations of clinically approved doses showed that GS-441524 concentrations in plasma exceeded the reported EC 50 values during the complete duration of treatment. Nonetheless, further studies are needed to explore the pharmacokinetics of remdesivir and its relationship to clinical efficacy, and the present model may serve as a useful starting point for additional evaluations.

Natural remedies for Alzheimer’s disease: A systematic review of randomized controlled trials - Saara Ahmad; Saad Bilal Ahmed; Asra Khan; Muhammad Wasim; Saiqa Tabassum; Saida Haider; Fatima Ahmed; Zehra Batool; Saima Khaliq; Hamna Rafiq; Prashant Tikmani; Anwar-ul-Hassan Gilani (Metabolic Brain Disease, 2023)

Catastrophic air blasts triggered by large ice/rock avalanches - Yu Zhuang; Qiang Xu; Aiguo Xing; Muhammad Bilal; Kaushal Raj Gnyawali (Landslides, 2023)

Microplastics in water, sediments, and fish at Alpine River, originating from the Hindu Kush Mountain, Pakistan: implications for conservation - Muhammad Bilal; Abdul Qadir; Atif Yaqub; Habib Ul Hassan; Muhammad Irfan; Mehmood Aslam (Environmental Science and Pollution Research, 2023)

Discovering patterns in the topography of existing settlements: the case of the China-Pakistan Economic Corridor (CPEC) route - Ahsen Maqsoom; Bilal Aslam; Umer Khalil; Sheheryar Azam; Zaheer Abbas Kazmi; Muhammad Usman Arif Rana (Arabian Journal of Geosciences, 2023)

Metal–Organic Framework-Based Composites for the Detection and Monitoring of Pharmaceutical Compounds in Biological and Environmental Matrices - Muhammad Rizwan; Vidhya Selvanathan; Atta Rasool; Muhammad Anees ur Rehman Qureshi; Dure Najaf Iqbal; Qudsia Kanwal; Syed Salman Shafqat; Tahir Rasheed; Muhammad Bilal (Water, Air, & Soil Pollution, 2022)

In Silico Dissection and Expression Analysis of Sucrose Synthase Gene Family in Sugarcane - Muhammad Noman; Iqra Siddique; Bilal Saleem; Saiqa Ilyas; Shaukat Ali; Muhammad Ramzan Khan (Sugar Tech, 2022)

Genome wide association mapping of yield and various desirable agronomic traits in Rice - Muhammad Ashfaq; Abdul Rasheed; Muhammad Sajjad; Muhammad Ali; Bilal Rasool; Muhammad Arshad Javed; Sami Ul Allah; Shabnum Shaheen; Alia Anwar; Muhammad Shafiq Ahmad; Urooj Mubashar (Molecular Biology Reports, 2022)

Plant Growth Promoters Alleviate Oxidative Damages and Improve the Growth of Milk Thistle (Silybum marianum L.) Under Salinity Stress - Noreen Zahra; Abdul Wahid; Muhammad Bilal Hafeez; Kanval Shaukat; Sobia Shahzad; Tariq Shah; Mohammed Nasser Alyemeni (Journal of Plant Growth Regulation, 2022)

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Developments in advanced oxidation processes for removal of microplastics from aqueous matrices - Komal Rizwan; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Exploration of solid waste materials for sustainable manufacturing of cementitious composites - Hamayun Khan; Anwar Baig; Mahtab Faisal; Adnan Khan; Kashif Gul; Nauman Ali; Nisar Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Porous materials for the recovery of rare earth elements, platinum group metals, and other valuable metals: a review - Sidra Iftekhar; Golnaz Heidari; Neda Amanat; Ehsan Nazarzadeh Zare; Muhammad Bilal Asif; Mahnaz Hassanpour; Vesa Pekka Lehto; Mika Sillanpaa (Environmental Chemistry Letters, 2022)

Petrofacies and diagenesis of Thanetian Lockhart Limestone in the Upper Indus Basin (Pakistan): implications for the Ceno-Tethys Ocean - Ahmer Bilal; Renchao Yang; Aiping Fan; Muhammad Saleem Mughal; Yang Li; Muhammad Basharat; Muhammad Farooq (Carbonates and Evaporites, 2022)

Influencing factors of consumers’ buying intention of solar energy: a structural equation modeling approach - Mirza Huzaifa Asif; Tan Zhongfu; Bilal Ahmad; Muhammad Irfan; Asif Razzaq; Waqar Ameer (Environmental Science and Pollution Research, 2022)

Sedimentology and Diagenesis of the Early–Middle Eocene Carbonate Deposits of the Ceno-Tethys Ocean - Ahmer Bilal; Renchao Yang; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Muhammad Zaheer; George Kontakiotis (Journal of Marine Science and Engineering, 2022)
An integrated study based on field observation, petrography, and scanning electron microscopy (SEM) on the Early–Middle Eocene carbonate rocks has been carried out, which were deposited in the Ceno-Tethys Ocean. The study area of the Yadgaar Section lies on the eastern margin of the Upper Indus Basin, Pakistan. The Early–Middle Eocene Margalla Hill Limestone and Chorgali Formation act as reservoir rocks in other parts of the basin and are also present in the Yadgaar Section. The lack of comprehensive study in this area makes these reservoir rocks highly attractive for sedimentological evaluations and future exploration of hydrocarbons. The Early–Middle Eocene carbonate rocks are divided into nine microfacies: dolomicritic foraminiferal mudstone–wackestone microfacies (EMI); green algae dominated, mixed foraminiferal wackestone–packstone microfacies (EMII); ostracod, green algae and gypsum dominating mudstone–wackestone microfacies (EMIII); algae and mixed foraminiferal wackestone–packstone microfacies (EMIV); Nummulites dominating mudstone–wackestone microfacies (EMV); algal limestone mudstone microfacies (EMVI); Assilina bed wackestone–packstone microfacies (EMVII); micritized larger benthic foraminiferal wackestone–packstone microfacies (EMVIII); and algal limestone, mudstone microfacies (EMIX). The transgressive-regressive environment in the Ceno-Tethys Ocean leads to the deposition of these microfacies in the platform interior, open marine platform, platform edge, platform margin reef, toe of the slope apron, arid–humid platform interior, platform edge, open marine platform interior, and restricted marine platform interior, respectively. Initial post-depositional diagenetic stages are identified from the base to the top of the strata by their respective cement types, i.e., the base–lower middle part of the strata demonstrates an eogenetic sub-stage with the appearance of drusy cement, the middle section indicates a mesogenetic sub-stage by the appearance of blocky cement, while the top portion again reveals an eogenetic sub-stage of diagenesis by the presence of drusy and blocky types of cement. The ascending–descending hierarchy of cement generations is directly proportional to the grade of diagenesis from the base to the top of the carbonate strata. Variable diagenetic effects on the various microfacies also increase the secondary porosity range and enhance the reservoir characteristics of the Formations. The presence of foraminifera microfossils determined that these carbonate formations date from the Early–Middle Eocene.

Bentonite binding with mercury(II) ion through promotion of reactive oxygen species derived from manure-based dissolved organic matter - Saeed Rehman; Sayyaf Yousaf; Quanyun Ye; Liu Chenhui; Muhammad Bilal; Ahson Jabbar Shaikh; Muhammad Saqib Khan; Sohail Anjum Shahzad; Pingxiao Wu (Environmental Science and Pollution Research, 2022)

Analyzing the impact of organizational culture on social sustainability: a perspective of the construction industry - Muhammad Irfan; Wesam Salah Alaloul; Maria Ghufran; Ghulam Yaseen; Muhammad Jamaluddin Thaheem; Abdul Hannan Qureshi; Muhammad Bilal (Environment, Development and Sustainability, 2022)

Modeling the fecal contamination (fecal coliform bacteria) in transboundary waters using the scenario matrix approach: a case study of Sutlej River, Pakistan - Muhammad Shahid Iqbal; Majedul Islam; Mujtaba Hassan; Hazrat Bilal; Izaz Ali Shah; Tzoraki Ourania (Environmental Science and Pollution Research, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Economic policy uncertainty and environmental degradation: the moderating role of political stability - Umar Farooq; Seemab Gillani; Bilal Haider Subhani; Muhammad Nouman Shafiq (Environmental Science and Pollution Research, 2022)

Exploring thiazole-linked thioureas using alkaline phosphatase assay, biochemical evaluation, computational analysis and structure–activity relationship (SAR) studies - Sajid Ali Channar; Pervaiz Ali Channar; Aamer Saeed; Aisha A. Alsfouk; Syeda Abida Ejaz; Rabail Ujan; Razia Noor; Muhammad Sajjad Bilal; Qamar Abbas; Zahid Hussain; Bilal Ahmad Khan; Hussain Raza; et al. (Medicinal Chemistry Research, 2022)

Neurotoxic effects of environmental contaminants—measurements, mechanistic insight, and environmental relevance - Nadia Afsheen; Sadia Rafique; Hamza Rafeeq; Kanwal Irshad; Asim Hussain; Zille Huma; Vineet Kumar; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

SARS-COV-2/COVID-19: scenario, epidemiology, adaptive mutations, and environmental factors - Asma Asghar; Hafiz Muhammad Imran; Naheed Bano; Sadia Maalik; Sajida Mushtaq; Asim Hussain; Sunita Varjani; Lotfi Aleya; Hafiz M. N. Iqbal; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Response of sorghum and millet to poultry and farmyard manure–based biochar treatments - Muhammad Fraz Ali; Ummar Ali; Shahid Bilal; Usman Zulfiqar; Sidra Sohail; Tajamul Hussain (Arabian Journal of Geosciences, 2022)

Effects of yeast extract on the production of phenylpropanoid metabolites in callus culture of purple basil (Ocimum Basilicum L. var purpurascens) and their in-vitro evaluation for antioxidant potential - Gouhar Zaman; Umar Farooq; Muhammad Naeem Bajwa; Hasnain Jan; Muzamil Shah; Riaz Ahmad; Anisa Andleeb; Samantha Drouet; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

A comprehensive review of heavy metal pollution in the coastal areas of Bangladesh: abundance, bioaccumulation, health implications, and challenges - Md.Refat Jahan Rakib; Md. Asrafur Rahman; Amarachi Paschaline Onyena; Rakesh Kumar; Aniruddha Sarker; M. Belal Hossain; Abu Reza Md. Towfiqul Islam; Md. Saiful Islam; Md. Mostafizur Rahman; Yeasmin Nahar Jolly; Abubakr M. Idris; Mir Mohammad Ali; et al. (Environmental Science and Pollution Research, 2022)

Exploring the technical and behavioral dimensions of green supply chain management: a roadmap toward environmental sustainability - Naila Nureen; Da Liu; Bilal Ahmad; Muhammad Irfan (Environmental Science and Pollution Research, 2022)

Robust bioinspired surfaces and their exploitation for petroleum hydrocarbon remediation - Nisar Ali; Essoh Lionnelle Gyllye; Chuansong Duanmu; Yong Yang; Adnan Khan; Farman Ali; Muhammad Bilal; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Synergetic Efficacy of Amending Pb-Polluted Soil with P-Loaded Jujube (Ziziphus mauritiana) Twigs Biochar and Foliar Chitosan Application for Reducing Pb Distribution in Moringa Leaf Extract and Improving Its Anti-cancer Potential - Bilal Rasool; Mahmood-ur-Rahman; Muhammad Zubair; Muhammad Asaf Khan; Pia Muhammad Adnan Ramzani; Agnieszka Dradrach; Veysel Turan; Muhammad Iqbal; Shahbaz Ali Khan; Hafiz Muhammad Tauqeer; Muniba Farhad; Zaheer Abbas Virk; et al. (Water, Air, & Soil Pollution, 2022)

Effect of forage to concentrate ratio on growth performance and feeding behavior of Thalli lambs - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Karamo Jatta; Sajjad Khan; Muhammad Riaz; Qamar Bilal; Urooj Anwar; Sibtain Ahmad; Hassan Munir Bajwa; Fahd Rasul (Tropical Animal Health and Production, 2022)

Xylitol Production from Sugarcane Bagasse Through Ultrasound-Assisted Alkaline Pretreatment and Enzymatic Hydrolysis Followed by Fermentation - Sabitri Siris Thapa; Smriti Shrestha; Muhammad Bilal Sadiq; Anil Kumar Anal (Sugar Tech, 2022)

The role of green growth, green financing, and eco-friendly technology in achieving environmental quality: evidence from selected Asian economies - Hummera Saleem; Muhammad Bilal Khan; Seyed Mohammadreza Mahdavian (Environmental Science and Pollution Research, 2022)

Nanotechnology-based controlled release of sustainable fertilizers. A review - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Umer Shahzad Malik; Mohammad Daud Khan; Juliana Heloisa Pinê Américo-Pinheiro; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)
The rising population is increasing food demand, yet actual crop production is limited by the poor efficiency of classical fertilizers. In particular, only about 40–60% of fertilizer nitrogen, 15–20% of phosphorus and 50–60% of potassium are used by crop plants, the rest ending polluting the environment. Nanofertilizers are promising alternatives. Here, we review plant nutrients, synthesis of zinc oxide nanoparticles, encapsulation of nanoparticles in fertilizers, and effect on plants.

Hazardous wastes, adverse impacts, and management strategies: a way forward to environmental sustainability - Guoqing Qian; Chuansong Duanmu; Nisar Ali; Adnan Khan; Sumeet Malik; Yong Yang; Muhammad Bilal (Environment, Development and Sustainability, 2022)

Novel strategies and advancement in reducing heavy metals from the contaminated environment - Quratulain Maqsood; Nazim Hussain; Mehvish Mumtaz; Muhammad Bilal; Hafiz M. N. Iqbal (Archives of Microbiology, 2022)

Lethal and sublethal effects of flonicamid (50 WG) and spirotetramat (240 SC) on Bemisia tabaci (Homoptera: Aleyrodidae): an age-stage two sex life table study - Aqsa Abbas; Javaid Iqbal; Ali Zeshan; Qurban Ali; Imran Nadeem; Humaira Malik; Tamsila Nazir; Muhammad Faheem Akhter; Bilal Bin Iqbal (Phytoparasitica, 2022)

Triggering mechanisms of Gayari avalanche, Pakistan - Bilal Saif; Mohammad Tahir; Amir Sultan; Muhammad Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah; Samia Gurmani (Natural Hazards, 2022)

A pilot study for enhanced transformation of a metabolite 3,5-dichloroaniline derived from dicarboximide fungicides through immobilized laccase mediator system - Aniruddha Sarker; Tofazzal Islam; Muhammad Bilal; Jang-Eok Kim (Environmental Science and Pollution Research, 2022)

Integrated application of plant bioregulator and micronutrients improves crop physiology, productivity and grain biofortification of delayed sown wheat - Naeem Ahmad; Ahmad Latif Virk; Sadam Hussain; Muhammad Bilal Hafeez; Fasih Ullah Haider; Muhammad Ishaq Asif Rehmani; Tauqeer Ahmad Yasir; Ariba Asif (Environmental Science and Pollution Research, 2022)

Nexus between non-renewable energy production, CO2 emissions, and healthcare spending in OECD economies - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir; Ghulam Yahya Khan; Muhammad Usman (Environmental Science and Pollution Research, 2022)

Decolorization of various dyes by microorganisms and green-synthesized nanoparticles: current and future perspective - Azharuddin B. Daphedar; Siddappa Kakkalameli; Basheerabegum Faniband; Muhammad Bilal; Ram Naresh Bhargava; Luiz Fernando Romanholo Ferreira; Abbas Rahdar; Dummi Mahadevan Gurumurthy; Sikandar I. Mulla (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2022)

Insight into soil nitrogen and phosphorus availability and agricultural sustainability by plant growth-promoting rhizobacteria - Qingwei Zeng; Xiaolei Ding; Jiangchuan Wang; Xuejiao Han; Hafiz M. N. Iqbal; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Gums-based engineered bio-nanostructures for greening the 21st-century biotechnological settings - Muhammad Bilal; Hira Munir; Muhammad Imran Khan; Mohsin Khurshid; Tahir Rasheed; Komal Rizwan; Marcelo Franco; Hafiz M. N. Iqbal (Critical Reviews in Food Science and Nutrition, 2022)

Emergence of stochastic resonance in a two-compartment hippocampal pyramidal neuron model - Muhammad Bilal Ghori; Yanmei Kang; Yaqian Chen (Journal of Computational Neuroscience, 2022)

Mechanisms of gene regulation by histone degradation in adaptation of yeast: an overview of recent advances - Safir Ullah Khan; Munir Ullah Khan; Fadia Kalsoom; Muhammad Imran Khan; Shuang Gao; Ahsanullah Unar; Muhammad Zubair; Muhammad Bilal (Archives of Microbiology, 2022)

Industrialization progress of lignocellulosic ethanol - Liangliang Wang; Muhammad Bilal; Congping Tan; Xirui Jiang; Fangfang Li (Systems Microbiology and Biomanufacturing, 2022)

Nerolidol: a potential approach in rheumatoid arthritis through reduction of TNF-α, IL-1β, IL-6, NF-kB, COX-2 and antioxidant effect in CFA-induced arthritic model - Shanila Akhter; Hafiz Muhammad Irfan; Alamgeer; Shah Jahan; Muhammad Shahzad; Muhammad Bilal Latif (Inflammopharmacology, 2022)

Insights to antimicrobial resistance: heavy metals can inhibit antibiotic resistance in bacteria isolated from wastewater - Massab Bashir Khaira; Muhammad Bilal Yusuf; Fariha Khan (Environmental Monitoring and Assessment, 2022)

Construction of Adipogenic ceRNA Network Based on lncRNA Expression Profile of Adipogenic Differentiation of Human MSC Cells - Chengcheng Liang; Sayed Haidar Abbas Raza; Muhammad Abuzar Raza Naqvi; Yanrong Feng; Rajwali Khan; Zuhair M. Mohammedsaleh; Abdullah F. Shater; Bassam M. Al-ahmadi; Fayez M. Saleh; Muhammad Ahsan Bilal; Linsen Zan (Biochemical Genetics, 2022)

Purification and functional characterization of lectin from Chenopodium album - Mahwish Javed; Muhammad Bilal; Bushra Tabassum; Arif Malik; Olawale Samuel Adeyinka; Muhammad Tariq; Idrees Ahmad Nasir (Journal of Proteins and Proteomics, 2022)

A review on sources of heavy metals, their toxicity and removal technique using physico-chemical processes from wastewater - Muhammad Rafique; Syeda Hajra; Muhammad Bilal Tahir; Syed Sajid Ali Gillani; Muneeb Irshad (Environmental Science and Pollution Research, 2022)

Preliminary investigation and dynamic analysis of a multiphase ice-rock avalanche on July 5, 2021, in the upper Naltar valley, Gilgit, Pakistan - Hasnain Gardezi; Aiguo Xing; Muhammad Bilal; Yu Zhuang; Shoaib Muhammad; Shahmir Janjua (Landslides, 2022)

Understanding the role of atmospheric circulations and dispersion of air pollution associated with extreme smog events over South Asian megacity - Muhammad Bilal; Mujtaba Hassan; Danyal Bin Taufiq Tahir; Muhammad Shahid Iqbal; Imran Shahid (Environmental Monitoring and Assessment, 2022)

Nano-structured dynamic Schiff base cues as robust self-healing polymers for biomedical and tissue engineering applications: a review - Umer Shahzad Malik; Muhammad Bilal Khan Niazi; Zaib Jahan; Mazhar Iqbal Zafar; Dai-Viet N. Vo; Farooq Sher (Environmental Chemistry Letters, 2022)
Polymer materials are vulnerable to damages, failures, and degradations, making them economically unreliable. Self-healing polymers, on the other hand, are multifunctional materials with superior properties of autonomic recovery from physical damages. These materials are suitable for biomedical and tissue engineering in terms of cost and durability. Schiff base linkages-based polymer materials are one of the robust techniques owing to their simple self-healing mechanism. These are dynamic reversible covalent bonds, easy to fabricate at mild conditions, and can self-reintegrate after network disruption at physiological conditions making them distinguished. Here we review self-healing polymer materials based on Schiff base bonds. We discuss the Schiff base bond formation between polymeric networks, which explains the self-healing phenomenon. These bonds have induced 100% recovery in optimal cases.

Effects of convective available potential energy, temperature and humidity on the variability of thunderstorm frequency over Bangladesh - Md Wahiduzzaman; Md. Arfan Ali; Jing-Jia Luo; Yu Wang; Md. Jalal Uddin; Shamsuddin Shahid; A. R. M. Towfiqul Islam; Sanjit Kumar Mondal; Ubaydur Rahaman Siddiki; Muhammad Bilal; Zhongfeng Qiu; Ramzah Dambul; et al. (Theoretical and Applied Climatology, 2022)

Dendritic Cell–Targeted Therapies to Treat Neurological Disorders - Asim Hussain; Hamza Rafeeq; Nimra Munir; Zara Jabeen; Nadia Afsheen; Khalil ur Rehman; Muhammad Bilal; Hafiz M. N. Iqbal (Molecular Neurobiology, 2022)

Separation and remediation of environmental pollutants using metal–organic framework-based tailored materials - Walter Dzumbira; Nisar Ali; Chuansong Duanmu; Yong Yang; Adnan Khan; Farman Ali; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Heavy metals contamination and associated health risks in food webs—a review focuses on food safety and environmental sustainability in Bangladesh - Aniruddha Sarker; Jang-Eok Kim; Abu Reza Md. Towfiqul Islam; Muhammad Bilal; Md. Refat Jahan Rakib; Rakhi Nandi; Mohammed M. Rahman; Tofazzal Islam (Environmental Science and Pollution Research, 2022)

Synthesis and evaluation of Ca-doped ferrihydrite as a novel adsorbent for the efficient removal of fluoride - Khalil Ahmad; Izaz Ali Shah; Sharafat Ali; Muhammad Tariq Khan; Muhammad Bilal Ahmed Qureshi; Syed Hassan Ali Shah; Asmat Ali; Wajid Rashid; Hifza Nayab Gul (Environmental Science and Pollution Research, 2022)

Do neonicotinoids better than pyrethroids for Coccinella septempunctata L. (Coleoptera: Coccinellidae)? A comparative sub-lethal indirect age-stage, two-sex life tables laboratory bioassay - Muhammad Rizwan; Bilal Atta; Misbah Rizwan; Ijaz Ashraf; Muhammad Arshad; Muhammad Tahir; Mudassir Ali; Arshed Makhdoom Sabir; Muhammad Bilal; Muhammad Yasir Ali (International Journal of Tropical Insect Science, 2021)

Does digitalization matter in green preferences in nexus of output volatility and environmental quality? - Carlos Samuel Ramos-Meza; Rinat Zhanbayev; Hazrat Bilal; Mubbashra Sultan; Zehra Betül Pekergin; Hafiz Muhammad Arslan (Environmental Science and Pollution Research, 2021)

Economic viability of solar energy export from the Middle East and North Africa to Europe and South Asia - Muhammad Zubair; Ahmed Bilal Awan (Environment, Development and Sustainability, 2021)

Bio-purification of sugar industry wastewater and production of high-value industrial products with a zero-waste concept - Muhammad Zohaib Nawaz; Muhammad Bilal; Arslan Tariq; Hafiz M. N. Iqbal; Huda Ahmed Alghamdi; Hairong Cheng (Critical Reviews in Food Science and Nutrition, 2021)

Integrated support vector regressor and hybrid neural network techniques for earthquake prediction along Chaman fault, Baluchistan - Umer Khalil; Bilal Aslam; Zaheer Abbas Kazmi; Ahsen Maqsoom; Muhammad Irshad Qureshi; Sheheryar Azam; Ahsan Nawaz (Arabian Journal of Geosciences, 2021)

Ecotoxicological Assessment and Environmental Risk of the Insecticide Chlorpyrifos for Aquatic Neotropical Indicators - Márjori Brenda Leite Marques; Isabella Alves Brunetti; Camila Aparecida Faleiros; Claudinei da Cruz; Hafiz M. N. Iqbal; Muhammad Bilal; Juliana Heloisa Pinê Américo-Pinheiro (Water, Air, & Soil Pollution, 2021)

Convective available potential energy (CAPE) in Pakistan and its association with precipitation and temperature - Sameen Malik; Rehan Ahmed; Muhammad Latif; Muhammad Azam; Ehsan Haroon; Muhammad Bilal Iqbal (Theoretical and Applied Climatology, 2021)

Revisiting the Role of Biologically Active Natural and Synthetic Compounds as an Intervention to Treat Injured Nerves - Natália Melo Souza; Mateus Figueiredo Gonçalves; Luiz Fernando Romanholo Ferreira; Muhammad Bilal; Hafiz M. N. Iqbal; Renato Nery Soriano (Molecular Neurobiology, 2021)

SNPs at 3′UTR of APOL1 and miR-6741-3p target sites associated with kidney diseases more susceptible to SARS-COV-2 infection: in silco and in vitro studies - Muhammad Safdar; Muhammad Sajjad Khan; Abdulkarim Yasin Karim; Shwan Ali Omar; Shukur Wasman Smail; Muhammad Saeed; Sana Zaheer; Mazhar Ali; Bilal Ahmad; Muhammad Tasleem; Yasmeen Junejo (Mammalian Genome, 2021)

Copper Nanoparticles as Growth Promoter, Antioxidant and Anti-Bacterial Agents in Poultry Nutrition: Prospects and Future Implications - Muhammad Sharif; Muhammad Aziz-ur Rahman; Bilal Ahmed; Rao Zahid Abbas; Faiz-ul Hassan (Biological Trace Element Research, 2021)

Knowledge, attitude, and practices associated with brucellosis among livestock owners and its public health impact in Punjab, Pakistan - Sabir Hussain; Abrar Hussain; Ubaid-ur-Rehman Zia; Syed Musa Raza Naqvi; Muhammad Yasir Zahoor; Muhammad Bilal; Jeffery HO; Olivier A. E. Sparagano (Biologia, 2021)

Comprehensive evaluation of machine learning models for suspended sediment load inflow prediction in a reservoir - Muhammad Bilal Idrees; Muhammad Jehanzaib; Dongkyun Kim; Tae-Woong Kim (Stochastic Environmental Research and Risk Assessment, 2021)

Nanotechnology-based immunotherapies to combat cancer metastasis - Yuping Zhao; Muhammad Bilal; Maimoona Qindeel; Muhammad Imran Khan; Kuldeep Dhama; Hafiz M. N. Iqbal (Molecular Biology Reports, 2021)

Sulfate-Based Fertilizers Regulate Nutrient Uptake, Photosynthetic Gas Exchange, and Enzymatic Antioxidants to Increase Sunflower Growth and Yield Under Drought Stress - Bilal Ahamid Shafiq; Fahim Nawaz; Sadia Majeed; Muhammad Aurangzaib; Abdullah Al Mamun; Muhammad Ahsan; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muqarrab Ali; Sarfraz Hashim; Tanveer ul Haq (Journal of Soil Science and Plant Nutrition, 2021)
The challenging impact of drought to agricultural productivity requires the adoption of mitigation strategies with a better understanding of underlying mechanisms responsible for drought tolerance. The present study aimed at investigating the effects of sulfur-based fertilizers on mitigation of drought stress in sunflower. Sulfate-containing fertilizers, viz., ammonium sulfate, zinc sulfate, magnesium sulfate, potassium sulfate, and gypsum, were initially evaluated at two different rates (10 and 20 mg kg −1 soil equivalent to 20 and 40 kg ha −1 , respectively) for nutrient uptake and growth-promoting traits in sunflower seedlings (cv. Hysun-33). The best performing fertilizer (gypsum) was then selected to evaluate the response of sunflower under drought stress imposed at flowering stage for three weeks (25–30% water holding capacity). Results indicated significant amelioration of drought stress with higher activity of photosynthetic apparatus, upregulation of antioxidative enzymes, and increased achene yield by gypsum application. In comparison to control, gypsum-treated plants (20 mg kg −1 soil) exhibited higher water status (32%), leaf photosynthetic rate (29%), transpiration rate (67%), and stomatal conductance (118%) under drought stress. The antioxidant enzyme activities of catalase, guaiacol peroxidase, and superoxide dismutase were also increased by 67%, 62%, and 126%, respectively, resulting in higher achene yield (19%) under water-deficit conditions. This study indicates that the application of sulfur-based fertilizers (gypsum) can be used to induce drought tolerance and obtain high sunflower yields under drought stress, and furthermore, it is a cost-effective strategy resulting in high benefit–cost ratio with respect to no gypsum application.

Deciphering the impact of novel coronavirus pandemic on agricultural sustainability, food security, and socio-economic sectors—a review - Mehvish Mumtaz; Nazim Hussain; Zulqarnain Baqar; Saima Anwar; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Assessing the physico-chemical parameters and some metals of underground water and associated soil in the arid and semiarid regions of Tank District, Khyber Pakhtunkhwa, Pakistan - Asif Khan; Muhammad Naeem; Muhammad Bilal; Abbas Khan; Fazle Subhan; Muhammad Ikram; Muhammad Ishaq Ali Shah; Saleem Ullah; Asmat Ullah; Atta Ullah (Environmental Monitoring and Assessment, 2021)

Investigation of Characteristics of Long Runout Landslides Based on the Multi-source Data Collaboration: A Case Study of the Shuicheng Basalt Landslide in Guizhou, China - Yu Zhuang; Aiguo Xing; Yangyang Leng; Muhammad Bilal; Yanbo Zhang; Kaiping Jin; Junyi He (Rock Mechanics and Rock Engineering, 2021)

Asymmetric macroeconomic determinants of CO2 emission in China and policy approaches - Bilal Aslam; Jinsong Hu; Muhammad Tariq Majeed; Zubaria Andlib; Sana Ullah (Environmental Science and Pollution Research, 2021)

Synergistic Effect of Urease and Nitrification Inhibitors in the Reduction of Ammonia Volatilization - Asim Hussain; Nazish Jahan; Zara Jabeen; Khalil Ur Rehman; Hamza Rafeeq; Muhammad Bilal; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2021)

Seasonal Dynamics of Microbial Contamination and Antibiotic Resistance in the Water at the Tietê Ecological Park, Brazil - Darlan Storto; Luana Barbosa Carvalho Nara; Dora Inés Kozusny-Andreani; Luiz Sergio Vanzela; Cleber Fernando Menegasso Mansano; Muhammad Bilal; Hafiz M. N. Iqbal; Juliana Heloisa Pinê Américo-Pinheiro (Water, Air, & Soil Pollution, 2021)

Exploring genetic diversity and population structure of Punjab goat breeds using Illumina 50 K SNP bead chip - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ghulam Bilal; Hafiz Muhammad Waheed; Muhammad Sajjad Khan; Muhammad Javaid Asad; Zulfiqar Hussain Kuthu (Tropical Animal Health and Production, 2021)

Environmental quality, climate indicators, and COVID-19 pandemic: insights from top 10 most affected states of the USA - Bilal; Muhammad Farhan Bashir; Khurram Shahzad; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan; Tehreem Fatima; Umar Numan (Environmental Science and Pollution Research, 2021)

Expression profiling of miRNA-196a biomarker in naïve hepatitis C virus-infected and Sofosbuvir plus Daclatasvir-treated patients - Nazim Hussain; Nimrah Farooq; Muhammad Maqsood; Muhammad Shahid Riaz Rajoka; Muhammad Bilal (Archives of Microbiology, 2021)

Heat shock protein gene identified from Agave sisalana (AsHSP70) confers heat stress tolerance in transgenic cotton (Gossypium hirsutum) - Anicet Agossa Batcho; Muhammad Bilal Sarwar; Bushra Rashid; Sameera Hassan; Tayyab Husnain (Theoretical and Experimental Plant Physiology, 2021)

Assessment of pathogenicity of Beauveria bassiana, Metarhizium anisopliae, Verticillium lecanii and Bacillus thuringiensis var. kurstaki against Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) via diet-bioassay technique under controlled conditions - Mubashar Iqbal; Muhammad Dildar Gogi; Bilal Atta; Muhammad Junaid Nisar; Muhammad Jalal Arif; Nazir Javed (International Journal of Tropical Insect Science, 2021)

Effect of co-application of wastewater and freshwater on the physiological properties and trace element content in Raphanus sativus: soil contamination and human health - Natasha; Muhammad Shahid; Aneeza Sardar; Hasnain Anwar; Sana Khalid; Sajid Hussain Shah; Ali Haidar Shah; Muhammad Bilal (Environmental Geochemistry and Health, 2021)

Late Cretaceous pelagic laminites at the northwestern margin of Indian plate, Pakistan: implications for basin bathymetry and ophiolite emplacement - Sajjad Ahmad; Suleman Khan; Bilal Wadood; Asad Naseer; Muhammad Noman; Jamal Wadood; Muhammad Muslim (Carbonates and Evaporites, 2021)

Various strategies applied for the removal of emerging micropollutant sulfamethazine: a systematic review - Sikandar I. Mulla; Zabin K. Bagewadi; Basheerabegum Faniband; Muhammad Bilal; Jong-Chan Chae; Paul Olusegun Bankole; Ganesh Dattatraya Saratale; Ram Naresh Bhargava; Dummi Mahadevan Gurumurthy (Environmental Science and Pollution Research, 2021)

Synergistic influence of CuO nanoparticles and spectral lights transforms biomass, antioxidative response, and antioxidants in Brassica nigra - Muhammad Zia; Hira Zafar; Faiza Zarrin Gul; Bilal Haider Abbasi; Zarrin Fatima Rizvi; Abdul Mannan (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

A comparative analysis of attabad landslide on january 4, 2010, using two numerical models - Hasnain Gardezi; Muhammad Bilal; Qiangong Cheng; Aiguo Xing; Yu Zhuang; Tahir Masood (Natural Hazards, 2021)

Elucidation of larvicidal potential of metallic and environment friendly food-grade nanostructures against Aedes albopictus - Toqeer Ahmed; Irfan Liaqat; Muhammad Zeeshan Hyder; Shaheen Akhtar; Assad Hafeez Bhatti; Shahid Bilal Butt; Zahid Imran; Tayyaba Yasmin; Shabbar Abbas (Environmental Geochemistry and Health, 2021)

A feasibility study on microwave imaging of bone for osteoporosis monitoring - Bilal Amin; Atif Shahzad; Lorenzo Crocco; Mengchu Wang; Martin O’Halloran; Ana González-Suárez; Muhammad Adnan Elahi (Medical & Biological Engineering & Computing, 2021)

Scientific data-driven evaluation of academic publications on environmental Kuznets curve - Muhammad Farhan Bashir; Benjiang Ma; Muhammad Adnan Bashir; Bilal; Luqman Shahzad (Environmental Science and Pollution Research, 2021)

Analysis of environmental taxes publications: a bibliometric and systematic literature review - Muhammad Farhan Bashir; Benjiang MA; Bilal; Bushra Komal; Muhammad Adnan Bashir (Environmental Science and Pollution Research, 2021)

Heat stress in cultivated plants: nature, impact, mechanisms, and mitigation strategies—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Lorenzo Barbanti; Muhammad Aamer; Muhammad Mehmood Iqbal; Muhammad Nawaz; Athar Mahmood; Abid Ali; Muhammad Talha Aslam (Plant Biosystems, 2021)

Appraisal of One Health approach amid COVID-19 and zoonotic pandemics: insights for policy decision - Muhammad Imran Arshad; Hilal Ahmad Khan; Bilal Aslam; Junaid Ali Khan (Tropical Animal Health and Production, 2021)

Depositional, diagenetic, and sequence stratigraphic constrains on reservoir characterization: a case study of middle Jurassic Samana Suk Formation, western Salt Range, Pakistan - Bilal Wadood; Mansoor Aziz; Junaid Ali; Nasar Khan; Jamal Wadood; Ahmad Khan; Muhammad Shafiq; Mohib Ullah (Journal of Sedimentary Environments, 2021)

Lethal and sublethal effects of clothianidin, imidacloprid and sulfoxaflor on the wheat aphid, Schizaphis graminum (Hemiptera: Aphididae) and its coccinellid predator, Coccinella septempunctata - Bilal Atta; Muhammad Rizwan; Arshed Makhdoom Sabir; Muhammad Dildar Gogi; Muhammad Asif Farooq; Abdullah Jamal (International Journal of Tropical Insect Science, 2021)

Yarrowia lipolytica as an emerging biotechnological chassis for functional sugars biosynthesis - Muhammad Bilal; Shuo Xu; Hafiz M. N. Iqbal; Hairong Cheng (Critical Reviews in Food Science and Nutrition, 2021)

Gas Adsorption and Controlling Factors of Shale: Review, Application, Comparison and Challenges - Asadullah Memon; Aifen Li; Bilal Shams Memon; Temoor Muther; Wencheng Han; Muhammad Kashif; Muhammad Usman Tahir; Imran Akbar (Natural Resources Research, 2021)

Photocatalytic degradation of crystal violet dye under sunlight by chitosan-encapsulated ternary metal selenide microspheres - Waqar Ahmad; Adnan Khan; Nisar Ali; Sana Khan; Salah Uddin; Sumeet Malik; Nauman Ali; Hamayun Khan; Hammad Khan; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Chemiluminescent-microparticle-immunoassay-based detection and prevalence of human immunodeficiency virus infection in Islamabad, Pakistan - Misbahud Din; Faheem Anwar; Muhammad Ali; Muhammad Yousaf; Bilal Ahmad; Abdullah (Archives of Virology, 2021)

Streamflow Variations in Monthly, Seasonal, Annual and Extreme Values Using Mann-Kendall, Spearmen’s Rho and Innovative Trend Analysis - Muhammad S. Ashraf; Ijaz Ahmad; Noor M. Khan; Fan Zhang; Ahmed Bilal; Jiali Guo (Water Resources Management, 2021)

Nexus between willingness to pay for renewable energy sources: evidence from Turkey - Iftikhar Muhammad; Malik Shahzad Shabbir; Sharjeel Saleem; Kanwal Bilal; Recep Ulucak (Environmental Science and Pollution Research, 2021)

Assessment of Drinking Water Sources for Water Quality, Human Health Risks, and Pollution Sources: A Case Study of the District Bajaur, Pakistan - Muhammad Haya Khan; Mohammad Nafees; Nisar Muhammad; Ubaid Ullah; Rahib Hussain; Muhammad Bilal (Archives of Environmental Contamination and Toxicology, 2021)

The sedimentological and stratigraphical analysis of the Paleocene to Early Eocene Dungan Formation, Kirthar Fold and Thrust Belt, Pakistan: implications for reservoir potential - Sajjad Ahmad; Bilal Wadood; Suleman Khan; Abd Ullah; Ghazi Mustafa; Muhammad Hanif; Hasbee Ullah (Journal of Sedimentary Environments, 2020)

Dechlorane Plus as an emerging environmental pollutant in Asia: a review - Mazhar Iqbal Zafar; Sundas Kali; Mehtabidah Ali; Muhammad Asam Riaz; Tayyaba Naz; Muhammad Mazhar Iqbal; Noshin Masood; Kashif Munawar; Bilal Jan; Sohail Ahmed; Amir Waseem; Muhammad Bilal Khan Niazi (Environmental Science and Pollution Research, 2020)

Over expression of a Chitinase 2 gene from Chinese Wild Strawberry improves resistance to anthracnose disease in transgenic Arabidopsis thaliana - Zhifeng Wen; Jinhui Bai; Lin Wang; Liping Yao; Bilal Ahmad; Muhammad Hanif; Qingxi Chen (Plant Biotechnology Reports, 2020)

Simplex-Centroid Design and Artificial Neural Network-Genetic Algorithm for the Optimization of Exoglucanase Production by Penicillium Roqueforti ATCC 10110 Through Solid-State Fermentation Using a Blend of Agroindustrial Wastes - Nájila da Silva Nunes; Lucas Lima Carneiro; Luiz Henrique Sales de Menezes; Marise Silva de Carvalho; Adriana Bispo Pimentel; Tatielle Pereira Silva; Clissiane Soares Viana Pacheco; Iasnaia Maria de Carvalho Tavares; Pedro Henrique Santos; Thiago Pereira das Chagas; Erik Galvão Paranhos da Silva; Julieta Rangel de Oliveira; et al. (BioEnergy Research, 2020)

Influence of metallic species for efficient photocatalytic water disinfection: bactericidal mechanism of in vitro results using docking simulation - Aaima Iftikhar; Muhammad Saqib Khan; Umer Rashid; Qaisar Mahmood; Habiba Zafar; Muhammad Bilal; Nadia Riaz (Environmental Science and Pollution Research, 2020)

Environmental pollution and COVID-19 outbreak: insights from Germany - Bilal; Muhammad Farhan Bashir; Maroua Benghoul; Umar Numan; Awais Shakoor; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan (Air Quality, Atmosphere & Health, 2020)

Advances in photo-catalysis approach for the removal of toxic personal care product in aqueous environment - Muhammad Bilal Tahir; Anam Ahmad; Tahir Iqbal; Mohsin Ijaz; Shabbir Muhammad; Saifeldin M. Siddeeg (Environment, Development and Sustainability, 2020)

Current findings on carp edema virus, control challenges, and future outlook - Tayyab Rehman; Lizi Yin; Muhammad Bilal Latif; Yaojia Zhou; Kaiyu Wang; Yi Geng; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Hongrui Guo; Weiming Lai; et al. (Aquaculture International, 2020)

Future Vision for Autonomous Ocean Observations - Christopher Whitt; Jay Pearlman; Brian Polagye; Frank Caimi; Frank Muller-Karger; Andrea Copping; Heather Spence; Shyam Madhusudhana; William Kirkwood; Ludovic Grosjean; Bilal Muhammad Fiaz; Satinder Singh; et al. (Frontiers in Marine Science, 2020)

Investigation and dynamic analyses of rockslide-induced debris avalanche in Shuicheng, Guizhou, China - Yanbo Zhang; Aiguo Xing; Kaiping Jin; Yu Zhuang; Muhammad Bilal; Shimin Xu; Yaoqiang Zhu (Landslides, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

Growth, Biomass Production, and Yield Potential of Quinoa (Chenopodium quinoa Willd.) as Affected by Planting Techniques Under Irrigated Conditions - Saif Ali; Muhammad Umer Chattha; Muhammad Umair Hassan; Imran Khan; Muhammad Bilal Chattha; Babar Iqbal; Muzammal Rehman; Muhammad Nawaz; Muhammad Zubair Amin (International Journal of Plant Production, 2020)

Environmental impacts and risk factors of renewable energy paradigm—a review - Muhammad Shahzad Nazir; Ziad M. Ali; Muhammad Bilal; Hafiz M. Sohail; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2020)

Environmental degradation, economic growth, and energy innovation: evidence from European countries - Muhammad Ali; Syed Ali Raza; Bilal Khamis (Environmental Science and Pollution Research, 2020)

State-of-the-art strategies and applied perspectives of enzyme biocatalysis in food sector — current status and future trends - Muhammad Bilal; Hafiz M. N. Iqbal (Critical Reviews in Food Science and Nutrition, 2020)

Light-mediated biosynthesis of phenylpropanoid metabolites and antioxidant potential in callus cultures of purple basil (Ocimum basilicum L. var purpurascens) - Munazza Nazir; Muhammad Asad Ullah; Muhammad Younas; Aisha Siddiquah; Muzamil Shah; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Phenolic Profile and Thermal Stability of Monovarietal Extra Virgin Olive Oils Based on Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Azhar Iqbal; Babar Manzoor Atta; Rahat Ullah; Muhammad Bilal Khan (Journal of Fluorescence, 2020)

Application of Fluorescence Spectroscopy in Wheat Crop: Early Disease Detection and Associated Molecular Changes - Babar Manzoor Atta; Muhammad Saleem; Hina Ali; Muhammad Bilal; Muhammad Fayyaz (Journal of Fluorescence, 2020)

Remote sensing of water turbidity in the Eastern China Seas from Geostationary Ocean Colour Imager - Shengqiang Wang; Ying Mao; Lufei Zheng; Zhongfeng Qiu; Muhammad Bilal; Deyong Sun (International Journal of Remote Sensing, 2020)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

In-vitro evaluation of antimicrobial, antioxidant, alpha-amylase inhibition and cytotoxicity properties of Cannabis sativa - Syed Bilal Shah; Lubna Sartaj; Shahid Hussain; Nabi Ullah; Muhammad Idrees; Asma Shaheen; Muhammad Sufyan Javed; Muhammad Kashif Aslam (Advances in Traditional Medicine, 2020)

Assessment of sugar and sugar accumulation-related gene expression profiles reveal new insight into the formation of low sugar accumulation trait in a sweet orange (Citrus sinensis) bud mutant - Syed Bilal Hussain; Ling-Xia Guo; Cai-Yun Shi; Muhammad Abbas Khan; Ying-Xing Bai; Wei Du; Yong-Zhong Liu (Molecular Biology Reports, 2020)

Identification and validation of superior housekeeping gene(s) for qRT-PCR data normalization in Agave sisalana (a CAM-plant) under abiotic stresses - Muhammad Bilal Sarwar; Zarnab Ahmad; Batcho Agossa Anicet; Moon Sajid; Bushra Rashid; Sameera Hassan; Mukhtar Ahmed; Tayyab Husnain (Physiology and Molecular Biology of Plants, 2020)

Groundwater quality assessment for drinking purpose: a case study from Sindh Industrial Trading Estate, Karachi, Pakistan - Muhammad Jahangir Khan; Bilal Ahmed Shah; Bassam Nasir (Modeling Earth Systems and Environment, 2020)

Damage potential of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) on wheat grains stored in hermetic and non-hermetic storage bags - Bilal Atta; Muhammad Rizwan; Arshed Makhdoom Sabir; Muhammad Dildar Gogi; Kazam Ali (International Journal of Tropical Insect Science, 2020)

Identification of wheat (Triticum aestivum L.) genotypes for food safety on two different cadmium contaminated soils - Min Lu; Xuerui Cao; Jianqing Pan; Tingqiang Li; Muhammad Bilal Khan; Hanumanth Kumar Gurajala; Zhenli He; Xiaoe Yang (Environmental Science and Pollution Research, 2020)

Nanozymes for medical biotechnology and its potential applications in biosensing and nanotherapeutics - Samman Munir; Asad Ali Shah; Hazir Rahman; Muhammad Bilal; Muhammad Shahid Riaz Rajoka; Abdul Arif Khan; Mohsin Khurshid (Biotechnology Letters, 2020)

Photocatalytic Performance of Zinc Ferrite Magnetic Nanostructures for Efficient Eriochrome Black-T Degradation from the Aqueous Environment under Unfiltered Sunlight - Ikramullah; Nisar Ali; Farman Ali; Zeshan Ali Sheikh; Muhammad Bilal; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2020)

Photocatalytic Degradation of Congo Red Dye from Aqueous Environment Using Cobalt Ferrite Nanostructures: Development, Characterization, and Photocatalytic Performance - Nisar Ali; Amir Said; Farman Ali; Fazal Raziq; Zarshad Ali; Muhammad Bilal; Laurence Reinert; Tasleem Begum; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2020)

The role of financial development, energy demand, and technological change in environmental sustainability agenda: evidence from selected Asian countries - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir (Environmental Science and Pollution Research, 2020)

Correlation of MLH1 polymorphisms, survival statistics, in silico assessment and gene downregulation with clinical outcomes among breast cancer cases - Saima Shakil Malik; Ayisha Zia; Sumaira Mubarik; Nosheen Masood; Sajid Rashid; Alice Sherrard; Muhammad Bilal Khan; Muhammad Tahir Khadim (Molecular Biology Reports, 2020)

Biomass for renewable energy production in Pakistan: current state and prospects - Muhammad Yaseen; Farhat Abbas; Muhammad Bilal Shakoor; Aitazaz A. Farooque; Muhammad Rizwan (Arabian Journal of Geosciences, 2020)

Synthesis and Application of Titanium Dioxide Nanoparticles for Removal of Cadmium from Wastewater: Kinetic and Equilibrium Study - Muhammad Atif Irshad; Muhammad Bilal Shakoor; Shafaqat Ali; Rab Nawaz; Muhammad Rizwan (Water, Air, & Soil Pollution, 2019)

Thidiazuron-induced efficient biosynthesis of phenolic compounds in callus culture of Ipomoea turbinata Lagasca and Segura - Waqar Ahmad; Adnan Zahir; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (In Vitro Cellular & Developmental Biology - Plant, 2019)

Assessing the immobilization efficiency of organic and inorganic amendments for cadmium phytoavailability to wheat - Yasir Hamid; Lin Tang; Min Lu; Bilal Hussain; Afsheen Zehra; Muhammad Bilal Khan; Zhenli He; Hanumanth Kumar Gurajala; Xiaoe Yang (Journal of Soils and Sediments, 2019)

ATPS: “Aqueous two-phase system” as the “answer to protein separation” for protein-processing food industry - Bilal Muhammad Khan; Kit-Leong Cheong; Yang Liu (Critical Reviews in Food Science and Nutrition, 2019)

The Ameliorative Role of 5-Aminolevulinic Acid (ALA) Under Cr Stress in Two Maize Cultivars Showing Differential Sensitivity to Cr Stress Tolerance - Ume Habiba; Shafaqat Ali; Muhammad Rizwan; Muhammad Bilal Hussain; Afzal Hussain; Pravej Alam; Abdulaziz A. Alqarawi; Abeer Hashem; Elsayed Fathi AbdAllah (Journal of Plant Growth Regulation, 2019)

Composted Sugarcane By-product Press Mud Cake Supports Wheat Growth and Improves Soil Properties - Muhammad Umer Chattha; Muhammad Umair Hassan; Lorenzo Barbanti; Muhammad Bilal Chattha; Imran Khan; Muhammad Usman; Abid Ali; Muhammad Nawaz (International Journal of Plant Production, 2019)

Evaluation of the air pollution tolerance index of ornamentals growing in an industrial area compared to a less polluted area - Iftikhar Ahmad; Bilal Abdullah; John Martin Dole; Muhammad Shahid; Khurram Ziaf (Horticulture, Environment, and Biotechnology, 2019)

Residues of endosulfan in cotton growing area of Vehari, Pakistan: an assessment of knowledge and awareness of pesticide use and health risks - Ashfaq Ahmad; Muhammad Shahid; Sana Khalid; Habiba Zaffar; Tatheer Naqvi; Arshid Pervez; Muhammad Bilal; Muhammad Arif Ali; Ghulam Abbas; Wajid Nasim (Environmental Science and Pollution Research, 2019)

Correction to: Impact assessment of sanitation system on the socio‑economic aspects of local community and environment in Hunza Valley Gilgit Baltistan-Pakistan - Farzana Baig; Muhammad Bilal; Bahadar Nawab; Qaisar Mahmood (International Journal of Energy and Water Resources, 2019)

Comparative efficiency of peanut shell and peanut shell biochar for removal of arsenic from water - Muhammad Sohail Sattar; Muhammad Bilal Shakoor; Shafaqat Ali; Muhammad Rizwan; Nabeel Khan Niazi; Asim Jilani (Environmental Science and Pollution Research, 2019)

Nickel toxicity in plants: reasons, toxic effects, tolerance mechanisms, and remediation possibilities—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Muhammad Aamer; Muhammad Nawaz; Abid Ali; Muhammad Aman Ullah Khan; Tahir Abbas Khan (Environmental Science and Pollution Research, 2019)

Management of green transportation: an evidence-based approach - Bilal Shouket; Khalid Zaman; Abdelmohsen A. Nassani; Abdullah Mohammed Aldakhil; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: The detoxification of heavy metals from aqueous environment using nano-photocatalysis approach: a review - Muhammad Bilal Tahir; Habiba Kiran; Tahir Iqbal (Environmental Science and Pollution Research, 2019)

Chemogenic silver nanoparticles enhance lignans and neolignans in cell suspension cultures of Linum usitatissimum L. - Adnan Zahir; Muhammad Nadeem; Waqar Ahmad; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Thermal Effects on Biochemical Signatures of UHT, Pasteurized and Domestically Boiled Buffalo Milk Detected by Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Saleem; Rahat Ullah; Saranjam Khan; Babar Manzoor Atta; Muhammad Bilal (Journal of Fluorescence, 2019)

Long-term spatiotemporal variations of aerosol optical depth over Yellow and Bohai Sea - Xiaojing Shen; Muhammad Bilal; Zhongfeng Qiu; Deyong Sun; Shengqiang Wang; Weijun Zhu (Environmental Science and Pollution Research, 2019)

Dielectric properties of bones for the monitoring of osteoporosis - Bilal Amin; Muhammad Adnan Elahi; Atif Shahzad; Emily Porter; Barry McDermott; Martin O’Halloran (Medical & Biological Engineering & Computing, 2019)

PM2.5 mapping using integrated geographically temporally weighted regression (GTWR) and random sample consensus (RANSAC) models - Hone-Jay Chu; Muhammad Bilal (Environmental Science and Pollution Research, 2019)

Fulvic Acid Prevents Chromium-induced Morphological, Photosynthetic, and Oxidative Alterations in Wheat Irrigated with Tannery Waste Water - Shafaqat Ali; Muhammad Rizwan; Abdul Waqas; Muhammad Bilal Hussain; Afzal Hussain; Shiliang Liu; Abdulaziz A. Alqarawi; Abeer Hashem; Elsayed Fathi Abd_Allah (Journal of Plant Growth Regulation, 2018)

Endophytic fungus Paecilomyces formosus LHL10 produces sester-terpenoid YW3548 and cyclic peptide that inhibit urease and α-glucosidase enzyme activities - Saqib Bilal; Liaqat Ali; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Sang-Mo Kang; Sang-Kuk Kim; In-Jung Lee (Archives of Microbiology, 2018)

CO2 foam for enhanced oil recovery (EOR) applications using low adsorption surfactant structure - Muhammad Sagir; Muhammad Mushtaq; Muhammad Bilal Tahir; Muhammad Suleman Tahir; Sami Ullah; Khurum Shahzad; Umer Rashid (Arabian Journal of Geosciences, 2018)

Metabolic engineering pathways for rare sugars biosynthesis, physiological functionalities, and applications—a review - Muhammad Bilal; Hafiz M. N. Iqbal; Hongbo Hu; Wei Wang; Xuehong Zhang (Critical Reviews in Food Science and Nutrition, 2018)

Yeast-extract improved biosynthesis of lignans and neolignans in cell suspension cultures of Linum usitatissimum L. - Muhammad Nadeem; Bilal Haider Abbasi; Laurine Garros; Samantha Drouet; Adnan Zahir; Waqar Ahmad; Nathalie Giglioli-Guivarc’h; Christophe Hano (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Role of sorption energy and chemisorption in batch methylene blue and Cu2+ adsorption by novel thuja cone carbon in binary component system: linear and nonlinear modeling - Saeed Rehman; Adnan Adil; Ahsan Jabbar Shaikh; Jehanzeb Ali Shah; Muhammad Arshad; Muhammad Arif Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2018)

Plant growth promoting endophytic fungi Asprgillus fumigatus TS1 and Fusarium proliferatum BRL1 produce gibberellins and regulates plant endogenous hormones - Lubna Bilal; Sajjad Asaf; Muhammad Hamayun; Humaira Gul; Amjad Iqbal; Ihsan Ullah; In-Jung Lee; Anwar Hussain (Symbiosis, 2018)

Tea waste as a potential biowaste for removal of hexavalent chromium from wastewater: equilibrium and kinetic studies - Usman Khalil; Muhammad Bilal Shakoor; Shafaqat Ali; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Enhanced biosynthesis of phenazine-1-carboxamide by Pseudomonas chlororaphis strains using statistical experimental designs - Huasong Peng; Jian Tan; Muhammad Bilal; Wei Wang; Hongbo Hu; Xuehong Zhang (World Journal of Microbiology and Biotechnology, 2018)

A comprehensive study on the surface chemistry of particulate matter collected from Jeddah, Saudi Arabia - Asim Jilani; Syed Zajif Hussain; Mohd Hafiz Dzarfan Othman; Usama Zulfiqar; Muhammad Bilal Shakoor; Imran Ullah Khan; Javed Iqbal; Attieh A. Al-Ghamdi; Ahmed Alshahrie (Journal of Atmospheric Chemistry, 2018)

Effects of biochar on growth, photosynthesis, and chromium (Cr) uptake in Brassica rapa L. under Cr stress - Shafaqat Ali; Muhammad Rizwan; Ruqia Bano; Saima Aslam Bharwana; Muhammad Zia ur Rehman; Muhammad Bilal Hussain; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Ultrasound-assisted adsorption of phenol from aqueous solution by using spent black tea leaves - Asmat Ali; Muhammad Bilal; Romana Khan; Robina Farooq; Maria Siddique (Environmental Science and Pollution Research, 2018)

Activity of acetylcholinesterase and acid and alkaline phosphatases in different insecticide-treated Helicoverpa armigera (Hübner) - Muhammad Bilal; Shoaib Freed; Muhammad Zubair Ashraf; Syed Muhammad Zaka; Muhammad Bismillah Khan (Environmental Science and Pollution Research, 2018)

Sucrose synthase genes: a way forward for cotton fiber improvement - Mukhtar Ahmed; Ahmad Ali Shahid; Sidra Akhtar; Ayesha Latif; Salah ud Din; Ma Fanglu; Abdul Qayyum Rao; Muhammad Bilal Sarwar; Tayyab Husnain; Wang Xuede (Biologia, 2018)

Phytochemical screening and in-vitro evaluation of pharmacological activities of peels of Musa sapientum and Carica papaya fruit - Sarmad Siddique; Shamsa Nawaz; Faqir Muhammad; Bushra Akhtar; Bilal Aslam (Natural Product Research, 2018)

Genome-Wide Analysis of Potassium Transport-Related Genes in Chickpea (Cicer arietinum L.) and Their Role in Abiotic Stress Responses - Farrukh Azeem; Bilal Ahmad; Rana Muhammad Atif; Muhammad Amjad Ali; Habibullah Nadeem; Sabir Hussain; Hamid Manzoor; Muhammad Azeem; Muhammad Afzal (Plant Molecular Biology Reporter, 2018)

Medicinal plant phytochemicals and their inhibitory activities against pancreatic lipase: molecular docking combined with molecular dynamics simulation approach - Bilal Ahmed; Usman Ali Ashfaq; Muhammad Usman Mirza (Natural Product Research, 2018)

Use of statistical analysis to validate ecogenotoxicology findings arising from various comet assay components - Bilal Hussain; Tayyaba Sultana; Salma Sultana; Khalid Abdullah Al-Ghanim; Muhammad Shahreef Masoud; Shahid Mahboob (Environmental Science and Pollution Research, 2018)

Evaluation of Ordinary Least Square (OLS) and Geographically Weighted Regression (GWR) for Water Quality Monitoring: A Case Study for the Estimation of Salinity - Majid Nazeer; Muhammad Bilal (Journal of Ocean University of China, 2018)

Toxicological Assessment and UV/TiO2-Based Induced Degradation Profile of Reactive Black 5 Dye - Muhammad Bilal; Tahir Rasheed; Hafiz M. N. Iqbal; Hongbo Hu; Wei Wang; Xuehong Zhang (Environmental Management, 2018)

Engineering Pseudomonas for phenazine biosynthesis, regulation, and biotechnological applications: a review - Muhammad Bilal; Shuqi Guo; Hafiz M. N. Iqbal; Hongbo Hu; Wei Wang; Xuehong Zhang (World Journal of Microbiology and Biotechnology, 2017)

DHI evaluation by combining rock physics simulation and statistical techniques for fluid identification of Cambrian-to-Cretaceous clastic reservoirs in Pakistan - Nisar Ahmed; Perveiz Khalid; Hafiz Muhammad Bilal Shafi; Patrick Connolly (Acta Geophysica, 2017)

Groundwater status in Pakistan: A review of contamination, health risks, and potential needs - Maimoona Raza; Fida Hussain; Jin-Yong Lee; Muhammad Bilal Shakoor; Kideok D. Kwon (Critical Reviews in Environmental Science and Technology, 2017)

Foliar application of aspartic acid lowers cadmium uptake and Cd-induced oxidative stress in rice under Cd stress - Muhammad Rizwan; Shafaqat Ali; Muhammad Zaheer Akbar; Muhammad Bilal Shakoor; Abid Mahmood; Wajid Ishaque; Afzal Hussain (Environmental Science and Pollution Research, 2017)

Reaction Mechanism and Degradation Pathway of Rhodamine 6G by Photocatalytic Treatment - Tahir Rasheed; Muhammad Bilal; Hafiz M. N. Iqbal; Hongbo Hu; Xuehong Zhang (Water, Air, & Soil Pollution, 2017)

Evaporation modelling using different machine learning techniques - Lunche Wang; Ozgur Kisi; Bo Hu; Muhammad Bilal; Mohammad Zounemat‐Kermani; Hui Li (International Journal of Climatology, 2017)
Accurate prediction of pan evaporation ( Ep ) is critical for water resource management. This article investigates the capabilities of three different soft computing methods at estimating monthly Ep at six stations in the Yangtze River Basin using climatic factors, including the air temperature ( Ta ), solar radiation ( Rg ), air pressure ( Pa ) and wind speed ( Ws ) for the period of 1961–2000. The first part of the study focused on testing and comparing model accuracy levels at each station using local input combinations. The results indicate that the fuzzy genetic ( FG ) model generally produces better results than adaptive neuro‐fuzzy inference systems with grid partition (ANFIS‐GP) and M5 model tree ( M5Tree ) specifications in terms of the root mean square error , mean absolute error and coefficient of determination values. The performance of the above models was also examined using cross‐station applications (estimating Ep without local input or output data) in the second part of the study. The third part focused on estimating Ep using generalized FG , ANFIS‐GP and M5Tree models. Collectively, the results demonstrate that the FG model can be successfully used to estimate Ep without any local inputs and outputs and that a single generalized FG model can also be used at six different locations.

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Vulnerability assessment of an agro-stressed aquifer using a source-pathway-receptor model in GIS - Yawar Hussain; Sadia F. Ullah; Abdul Q. Aslam; Muhammad B. Hussain; Gulraiz Akhter; Hernan E. Martinez-Carvajal; Frédéric Satgé; Arshad Ashraf; Bilal Iqbal; Martin Cárdenas-Soto (Modeling Earth Systems and Environment, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Bio-based degradation of emerging endocrine-disrupting and dye-based pollutants using cross-linked enzyme aggregates - Muhammad Bilal; Muhammad Asgher; Hafiz M. N. Iqbal; Hongbo Hu; Xuehong Zhang (Environmental Science and Pollution Research, 2017)

Microelectrophoretic study of environmentally induced DNA damage in fish and its use for early toxicity screening of freshwater bodies - Bilal Hussain; Tayyaba Sultana; Salma Sultana; K. A. Al-Ghanim; Shahreef Masood; Muhammad Ali; Shahid Mahboob (Environmental Monitoring and Assessment, 2017)

Correlation of Cadmium and Magnesium in the Blood and Serum Samples of Smokers and Non-Smokers Chronic Leukemia Patients - Noman Khan; Hasan Imran Afridi; Tasneem Gul Kazi; Muhammad Balal Arain; Muhammad Bilal; Asma Akhtar; Mustafa Khan (Biological Trace Element Research, 2017)

Chromium Exposure in the Adult Population, Consuming Different Types of Smokeless Tobacco Products in Pakistan - Asma Akhtar; Hasan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Sadaf Sadia Arain; Jameel Ahmed Baig; Noman Khan; Mustafa Khan; Muhammad Bilal (Biological Trace Element Research, 2017)

Vortex-assisted ionic liquid-based dispersive liquid–liquid microextraction for assessment of chromium species in artificial saliva extract of different chewing tobacco products - Asma Akhtar; Tasneem Gul Kazi; Hassan Imran Afridi; Syed Ghulam Musharraf; Farah Naz Talpur; Noman Khan; Muhammad Bilal; Mustafa Khan (Environmental Science and Pollution Research, 2016)

First report on fish cysteine as a biomarker of contamination in the River Chenab, Pakistan - Bilal Hussain; Tayyaba Sultana; Salma Sultana; Shahid Mahboob; Muhammad Farooq; Khalid Al-Ghanim; Shahid Nadeem (Environmental Science and Pollution Research, 2016)

Phytochemistry of Daphne oleoides - Muhammad Riaz; Asma Saleem; Shabana Siddique; Bilal Ahmad Khan; Mohammad Nur-e-Alam; Syed Shahzad-ul-Hussan; Ghulam Abbas Miana; Muhammad Qayyum Khan (Natural Product Research, 2016)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

Study of physio-psychological effects on traffic wardens due to traffic noise pollution; exposure-effect relation - Shamas Tabraiz; Saeed Ahmad; Iffat Shehzadi; Muhammad Bilal Asif (Journal of Environmental Health Science and Engineering, 2015)

Interactive effects of melatonin and light on growth parameters and biochemical markers in adventitious roots of Withania somnifera L. - Muhammad Adil; Bilal Haider Abbasi; Tariq Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Heterogeneous expansion of end-moraine dammed lakes in the Hindukush-Karakoram-Himalaya ranges of Pakistan during 2001–2013 - Arshad Ashraf; Rozina Naz; Muhammad Bilal Iqbal (Journal of Mountain Science, 2015)

Response of nitrogen assimilating enzymes during in vitro culture of Argyrolobium roseum - Darima Habib; Muhammad Zia; Yamin Bibi; Bilal Haider Abbasi; Muhammad Fayyaz Chaudhary (Biologia, 2015)

EDTA enhanced plant growth, antioxidant defense system, and phytoextraction of copper by Brassica napus L. - Ume Habiba; Shafaqat Ali; Mujahid Farid; Muhammad Bilal Shakoor; Muhammad Rizwan; Muhammad Ibrahim; Ghulam Hasan Abbasi; Tahir Hayat; Basharat Ali (Environmental Science and Pollution Research, 2015)

Time-course changes in growth and biochemical indices of mung bean [Vigna radiata (L.) Wilczek] genotypes under salinity - Syed Hammad Raza; Muhammad Bilal Ahmad; Muhammad Arslan Ashraf; Fahad Shafiq (Brazilian Journal of Botany, 2014)

EDTA ameliorates phytoextraction of lead and plant growth by reducing morphological and biochemical injuries in Brassica napus L. under lead stress - Urooj Kanwal; Shafaqat Ali; Muhammad Bilal Shakoor; Mujahid Farid; Sabir Hussain; Tahira Yasmeen; Muhammad Adrees; Saima Aslam Bharwana; Farhat Abbas (Environmental Science and Pollution Research, 2014)

In vitro callogenesis and detection of somaclonal variations in Plantago ovata L. - Tariq Mahmood; Aysha Jameel; Bilal Haider Abbasi; Faiza Munir; Syed Muhammad Saqlan Naqvi (Journal of Crop Science and Biotechnology, 2012)

Factors affecting yield and composition of camel milk kept under desert conditions of central Punjab, Pakistan - Sibtain Ahmad; Muhammad Yaqoob; Muhammad Qamar Bilal; Muhammad Kasib Khan; Ghulam Muhammad; Li-Guo Yang; Muhammad Tariq (Tropical Animal Health and Production, 2012)

Risk factors associated with prevalence and major bacterial causes of mastitis in dromedary camels (Camelus dromedarius) under different production systems - Sibtain Ahmad; Muhammad Yaqoob; Muhammad Qamar Bilal; Ghulam Muhammad; Li-Guo Yang; Muhammad Kasib Khan; Muhammad Tariq (Tropical Animal Health and Production, 2012)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

Assessment of genetic variability among selected species of Apocynaceae - Tariq Mahmood; Anna Iqbal; Nazia Nazar; Ishrat Naveed; Bilal Haider Abbasi; Syed Muhammad Saqlan Naqvi (Biologia, 2011)

Efficient regeneration and antioxidant potential in regenerated tissues of Piper nigrum L. - Nisar Ahmad; Hina Fazal; Bilal Haider Abbasi; Muhammad Rashid; Tariq Mahmood; Nighat Fatima (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Shoot regeneration and free-radical scavenging activity in Silybum marianum L. - Bilal Haider Abbasi; Mubarak Ali Khan; Tariq Mahmood; Mushtaq Ahmad; Muhammad Fayyaz Chaudhary; Mir Ajab Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Heavy Metal Residues in the Milk of Cattle and Goats During Winter Season - Ijaz Javed; Ibadullah Jan; Faqir Muhammad; Zia-ur-Rahman; M. Zargham Khan; Bilal Aslam; Javed Iqbal Sultan (Bulletin of Environmental Contamination and Toxicology, 2009)